Proteomic and metabolomic analysis of Litopenaeus vannamei infected with infectious hypodermal and hematopoietic necrosis virus (IHHNV) - Fan Yang; Shou-Xin Luo; Zhi-Peng Yin; Ling-Jun Si; Ting Li; Lin-Rui Chang; Dong-Chun Yan (Aquaculture, 2027)

Nitrate photolysis as major summer daytime sources of ambient HONO in Southeastern Coastal China - Ziying Chen; Feng Zhang; Lingling Xu; Ziyi Lin; Xiuwen Yong; Yuping Chen; Gaojie Chen; Xiaoting Ji; Xiaolong Fan; Lingjian Wang; Mengren Li; Jinsheng Chen (Atmospheric Research, 2026)

Mitogenomes of three Sinoxylon species and phylogenetic analysis of Bostrichoidea (Coleoptera) - Hua-Min Fan; Xiao-Yun Wang; Kai Lin; Qian Lu; Qiu-Hong Tao; Jun Li; Xia-Lin Zheng (Molecular Genetics and Genomics, 2026)

Ferroptosis-related ceRNA axis regulates the apoptosis and proliferation of uveal melanoma cells through MAPRE2 - Hai-Bo Wang; Li Dong; He-Yan Li; Xin Liu; Fan Zhang; Lin-Hui Yuan; Wen-Bin Wei (Functional & Integrative Genomics, 2026)

Hydrogeochemical characteristics, salinization, and irrigation suitability assessment of coastal groundwater in Hainan Island, China - Yongsheng Lin; Shengzhang Zou; Li Lu; Xianyu Wei; Lianjie Fan; Jinhui Liu (Marine Pollution Bulletin, 2026)

Tracking global extreme afternoon photosynthesis depression: Frequency, duration, and drivers from satellite-based hourly GPP products - Jingyu Lin; Xing Li; Xiaojun Li; Xuanlong Ma; Lei Fan; Sadegh Ranjbar; Jing M. Chen (Remote Sensing of Environment, 2026)

DlERF98 transcription factor mediates salicylic acid-induced disease resistance in postharvest longans by activating phenylpropanoid metabolism - Qi Chen; Zhongqi Fan; Ruiling Zhuo; Yifen Lin; Hui Wang; Boqiang Li; Shiping Tian; Mengshi Lin; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2026)

New perspectives on the role of oil-gas in mineralization of sandstone-hosted uranium deposits: Carbonate evidence from Yuejin Ⅱ, Qaidam Basin, China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Zhi-Lin Cheng; Zhao-Hui Li; Xue-Feng Gao; Ping Feng (Journal of Asian Earth Sciences, 2026)

Effects of sustained eccentric loading on concrete-encased concrete-filled steel tubular (CFST) columns - Zhi-Cheng Yang; Di Fan; Guan-Yuan Zhao; Li Zhu; Lin-Hai Han; Chen-Yu Zhang (Engineering Structures, 2026)

A VR-treadmill-EEG laboratory method for studying effects of human activity states on thermal comfort in different types of large-scale public buildings - Zheng Li; Xinling Jin; Guoqing Song; Qingwen Zhang; Bintian Lin; Ankita Yonzan; Tianli Xu; Feng Fan (Energy and Buildings, 2026)

Typhoons-induced destruction and rapid reconstruction of the summer coastal upwelling system on a typical upwelling developing area: A case study in the Taiwan Strait - Xiaofang Fan; Fangfang Shu; Binxin Zheng; Yunpeng Lin; Yuting Lin; Fusheng Luo; Yunhai Li (Continental Shelf Research, 2026)

Poly(phenol-imidazole) nanosheets engineered multifunctional hydrogel for promotion of infected diabetic wound healing - Jia Xin Yu; Lu Yao Li; Yu Fan; Piao Zheng; Sha Yang; Qi Fang Liu; Cai Juan Huang; Ya Lin Cao; Yang You (Chemical Engineering Journal, 2026)

Idealized simulations reveal the potential for widespread high supersaturation in marine tropical deep convection - Chunying Fan; Siwei Li; Lin Zang; Zengxin Pan; Feiyue Mao; Fan Liu; Wei Gong; Daniel Rosenfeld (Atmospheric Research, 2026)

Intensifying aridity shapes network patterns of soil bacterial communities and geographical distribution of sensitive functional groups in grasslands and farmlands on the Loess Plateau - Jia Wang; Xinyi Guo; Yuru Gao; Kang Zhang; Zhen Yang; Xin Zhao; Jushui Hu; Junyao Deng; Jiaqing Liu; Li Li; Peng Shi; Yanbing Lin; et al. (Applied Soil Ecology, 2026)

SERS sensing platform based on MIL-100(Fe)@AgNPs for norepinephrine/adenosine monitoring in patient plasma - Peng Zhao; Kai Liu; Yueyan Li; Xiaofang Ban; Yuheng Wu; Jiaqi Liu; Xiaohong Wu; Ziyi Cheng; Fan Wang; Shuo Li; Feng Lin; Huifang Tang; et al. (Analytica Chimica Acta, 2026)

Lactiplantibacillus plantarum LP15-1 alleviates deoxynivalenol-induced intestinal injury in mice by inhibiting ferroptosis and modulating the gut microbiota - Kunru Teng; Jiefeng Li; Beibei He; Dan Song; Tao Duan; Kuanbo Liu; Lin Qiao; Aike Li; Weiwei Wang; Shijie Fan (Toxicon, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Single-site amino acid residue mutation reshapes the characteristics of double bond positions for protostadienol-type triterpenols - Pengyang Lin; Yunpeng Wang; Bing Li; Xuebingting Zhang; Baolian Fan; Ruoshi Huang; Zhongju Ji; Fan Zhang; Jingcai Liang; Lixin Duan (Phytochemistry, 2026)

Paleoenvironmental shifts shape the dispersal and persistence of Urticaceae in karst tiankeng microrefugia of South China - Yingfei Pan; Feng Chen; Yuxin Dai; Fan Lin; Zhenhai Deng; Lu Li; Liwen Li; Tongfang Sun; Jiaojiao Zhang; Hao Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mechanistic bifurcation and coordination modification in peroxymonosulfate activation by cobalt catalysts - Yan Zhao; Fan Wu; Xiaojiao Chen; Yingyi Wang; Li Hui; Hong Lin (Journal of Environmental Chemical Engineering, 2026)

Preparation of Ag/CuV2O6 nanowires and investigation of the delayed antibacterial effect of fluorescent materials on photocatalysts - Xu Li; Yifang Zhang; Qiao Xia; Jiye Fan; Huaxiang Lin; Rusheng Yuan; Jinlin Long (Journal of Environmental Chemical Engineering, 2026)

Enhanced simultaneous nitrogen and phosphorus removal via a step-feed anoxic/oxic process coupled with side-stream enhanced biological phosphorus removal - Ruoyu Wu; Dongqi Wang; Mengbo Huang; Yanzhe Gong; Guangxiang Duan; Jiayu Bi; Wengui Gu; Lu Qin; Yuan Guo; Xiaopeng Qiu; Yishan Lin; Da Kang; et al. (Journal of Environmental Chemical Engineering, 2026)

Orbital forcing of lacustrine shale deposition and organic matter enrichment: Insights from the Eocene Shahejie Formation in the Dongying Sag, Bohai Bay Basin, China - Zhenhe Wang; Juye Shi; Quanyou Liu; Tailiang Fan; Zhiqian Gao; Gongda Li; Xinyue Lin; Zhenqian Yang; Zhijun Jin (Journal of Asian Earth Sciences, 2026)

Metabolic complementarity and enhanced biofilm formation drive the synergistic symbiosis of lactic acid bacteria and yeast in Tibetan kefir - Liangli Wu; Jianwei Zang; Luyao Xiao; Chang Xu; Xia Fan; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Tao Lin; Wei Li (International Dairy Journal, 2026)

Gut microbiota-derived SCFAs mediate the intestinal anti-aging effect of structurally characterized Dendrobium officinale glucomannan via Treg immune regulation in mice - YingJie Dong; Yawen Sun; Minqiu Lin; Fan Liu; Jiayue Zhu; Bo Li; Guiyuan Lv; Suhong Chen (Food Research International, 2026)

Effects of clay jar and stainless steel fermentation on microbial succession and flavor formation in spontaneously fermented Cabernet Sauvignon wine - Fan Yang; Lin Pan; Ru Zhai; Fuqi Li; Wen Li; Kaixiong Li (Food Bioscience, 2026)

Mechanisms and applications of multifunctional low-temperature plasma technology for enhancing food safety - Jun Yan; Xue Yuan; Marie-Laure Fauconnier; Xiaoming Fang; Zhiqiang Kong; Lin Li; Bei Fan; Jesus Simal-Gandara; Minmin Li (Food Control, 2026)

Fermentation of ginseng juice by Lactiplantibacillus plantarum SP055 and Limosilactobacillus fermentum LB-9: Fermentation characteristics and ginsenoside biotransformation pathways - Jianwei Zang; Wei Liu; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Yimeng Kou; Chunling Meng; Jiamin Xu; Tao Lin; Xin Rui; Dan Gan; et al. (Food Microbiology, 2026)

Synergistic effects of dimethyl sulfoxide and water in hydrothermal carbonization of poplar form spheric hydrochar with enhanced yields - Haisheng Lin; Mengjiao Fan; Chao Li; Yuchen Jiang; Lijun Zhang; Shu Zhang; Xun Hu (Biomass and Bioenergy, 2026)

Forchlorfenuron (CPPU) suppresses fruitlet abscission in Areca catechu by modulating carbohydrate allocation, hormonal dynamics, and lignin biosynthesis - Lin-Kai Wang; Wen-Cheng Fan; Han Gong; Dong-Xia Li; Li-Yun Liu; Meng Li; Jia Li (Planta, 2026)

Multi-dimensional coupling framework for soil salinity assessment: Revealing spatiotemporal interactions among soil, environment, and cotton growth - Bowei Xu; Jiajie Yang; Rumeng Zhao; Jilian Li; Xinzhu Ning; Fuguang Li; Hai Lin; Zuoren Yang; Liqiang Fan (Agricultural Systems, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Quality-aware generative distillation for robust and efficient livestock detection - Jin Liu; Weinan Hong; Lei Yao; Fanrong Kong; Zipei Fan; Lin Lei; Yuanqian Ma; Xinwei Li (Computers and Electronics in Agriculture, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Interferon-tau regulates the PGE2/PGF2α ratio via ISG15 in the goat corpus luteum during early pregnancy - Chunmei Shang; Haokun Liu; Zuhui Li; Yuanmeng Mou; Chenling Fan; Shan Liu; Yaping Jin; Pengfei Lin (Theriogenology, 2026)

Leaf cell wall mechanics reveal contrasting patterns of structural persistence and tissue plasticity in two temperate tree species - Zeyu Lin; Dayong Fan; Xingyue Li; Xiangping Wang (Plant Science, 2026)

Experimental study of a dual-chain transmission hybrid power generation wave energy converter - Chenglong Li; Guojun Pan; Hui Li; Beichen Lin; Shaohui Yang; Weiwei Fan; Xianbin Yan (Ocean Engineering, 2026)

Quaternary submarine slope gullies on the northern South China Sea margin: Architecture, initiation, and evolution - Zhina Wang; Haiteng Zhuo; Zhen Sun; Zhenyu Zhu; Xiujuan Wang; Ming Su; Jie Li; Qi Fan; Shan Liu; Zhixuan Lin (Marine Geology, 2026)

Organophosphate flame retardants and incident type 2 diabetes: Integrating population evidence, mechanistic insights, and effect modification by healthy lifestyle - Xueyan Wu; Yilin Zhou; Yue Nie; Haoran Xu; Hengrui Liu; Mengke Cheng; Yao Guo; Fangyuan Lin; Xin Tang; Peihan Chen; Dandan Wei; Jian Hou; et al. (Journal of Hazardous Materials, 2026)

Fungal necromass dominates soil organic carbon accrual after decadal active restoration of alpine grassland - Shijie Zhou; Jinchao Gong; Keqi Fan; Abraham Allan Degen; Jingjing Wu; Xiongkui Lin; Tahmina Kausar; Yue Xiu; Linlin Li; Liang Tie; Ziwei Yang; Congyu Ma; et al. (Journal of Environmental Management, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Change detection-based machine learning for earthquake-triggered landslide identification in complex mountain landscapes - Lin Wang; Limin Zhang; Feng Cheng; Xiwei Fan; Shuang Li (Geomorphology, 2026)

Fe2+ alters carbon and nitrogen metabolic networks in a composite microbial consortium: Metagenomic insights into the shift from denitrification to DNRA - Lin Zhang; Bowei Zhao; Xiao Zhang; Yuan Li; Haibo Li; Shuying Yuan; Haoxiang Ning; Bingcheng Lv; Le Li; Xiaojun Fan; Xiuping Yue (Environmental Research, 2026)

Seasonal variations in air-sea interface processes and water column biogeochemical regulation mechanisms of PAHs in the South China Sea - Jingwen Shi; Ye Li; Yina Tanli; Mengyang Liu; Yan Lin; Lin Zhang; Mingjun Feng; Hongwei Ke; Xiangrong Xu; Zi-Feng Zhang; Yi-Fan Li; Xuehong Zheng; et al. (Environmental Research, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Spatiotemporal radical engineering via non-destructive synchrotron lithography for multimodal functionalization of inert polymers - Hao Zhang; Xincheng Xie; Shengbin Cao; Fan Zhang; Lin Da; Yang Liu; Bomin Liu; Feng Tian; Caizhen Zhu; Xiuhong Li; Jian Xu (Chemical Engineering Journal, 2026)

Environment-responsive multi-enzymed Cu/Cu2O@NC nanorhombic nanoplatform for infected wound antimicrobial treatment - Ji Cheng; Hao Zhang; Yueting Jiang; Zuojia guo; Rui Liu; Xiantao Lin; Hanjin Lu; Yunjun zhang; Wenxuan Fan; Ding Luo; Jinghua Li (Chemical Engineering Journal, 2026)

Built-in electric field-driven d-band engineering in metal sulfide heterojunctions for high-efficiency electro-Fenton degradation of antibiotics - Xiangwei Zou; Yue Wang; Xinyu Wang; Lin Lin; Xiao-yan Li; Chitou Lei; Xiaojun Fan; Weng Ian Ieong; Qinfen Gu; Lianpeng Sun; Chao Yang (Chemical Engineering Journal, 2026)

Pd single atoms anchored on mesoporous C3N5: An exceptional photocatalyst for hydrogen production - Yang Wang; Cun-Feng Fan; Jiao-Yan Li; Xiao-Qin Zheng; Xuan-Yi Liu; Ying Zhou; Jiahui Kou; Hengming Huang; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Diagnosing apparent hydraulic memory in pressurized slug tests with a lagging theory framework - Ying-Fan Lin; Li-Chen Cheng (Advances in Water Resources, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Stakeholder priorities dominate the evaluation of climate change impacts on ecosystem-service multifunctionality - Xin Jing; Hao Wang; Wei Xu; Xiaomin Fan; Lin Jiang; Yu Li; Zhiyuan Ma; Peter Manning; Nathan J. Sanders; Bernhard Schmid; Yunfeng Yang; Zhenhua Zhang; et al. (Science China Life Sciences, 2026)

Apigenin in TMG inhibits colorectal tumorigenesis by targeting GSK3β/APC/β-catenin signaling pathway - Mei Li; Wei Wang; Renjing Lin; Fan Hu; Chongsi Xu; Biao Xie (In Vitro Cellular & Developmental Biology - Animal, 2026)

Robust long-range obstacle detection in farmland via LiDAR-Camera fusion and cascaded ground filtering - Wenyu Zhang; Yuexin Lin; Qingrong Huang; Fan Ding; Xiwen Luo; Zhigang Zhang; Lian Hu; Yuchi Deng; Jianming Wu; Jiehao Li (Computers and Electronics in Agriculture, 2026)

Prediction of energy consumption and carbon emission in Yunnan Province based on LEAP modeling - Zhengyuan Fan; Jie Yu; Taiwei Gu; Cui Qiao; Shaoyuan Li; Lin Ma; Wenhui Ma (Utilities Policy, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Irregular-wave transformation over an open-top artificial reef with low-opening-ratio baffles under variable relative submergence - Hongyi Li; Cuiping Kuang; Jiadong Fan; Jilong Chen; Xin Cong; Lin Li (Ocean Engineering, 2026)

Janus composite membranes for suppressing thermal wetting in membrane distillation of flue gas desulfurization wastewater - Xinxin Lin; Qiaoling Ye; Binbin Li; Huiyi Cai; Caiyi Fan; Zhongsen Yan (Journal of Water Process Engineering, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Co-activation and signal crosstalk between parthanatos and mitophagy in light-induced retinal injury - Yu-Lin Li; Si-Ming Zhang; Bin Fan; Guang-Yu Li (Journal of Photochemistry and Photobiology B: Biology, 2026)

Local polarization-piezoelectric field promotes water dissociation for efficient fluorinated pollutants defluorination - Yi Liu; Zhikui Zhou; Yuhang Xu; Xinyu Liu; Ying Zhou; Zixiang Lin; Ning Li; Li Yang; Xiaoyun Fan (Journal of Hazardous Materials, 2026)

Structure, digestive fate and gut metabolic activity of longan polysaccharide prepared by fermentation of Ligilactobacillus salivarius XIF24 - Lei Pan; Fan Zhang; Yaqing Lin; Lin Wang; Shaodan Peng; Jihua Li; Wei Zhou (Food Bioscience, 2026)

Acidified freshwater disrupts skeletal mineralization and bone remodeling gene expression in zebrafish (Danio rerio) larvae - Chia-Hao Lin; Jun-Yi Wang; Ming-Fan Li; Hsuan-Yi Hsu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Construction of conductive polyimide dressings for accelerated wound healing via an interfacial compatibility optimization and polyelectrolyte complexation synergistic strategy - Lizhi Lin; Kexiang Fan; Hang Luo; Jueying Yang; Huaping Liang; Yongqiang Feng; Lijie Li; Kelin Peng; Yu Chen (Chemical Engineering Journal, 2026)

A-site Yb-doped CaMnO3-δ perovskite as a Co-/Sr-free oxygen electrode with enhanced conductivity and stability for solid oxide fuel cells - Qun Yang; Rengang Li; Jingxuan Hao; Hongpeng Fan; Yucheng Zhang; Yue Hu; Xiao Lin; Linjuan Zhang; Dehua Zheng; Zaifeng Li; Jian-Qiang Wang (Chemical Engineering Journal, 2026)

ANN-assisted interfacial engineering of MOFs heterostructures for synergistic CO2 photoreduction and antibiotic elimination - Fan Ye; Zhe Lin; Xu-Chao Xia; Ting Zou; Jin-Yu Dai; Lin Zhang; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2026)

Steric hindrance modulation in covalent triazine frameworks enables ultrahigh SO2 and SF6 capture - Xiaoyu Wang; Zhaosheng Fan; Lin Hu; Chang Liu; Xiaocui Xie; Xiaojuan Gu; Mingxuan Liu; Yixian Du; Xu Yan; Chen Chen; Xiongli Liu; Lin Li; et al. (Chemical Engineering Journal, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Influence of Multi-field Coupling Effect on Coal Porosity in the Process of Liquid Nitrogen Fracturing in Watery Coal - Cheng Wang; Li Liu; Yongfei Jin; Yiru Fan; Haifei Lin; Min Yan; Chi-Min Shu (Natural Resources Research, 2026)

Atmospheric gaseous HCl influenced by sea-land breeze circulation in a southeast Chinese coastal city - Xiaolong Fan; Lei Yao; Yee Jun Tham; Chen Yang; Yuping Chen; Huiwen Chen; Gaojie Chen; Ziyi Lin; Youwei Hong; Mengren Li; Lingling Xu; Jinsheng Chen (ENGINEERING Environment, 2026)

Population Decline, Inbreeding and Hybridization Shape the Genetic Vulnerability of a Critically Endangered Seabird - Guoling Chen; Chenqing Zheng; Lanhui Peng; Hongzhou Lin; Feng Dong; Shou‐Hsien Li; Yiwei Lu; Siyu Wang; Zhongyong Fan; Yinan Fu; Peng Ding; Jian Zhang; et al. (Molecular Ecology, 2026)
Many endangered species have been rescued from the brink of extinction, yet their long‐term viability remains uncertain due to the prolonged genetic consequences of severe bottlenecks. In particular, the combined effects of inbreeding and hybridization with closely related species remain poorly understood. Using a comparative conservation genomic framework, we investigated these issues in the Chinese crested tern ( Thalasseus bernsteini ), a critically endangered seabird once presumed extinct but which has increased to approximately 100 individuals over the past two decades and its close relative, the great crested tern ( T. bergii ). We demonstrate that the Chinese crested tern has experienced ongoing genetic erosion. Its prolonged population decline has intensified genetic drift and reduced the efficiency of purifying selection, resulting in genome‐wide accumulation of highly deleterious mutations. Highly inbred individuals also carry significantly more homozygous deleterious mutations than less inbred individuals. In both species, runs of homozygosity (ROH) show a relative enrichment of moderately and weakly deleterious mutations. Even more concerning, we found an enrichment of moderately and weakly deleterious mutations in putatively introgressed regions in both species, suggesting that occasional hybridization may have facilitated the spread of deleterious variants and could potentially compromise long‐term fitness. These findings highlight that severe bottlenecks have lasting genomic consequences and that both inbreeding and hybridization can increase the genetic vulnerability of small populations—underscoring the importance of management strategies that promote population growth and sustained genetic monitoring.

Temperature and osmotic pressure dual-stimuli-responsive ophthalmic gels embedded with HPCD-modified nanoparticles for prolonged-release delivery of natamycin - Bixia Lin; Fangfei Fan; Hui Xu; Xin Li; Yufei Li; Chunya Qin; Xiaoyun Zhang; Shiqiang Zhang; Yang Gao; Lirong Niu (Drug Delivery and Translational Research, 2026)

Numerical Simulation of Hydraulic Fracturing in Bedding Reservoir Rocks with Natural Fractures - Li Fan; Yibo Wang; Xiaoning Wang; Shaojiang Wu; Jianghao Lin (Rock Mechanics and Rock Engineering, 2026)

Agmatine induces mitophagy via the PTS-I2R pathway to increase autophagic flux and attenuate sepsis-induced intestinal epithelial cell apoptosis - He Jin; Shuangqin Yin; Yongming Li; Xiangwei Hou; Lin Qiao; Tianyin Kuang; Jing Zhou; Xue Yang; Wanting Zeng; Chao Fan; Li Luo; Lihui Wang; et al. (Inflammation Research, 2026)

Two new monoterpene glycosides from the endophytic fungus Diaporthe nobilis and their cytotoxic effects - Ying Chen; Jian Wang; Cai-Lin Zhao; Xiu-Feng Yang; Jin Ye; Lin-Ping Zhang; Yun-Xiao Li; Fan-Wei Liu; Le Zhang; Bo Song (Natural Product Research, 2026)

Hemodynamic decoding for multimodal connected cardiovascular healthcare - Yun Ke; Ruijun Pan; Jun Li; Wanghuai Xu; Dalong Ni; Zhou Li; Zhong Lin Wang; Fan Yang (Science Bulletin, 2026)

Is BPA only the tip of the iceberg? Occurrence and risk assessment of 32 bisphenol analogues in landfill leachate - Zhi-Zhong Zhang; Lin-Hui Zhang; Hang Li; Fei Chen; Sakhayana Nikolaevna Danilova; Ming-Han Li; Bing-Feng Liu; Yi-Fan Li; Zi-Feng Zhang (Journal of Hazardous Materials, 2026)

H3K18 lactylation-regulated ATG10 is involved in the acute respiratory distress syndrome induced by acute exposure to hydrogen sulfide through activation of autophagy in lung epithelial cells - Bingyu Ling; Ping Geng; Bowen Fan; Xiaolong Wu; Yi Yang; Jiaheng Lin; Wenjie Li; Qizhan Liu; Cheng Cheng; Jinsong Zhang; Hao Wu (Journal of Hazardous Materials, 2026)

Immobilized Ni-Ce bimetal catalysts enhanced ozonation oxidation of refractory organics in swine wastewater - Pei Wang; Zhu Liang; Qiushi Li; Xiao-yan Li; Kaimin Shih; Xiaojun Fan; Chitou Lei; Lin Lin (Journal of Hazardous Materials, 2026)

How policy constraints reshape systematic conservation planning: evidence from ecosystem services, biodiversity co-representation, and ecological connectivity in the Yangtze River Basin - Ziang Tian; Shiliang Liu; Jiayi Lin; Wanting Wang; Yetong Li; Yifei Zhao; Zechen Wang; Miaomiao Liu; Jingyang Fan; Yuhong Dong; Lam‐Son Phan Tran; Gang Wu (Journal of Cleaner Production, 2026)

Tropical-origin lactic acid bacteria co-fermentation enables protein network restructuring and glucose-lipid metabolic regulation in coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Xia Fan; Xin Rui; Tao Lin; Wei Li (Innovative Food Science & Emerging Technologies, 2026)

Beyond saponins: An integrated mass spectrometry strategy for profiling, spatial mapping, and rapid authentication of non-saponin constituents in Panax species - Wenxiang Fan; Ziwei Li; Longchan Liu; Linnan Li; Rufeng Wang; Zhengtao Wang; Qiong Lai; Lin Zheng; Li Yang (Food Research International, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

A tropical fermented-food-derived Lactiplantibacillus plantarum SP055 alleviates DSS-induced colitis through coordinated regulation of gut microbiota and intestinal barrier function - Jianwei Zang; Yibo Shi; Xiaotong Hao; Xia Fan; Yimeng Kou; Wanxiang Zhang; Luyao Xiao; Chang Xu; Tao Lin; Xin Rui; Dan Gan; Wei Li (Food Bioscience, 2026)

Unveiling sulfur-vacancy-induced electron transfer pathways in FeNi2S4 steering peroxydisulfate activation from radical to non-radical oxidation - Yuansheng Wang; Xueming Lin; Zhicong Lan; Jiayi Li; Honghao Zeng; Hanyun Zhang; Min Yu; Jiaqu Tan; Dongya Li; Fan Yang (Chemical Engineering Journal, 2026)

Synergistic atomic-level anchoring and pore engineering of cobalt-nitrogen-carbon for anti-fouling and robust capacitive deionization - Huakun Pan; Haodong Zhang; Xinxi Teng; Yang Fan; Yaming Wang; Lin Li; Guisong Zhang; Meiling Liu; Haiou Song; Aimin Li; Shupeng Zhang (Chemical Engineering Journal, 2026)

Root-mediated oxygen transfer drives Methylobacter enrichment and secondary alcohol metabolism to strengthen chlorobenzene degradation in landfill rhizosphere systems - Liang-jie Li; Yu-fan Liu; Zhi-lin Xing; Kun Cao; Tian-tao Zhao (Biomass and Bioenergy, 2026)

Variable effect of soil biota on phosphorus mobilization and acquisition strategies of different crop species - Yuanyuan Fan; Xinyue Ma; Wei Yuan; Lin Zhang; Chaochun Zhang; Haigang Li; Chunjie Li (Plant and Soil, 2026)

Resveratrol synergizes with chloroquine to inhibit the malignant progression of oral squamous cell carcinoma by regulating KIF11 - Jianfeng Dong; Qing Zhu; Xuhui Fan; Shuning Li; Lin Lu; Guojie Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Tinosporoside E and tinosporane A: two new clerodane diterpenes from the tuberous roots of Paratinospora sagittata - Li Fan; Yu-Jie Zhang; Shi-Peng Zhang; Wan-Shu Li; Ling-Juan Zhu; Hang-Juan Lin (Natural Product Research, 2026)

Mechanistic responses of coccolithophores to exposure to the marine pollutant atrazine - Xiang-Wu Chen; Yi-Tong Huang; Yue-Tao Song; Zhuo-Fan Li; Xue-Ling Huang; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

Do economic impacts of heat waves vary across climates? Evidence from Chinese cities - Fan Lin; Chaosu Li (Urban Climate, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Petrogenesis of Late Triassic adakitic rocks and basalts from the southern Lhasa: Insights into subduction initiation of Neo-Tethys - Cheng Li; Lin Ma; Andrew C. Kerr; Wei Dan; Qiang Wang; Zhiwei Yu; Wei Qiao; Rui Pu; Fan Yang (Lithos, 2026)

Pollution characteristics and health effects of vehicle emissions particulate matter in undersea tunnel - Anqi Hou; Lingjun Li; Ziyi Lin; Mengren Li; Xiaolong Fan; Xiaohe Wu; Yanting Chen; Lingling Xu; Jinsheng Chen (Journal of Environmental Sciences, 2026)

Melatonin safeguards embryo and blastoid development against oxybenzone toxicity via a mitochondrial-linked NAD+ and glucose metabolic axis - Yuying Xiong; Haiying Zhu; Han Xie; Yunqi Wu; Ruojin Shi; Xueling Zhang; Lin Zhu; Yiwen Wang; Ke Zhong; Lei Li; Yaming Meng; Minyu Xie; et al. (Environmental Pollution, 2026)

Boron species with negative Poisson's ratio alleviating expansion-induced degradation in silicon-based anode for enhanced cycling stability - Yihao Fan; Junzhe Zhang; Lei Ma; Zhi Chen; Minglu Li; Shunan Lin; Danfeng Zhang; Peng Li; Liyong Wang; Yan-Bing He; Huiqi Wang (Chemical Engineering Journal, 2026)

Synergistic interface engineering in a polymeric deep eutectic electrolyte for stable and dendrite-free sodium metal batteries - Yi-fan Zhao; Hai-yang Wang; Chen Wang; Lin Li (Chemical Engineering Journal, 2026)

Hydrogen-bonding guided isoreticular supramolecular frameworks with self-recovery for efficient natural gas purification - Zhou-Rui Yan; Xiao-Han Li; Shi-Kai Zheng; Ze-Jiu Diao; Fan Li; Jin-Peng Liu; Guoliang Liu; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Coupling a Ti/SnO₂-Sb@TiO₂/SnO₂ photoanode with Ce-cu/BC particle electrodes for synergistic ofloxacin detoxification: Insights into mechanisms and transformations - Siyu Yi; Lei Yu; Lin Liu; Zhiwei Fan; Yingke Zhou; Huizhen Zhao; Fuping Li; Xuanming Feng; Hao Wang (Chemical Engineering Journal, 2026)

The synergy of active and passive satellite sensors for robust sea-fog detection: A two-stage machine-learning model with constraints from ICOADS - Luyu Yan; Xuehua Fan; Disong Fu; Hongrong Shi; Lin Chen; Bo Li; Zhuhui Jiang; Xiaoqiong Zhen; Xiaoguang Sun; Xiangao Xia (Atmospheric Research, 2026)

Aged nanoplastics exacerbate CPPD-induced ocular toxicity via the thyroxine pathway in zebrafish - Jin Li; Yi Zheng; Yuying Yin; Wenda Gao; Fan Tang; Xinlin Zhao; Qi Xin; Suiyi Liu; Jiaqi Xiong; Jian Lin; Da Sun; Jiangfei Chen (Aquatic Toxicology, 2026)

An integrated strategy for Cyclotella cryptica cultivation: From antibiotic selection to efficient mixotrophic bioprocessing - Yalan Yu; Zhichao He; Tengsheng Qiao; Sizhe Fan; Lin Zhang; Jian Li; Spiros N. Agathos; Kehou Pan; Jichang Han (Algal Research, 2026)

Advances and Perspectives in Atmospheric Environment Modeling in China - Zifa Wang; Xinwei Li; Meng Gao; Baozhu Ge; Xiao Tang; Xueshun Chen; Qizhong Wu; Lin Wu; Zhe Wang; Ting Yang; Xiaole Pan; Huansheng Chen; et al. (Advances in Atmospheric Sciences, 2026)

Improving growth performance across multiple sheep breeds by targeting the MSTN gene using an enhanced Cas12i system - Bo Liu; Huanyu Song; Miao Yan; Yu Wu; Pengfei Li; Zhanqing Fan; Yufei Chen; Yangsheng Wu; Jiapeng Lin; Liqin Wang; Xiaoyu Niu; Kun Xu; et al. (Science China Life Sciences, 2026)

Effects and Correlations of Acetic Acid Concentration on the Combustion Characteristics and Functional Groups of Coal - Junhong Si; Ziming Fan; Lin Li; Yiqiao Wang; Zihao Zhao (Natural Resources Research, 2026)

Faulting structure and seismic hazard: Insights from the 2024 MW 5.2 Bakersfield earthquake sequence - Weidong Li; Pengcheng Zhou; Fan Zhang; Jiangyang Zhang; Zhiyuan Zhou; Tao Zhang; Jinyu Tian; Jian Lin (Tectonophysics, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

Slightly acidic electrolyzed water enhances fruit disease resistance in longans by activating phenylpropanoid and flavonoid pathways - Qingqing Liu; Shengtai Lin; Yuxin Wu; Zhongqi Fan; Ruiling Zhuo; Yifen Lin; Boqiang Li; Shiping Tian; Mengshi Lin; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2026)

Endophyte-engineered plant immunity: A post-GMO strategy for programmable crop defense - Fan Zhang; Jing Zheng; Xinyun Xie; Mengru Tang; Hongyang Li; Linyin Zuo; Lu Zheng; Hao Liu; Junbin Huang; Zhinan Mei; Xiao-Lin Chen (Molecular Plant, 2026)

Urea as a rising driver of harmful algal blooms: Integrating global patterns, metabolic pathways, and ecological consequences - Huaizhi Qin; Muhamad Syaifudin; Tangcheng Li; Wenkang Fan; Hong Du; Senjie Lin (Harmful Algae, 2026)

Assessing the fidelity of clay-size lithium isotopes as chemical-weathering tracers in detrital sedimentary successions - Xia Zhang; Chunming Lin; Robert W. Dalrymple; Cheng Cao; Daidu Fan; Guyue Tan; Xin Li (Geochimica et Cosmochimica Acta, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Recent advances in exopolysaccharides from lactic acid bacteria: Acquisition, characterization, bioactivities, and applications - Yanli Li; Wenye Zhang; Xiangmin Pan; Yonglan Xiao; Lin Liu; Fan Ding; Guangjian Li; Liqing Zhao (Food Bioscience, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

Efficient construction of triple-phase boundaries for fabrication of high-performance reversible solid oxide cells - Rengang Li; Qun Yang; Jingxuan Hao; Hongpeng Fan; Xiao Wei; Yucheng Zhang; Mingdong Zhou; Xiao Lin; Linjuan Zhang; Jian-Qiang Wang (Chemical Engineering Journal, 2026)

Loofah-inspired recyclable MXene/polypyrrole fiber-skeleton hydrogels for machine-learning-assisted multimodal flexible sensor - Zhiyang Li; Chendan Cui; Fan Yang; Di Yuan; Hemiao Wang; Zhaoyun Lin; Lupeng Shao; Qiang Wang; Weikun Jiang; Linglong Shi; Yu Liu; Dehai Yu (Chemical Engineering Journal, 2026)

Turning harm into benefit: Leveraging anaerobic starvation to establish novel Tetrasphaera dominated simultaneous partial nitrification, denitrification, phosphorus removal, and in-situ sludge reduction process - Zhiwei Fan; Haoyu Lin; Juannong Chen; Ziqi Zhao; Mingxing Lu; Fuping Li; Wei Zeng (Bioresource Technology, 2026)

Hydrochemical Characteristics, Water Quality, and Health Risk Assessment of Groundwater in Zhanjiang Area, Guangdong Province, China - Yongsheng Lin; Jinhui Liu; Shengzhang Zou; Yeyu Yang; Lianjie Fan; Li Lu (Water, Air, & Soil Pollution, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Regulation mechanism of the hadal trench-derived fungus Chaetomium globosum YP-106 under oxygen stress as revealed by integration of metabolomic and transcriptomic profiles - Yaqin Fan; Xin Liu; Yan Zhang; Yuxuan Gai; Xin Li; Lin Song (Journal of Oceanology and Limnology, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

DlNAC41 and DlNAC100 transcription factors modulate longan pulp breakdown via adjusting the expression of cell wall degradation-related genes - Hui Wang; Wenlong Zhou; Xinyue Mu; Zhongqi Fan; Ruiling Zhuo; Yihui Chen; Wangjin Lu; Boqiang Li; Shiping Tian; Yifen Lin; Hetong Lin (Postharvest Biology and Technology, 2026)

DlbHLH66 transcription factor is involved in the acidity differences in the pulp of fresh longan cv. ‘Fuyan’ and ‘Dongbi’ during storage - Zhongqi Fan; Lingzhen Zeng; Shucheng Li; Hui Wang; Ruiling Zhuo; Yifen Lin; Yihui Chen; Wangjin Lu; Boqiang Li; Shiping Tian; Hetong Lin (Postharvest Biology and Technology, 2026)

Obstacle avoidance path tracking control for underwater tracked robots with path-dependent constraints - Xiaolong Yao; Kelin Feng; Kewen Li; Yongming Li; Yu Wang; Xuejian Bai; Wenxing Sun; Yazhou Fan; Zheng Wang; Guohai Lin (Ocean Engineering, 2026)

Fe/Cu-γ-Al2O3 catalyst for pilot-scale internal circulation Fenton degradation of methyl orange: performance and mechanism - Dekai Fan; Yanran Lin; Peng Zhu; Yingwen Zhang; Bang Yao; Li Chao; Zhuangzhuang Jia; Jianjun Dai; Yingrui Ning; Rong Xiao; Chen Chen; Lei Gao; et al. (Journal of Environmental Management, 2026)

Concurrent removal of salinity and microplastics from wastewater using a stacked microbial desalination cell - Siyu Yi; Lei Yu; Lin Liu; Zhiwei Fan; Yingke Zhou; Huizhen Zhao; Xuanming Feng; Fuping Li; Hao Wang (Journal of Environmental Chemical Engineering, 2026)

Insights into the copigmentation effect and mechanism of five carbohydrates on thermal and color stability of mulberry anthocyanins - Qian Li; Xuanran Lin; Zhengguang Wang; Dongxu Xing; Fan Liu; Qingyi Wei; Yuxiao Zou (Food Chemistry, 2026)

Modeling water-nitrogen management for maize production and greenhouse gas emissions in arid Northwestern China using the DNDC model - Runheng Yang; Jinxia Zhang; Meng Yin; Pengliang Tian; Liangliang Du; Yingru Xie; Lin Ding; Yangang Yang; Qingzhuo Li; Jianrong Xiao; Xi Wei; Xinlong Fan (Field Crops Research, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Multi-material vibration attenuation metastructure under multidirectional loads - Yu Li; Lin Li; Cuiping Bai; Zhidong Liu; Hualin Fan (Engineering Structures, 2026)

Ultra-efficient and selective static/dynamic sequestration of selenate from contaminated water by cationic polymeric networks - Wenxia Lin; Yidan Zhou; Fan Lin; Qing Li; Yimin Cai; Wen Feng (Desalination, 2026)

Neuro-inspired tactile system for robotic embodied perception - Yiyang Li; Ning Li; Herong Wang; Xiaojian Rao; Han Liu; Yue Jiang; Weiguan Zhang; Yue Xiao; Yong Tian; Lin Fan; Jindong Tian (Chemical Engineering Journal, 2026)

Thiourea-based networks with nanocarbon fillers for antistatic, self-healing, and plasma-resistant elastomers - Tse-Yu Lo; Shu-Fan Li; Chia-Wei Chang; Huan-Wei Lin; Heng-Hsuan Su; Kuan-Hung Liu; Po-Chia Huang; Jiun-Tai Chen (Chemical Engineering Journal, 2026)

Nonequilibrium fractionation of rare earth elements during typhoon-induced event sedimentation - Yanbin Fan; Yunhai Li; Yunpeng Lin; Haidong Li; Hengbo Wang; Haibo Fan; Hannv Zhang; Guicai Zhong; Feng Jiang (Frontiers in Marine Science, 2026)
High-energy, short-lived typhoon deposition can disrupt particle–water interactions, raising the question of whether rare earth elements (REEs) in event deposits still reflect equilibrium-controlled partitioning or instead capture transient, non-equilibrium geochemical states. We sampled a ~0.5–1 cm surface storm layer and underlying background sediments at 11 stations in the northeastern Beibu Gulf on 29–30 September 2024 (20–21 days after Typhoon Yagi), and quantified major/trace elements and REEs by ICP-OES and ICP-MS, integrating grain size/TOC and statistical correlations. Storm deposits show systematically lower ∑REE and LREE concentrations and slightly lower LREE/HREE ratios than background sediments, accompanied by weaker negative Eu anomalies and a shift toward slightly negative Ce anomalies relative to the mild positive Ce anomaly in background deposits. Despite finer textures and elevated TOC in the storm deposits, the canonical grain-size/adsorption control collapses, with ∑REE exhibiting little to no correlation with grain-size under storm conditions. Critically, storm deposits display pronounced LREE–HREE decoupling: LREE behave quasi-conservatively with “event-scale inertia”, whereas HREE respond more sensitively to non-equilibrium carrier reorganization and rapid settling. This selective decoupling provides a diagnostic geochemical fingerprint for identifying event-driven sedimentation and highlights the need to incorporate kinetic/time-scale effects when interpreting REE-based proxies in dynamic environments.

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Y/Ho ratios in marine sediments unveil Neoproterozoic ocean acidification - Yong-Sheng Liu; Wen-Shuai Li; Jun-Bo Zhang; Jie Lin; Ao Yang; Lian Zhou; Dai-Du Fan; Xi Zhu; Ying-Hua Zhang (Science Bulletin, 2026)

AeroTrans: Hourly AOD retrieval over land from MSG-1/SEVIRI imagery integrating Transformer and transfer learning - Yulong Fan; Zhanqing Li; Lin Sun; Oleg Dubovik; Zhihui Wang; Fan Cheng; Xiaohang Shi; Jing Wei (Remote Sensing of Environment, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Effects of alkaline pretreatment on side-stream enhanced biological phosphorus removal and recovery process - Ruoyu Wu; Dongqi Wang; Yufan Wu; Lu Qin; Xiaonian Feng; Yi Xiao; Yanzhe Gong; Guangxiang Duan; Jiayu Bi; Zhiqiang Xu; Yuan Guo; Jiake Li; et al. (Journal of Water Process Engineering, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Microbial metabolic remodeling under the electric field: A CUE-centered mechanism for enhanced petroleum bioremediation - Ruijuan Fan; Ke Li; Yang Lin; Bingyan Yin; Xingfu Yan (International Biodeterioration & Biodegradation, 2026)

Early evolution of the Meso-Tethys Ocean: Constraints from Permo-Triassic flysch deposits - Si-Lin Sun; Jian-Jun Fan; Bo-Chuan Zhang; Jia-Wei Bai; Xin-Yu Hou; Yang Wang; Li-Qiang Zhang (Gondwana Research, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

NaCl substitution characteristics of Salicornia plant salt and potential application in sturgeon caviar: focus on antibacterial activity and phospholipids oxidation - Weijia Zhang; Lingxin Kong; Jingqi Shen; Yuanhui Zhao; Yujin Li; Shuang Cong; Jian Li; Jinlin Wang; Fan Bai; Peng Xu; Lin Gao; Xinxing Xu (Food Chemistry, 2026)

Texture and structure of high-moisture extrudates produced from soybean protein isolates with different 7S/11S globulin ratios - Chengxin Fei; Lin Li; Ruojie Zhao; Xinrui Wang; Bei Fan; Liya Liu; Fengzhong Wang; Yatao Huang (Food Hydrocolloids, 2026)

Discrepancies in microbial nitrogen cycling among diverse karst hydrological systems: enhanced nitrate reduction potential in karst conduits - Danni Zhu; Yi Li; Lihua Niu; Changsong Zhou; Lianjie Fan; Haiping Lu; Li Lin (CATENA, 2026)

Alpha-ketoglutarate restores oral epithelial homeostasis via FOXM1-mediated cell cycle regulation - Yuan Wang; Yimeng Cai; Qi Yin; Shuqin Cao; Yuyu Li; Yuhan Li; Qiwen Li; Qian Wang; Pochun Lin; Li Mei; Malcolm Xing; Leixiao Yu; et al. (Science China Life Sciences, 2026)

Mechanistic Links Between Suspended Sediment Dynamics and Metal Partitioning Under Tidal Forcing: A Case Study of Quanzhou Bay - Yanbin Fan; Yunhai Li; Yunpeng Lin; Shangshang Yang; Zhijie Chen; Xiang Cao; Chenyang Wang; Shanshan Zhang; Jinzeng Jiang; Mingyang Jiang; Kaichao Wan (Journal of Marine Science and Engineering, 2026)
The coupling of physical transport and phase-transfer processes represents a fundamental mechanism governing metal cycling in estuarine systems under tidal oscillations. Taking Quanzhou Bay as a model system, we conducted continuous observations and sample collection at the river channel (Q1), the turbidity maximum zone (Q2), and the outer bay channel (Q3). The metals (Al, Ti, Ba, Cu, Mn, and Zn) were measured by ICP-MS to systematically investigate the distribution, transport, and inter-media transfer across multiple water layers under varying estuarine processes. Our findings demonstrate that particulate metal concentrations in Quanzhou Bay exhibit strong synchrony with suspended sediment concentrations (SSC) over tidal cycles, displaying a distinct sediment-following pattern controlled by alternating end members. Particulate metal fluxes during flood and ebb-tides generally followed the hierarchy Q1 > Q2 >> Q3. Notably, stations Q1 and Q2 were dominated by flood-tide fluxes with net transport directed landward, whereas Q3 was characterized by ebb tide dominance with net flux directed seaward—revealing a spatial division of labor between “inner bay retention/reallocation” and “outer bay channel export”. In contrast, dissolved metals exhibited marked element-specific responses to tidal forcing: Al and Ti increased during flood tides at stations Q1 and Q2, while Ba and Cu showed opposite trends, and Mn and Zn displayed more conservative behavior. Concurrently, solid/liquid partition coefficient (logKd) values for Al, Ti and Ba, Cu exhibited inverse patterns over tidal cycles, suggesting divergent adsorption–desorption regulation under identical hydrodynamic conditions that drives differential phase-transfer dynamics. These disparities likely reflect intrinsic chemical properties and source variations among the elements. This study elucidates, at the tidal timescale, the coupled processes of “alternating end-member control—estuarine filter modulation—concurrent channelized export and inner bay retention” in Quanzhou Bay, providing critical process-level insights for metal flux quantification and bay pollution remediation initiatives in an ecological restoration project.

Mesenchymal stem cell exosomes alleviate ischemic myocardial injury by miR-125b-5p/BTG2 pathway - Lijun Luo; Lieyou Li; Shuyun Wu; Xinjie Zeng; Lin Fan (Molecular and Cellular Biochemistry, 2026)

Adjuvant-metal-ion-chelating PTEN mRNA with cell-membrane-coating augments the immune sensitivity for precise cancer immunotherapy - Mengyu Guo; Jin-Cheng Guo; Haodong Yao; Fene Gao; Lina Zhao; Lu Cai; Xuan Fan; Lin Bao; Xin Li; Xiaoyu Zhang; Mingdi Hu; Jie Mei; et al. (Science Bulletin, 2026)

The changes of antioxidant system, membrane integrity and phenolics metabolism participate in bongkrekic acid and adenosine triphosphate-mediated energy status regulating longan pericarp browning - Meiling Li; Hetong Lin; Ruiling Zhuo; Boqiang Li; Yifen Lin; Yihui Chen; Zhongqi Fan; Hui Wang (Postharvest Biology and Technology, 2026)

Synergistic pathogenic mechanisms of EHP and IHHNV co-infection in Litopenaeus vannamei: Insights from RNA-seq analysis - Lin-Rui Chang; Cai-Yi Chen; Fan Yang; Chuan-Yu He; Fan Li; Ting Li; Ling-Jun Si; Dong-Chun Yan (Journal of Invertebrate Pathology, 2026)

Concurrent removal of cetirizine hydrochloride and biodiesel accumulation in Chlorella vulgaris - Wen-Bo Yan; Zhong-Hong Zhang; Guo-Hui He; Jia-Xuan Tang; Hui-Lin Guo; Yi-Fan Zhan; Wei-Dong Yang; Hong-Ye Li; Xiang Wang (Journal of Hazardous Materials, 2026)

The bioaccumulation characteristics and combined toxicity effects of aged microplastics with adsorbed Hg(II) in oysters - Lianghong Li; Chun Lv; Qijia Zhou; Qiaoguo Tan; Haiying Lin; Qingge Feng; Xiaohong Song; Xianghua Wu; Qiuyan Hu; Lixin Huang; Jie He; Guanjian He; et al. (Journal of Hazardous Materials, 2026)

A novel mainstream application of aerobic granular sludge for nitrite supply to Anammox: insights from granule size and microbial stratification - Zongshuo Han; Xiaoying Zheng; Wenfei Li; Haidong He; Yi Fan; Tao Lin; Wei Chen (Journal of Cleaner Production, 2026)

The primary sources of ROx radicals in atmosphere: Oxidative capacity and self-purifying effect - Gaojie Chen; Ziyi Lin; Xiaoting Ji; Lingling Xu; Xiaolong Fan; Mengren Li; Youwei Hong; Jinsheng Chen (Journal of Environmental Sciences, 2026)

Human settlement doubled global oceanic island erosion and fire regimes during the early colonization stage - Fan Zhang; Huawei Wang; Chuan-Chou Shen; Jian Lin; Kai Zhou; Yongshun Chen; Kunshan Bao; Xinxin Li (Global and Planetary Change, 2026)

Pore structure reconfiguration and microscale fluid response in bituminous coal under CO2 and flue gas-enhanced coalbed methane recovery - Ke Li; Chuanjie Zhu; Jiawei Wang; Xuanye fan; Yuchen Liu; Cheng zhai; Baiquan Lin (Fuel, 2026)

Enhanced marine primary productivity during the long-term Ordovician cooling: A barium isotope perspective from South China - Shengchao Yang; Junxuan Fan; Chao Li; Yi-Bo Lin; Yiying Deng; Zongyuan Sun; Jian Cao; Shu-zhong Shen (Earth and Planetary Science Letters, 2026)

Laser-driven atomic dispersion strategy: Collective catalysis synergy of atomic clusters and single atoms for enhanced CO₂ hydrogenation - Rongxia Zhao; Furong Liu; Shilin Fan; Zerui Li; Hongfeng Yin; Degao Wang; Lin Li; Yuxiang Liu; Zhu Liu (Chemical Engineering Journal, 2026)

Design and optimization of CuBi modified Ti hollow fiber electrocatalytic membranes via co-electrodeposition for enhanced removal of sulfamethoxazole - Xiaoqing Yan; Zonglin Pan; Guoqing Feng; Ruisong Xu; Lin Li; Shuaifei Zhao; Xinfei Fan; Chengwen Song; Tonghua Wang (Chemical Engineering Journal, 2026)

Dynamic variations of near-surface temperature and moisture at a desertified permafrost site on the Qinghai-Tibet Plateau - Zhanju Lin; Nuocheng Li; Xuhui Wang; Xingwen Fan; Wenjiao Li; Xuyang Wu; Peng Zhang (Cold Regions Science and Technology, 2026)

Assessing the impacts of climate warming and engineering activities on the thermal regime of permafrost in the Kunlun Mountains, Qinghai-Tibet Railway - Zhanju Lin; Xuhui Wang; Xuyang Wu; Wenjiao Li; Peng Zhang; Nuocheng Li; Xingwen Fan (Cold Regions Science and Technology, 2026)

FGF2 Enhances MSCs Secretome Therapy for Skin Photoaging by Delaying Senescence via iNAMPT/AMPK Signaling and Facilitating eNAMPT-Mediated Regenerative Crosstalk - Yixin Zhang; Manping Lu; Jieqing Ouyang; Lin Liang; Fan Li; Zhihan Pei; Lihao Chen; Miaoman Ye; Jiajie Tan; Liwei Xiang; Lijing Kong; Long Huang; et al. (Stem Cell Reviews and Reports, 2026)

Assessment of dynamic drought risk and transition characteristics by combining an indicator-based approach and Markov chain model - Bin Huang; Tao Peng; Tianyi Fan; Vijay P. Singh; Xiaohua Dong; Qingxia Lin; Wenjuan Chang; Ji Liu; Yan Huang; Jiali Guo; Yinghai Li; Dan Yu (Natural Hazards, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Mussel Production in the Global Blue Food System: Current Status, Sustainability Challenges, and Future Trajectories - Fan Li; Hai-Jie Gao; Yun-Lin Ni; Peng-Zhi Qi (Fishes, 2026)
This review examines the status, challenges, and future trajectories of global mussel aquaculture within the blue food system. Despite steady production growth, mussels’ relative contribution to total bivalve output has significantly declined over recent decades due to disproportionate expansion of oyster, clam, and scallop sectors. A major geographical production shift has occurred, with Asia, spearheaded by China, emerging as the dominant region, supplanting traditional European producers while the Americas rapidly ascend. China’s overwhelming dominance in overall bivalve production starkly contrasts with its underdeveloped mussel sector, where growth lags behind other bivalves despite substantial absolute increases, reflecting a fundamental restructuring of species composition. The industry faces interconnected sustainability constraints: persistent vulnerabilities in spat supply stemming from environmental variability, hatchery limitations, and disease transmission risks; escalating environmental stressors including climate change impacts, harmful algal blooms, pollution, and pathogens; structural flaws in value chains characterized by fragmented production, market volatility, and underutilized byproducts; and governance challenges related to spatial access and licensing inefficiencies. This review advocates for a comprehensive strategy to boost the mussel aquaculture. These encompass advancing hatchery technology and genetic breeding programs, implementing ecosystem-based management such as multi-trophic systems and AI-enhanced environmental monitoring, restructuring value chains through producer cooperation and high value product diversification, and establishing science-based spatial planning frameworks with streamlined governance. Addressing these challenges holistically is critical to position mussel farming as a resilient pillar of sustainable blue food production capable of reconciling ecological integrity with economic viability and social equity.

Cadmium Exposure Facilitates Oral Squamous Cell Carcinoma Progression and Epithelial–mesenchymal Transition Through the Upregulation of ATP1B4 - Jianbo Zhang; Jingdian Li; Jinghong Liu; Yongchun Peng; Huifeng Pi; Weijia Qing; Zhijing He; Xi Zhou; Bo Li; Junxin Liu; Qingyun Lin; Tengfei Fan (Biological Trace Element Research, 2026)

Bioactive metabolites from Samsoniella sp. KY1174: isolation, characterization, and cytotoxicity against cancer cell lines - Xingtong Chen; Huiting Wu; Huilin Shu; Haoyu Yu; Fan Cai; Jianbin Xiao; Wei Lin; Yuxin Shi; Mingliang Zhang; Qin Li; Huaidong Zhang; Wanhao Chen; et al. (Natural Product Research, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Pooled data from phase 3 clinical trials comparing the clinical activity of ceftolozane/tazobactam versus meropenem for the treatment of complicated intra-abdominal infections - Zhiqiang Li; Yue Kang; Hongqiang Gao; Yingpeng Zhao; Ding Luo; Dongdong Wang; Xiang Zhang; Jieqi Yu; Guang Chu; Jun Cao; Fan Wang; Xiongqi Zhao; et al. (Infectious Diseases, 2026)

A modeling approach for dynamically assessing the carbon storage potential of the Manila clam Ruditapes philippinarum in typical aquaculture systems - Weiwei Jiang; Weiwei Li; Fan Lin; Jinghui Fang; Yuze Mao; Jianguang Fang; Zengjie Jiang (Aquaculture, 2026)

Spatiotemporal variations of halogenated polycyclic aromatic hydrocarbons in sediments of Pearl River Estuary: Occurrence, sources, and potential ecological risks - Fan Lin; Yan Li; Li Lin; Ke Yuan; Lihua Yang; Yongshun Huang; Baowei Chen; Tiangang Luan (Marine Pollution Bulletin, 2026)

DDX21 nuclear-cytoplasmic shuttling recruits RPS18 to viral dsRNA to promote CSFV replication - Bingke Li; Bolun Zhou; Chenchen Sun; Shurou Li; Ye Bai; Ruibo Zhao; Yiwan Song; Yintao He; Lin Yi; Hongxing Ding; Shuangqi Fan; Jinding Chen; et al. (Veterinary Microbiology, 2026)

Insecticide resistance monitoring and identification of ryanodine receptor mutations driving diamide resistance in Cnaphalocrocis medinalis - Hong-Shuang Li; Pin-Xuan Lin; Meng-Zhen Wang; Bei-Bei Dong; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2026)

Predictive modeling of high-speed ice-structure interaction using PD-AE-LSTM - Ming He; Mengshan Xie; Yu Ao; Xinran Li; En-Fan Lin (Ocean Engineering, 2026)

Cryo-EM structures of Arabidopsis heteromultimeric isoamylase complex essential for starch granule biogenesis - Ruiying Wang; Wenjuan Li; Yutong Wu; Huajian Lin; Xiang Lin; Lizhi Zhu; Ruiqiang Ye; Jinru Zhang; Minrui Fan (Molecular Plant, 2026)

Ketamine's brain spatial distribution and metabolic effects in a mouse model of anxiety: Insight into in situ mass spectrometry imaging and metabolomics methods - Hong Yang; Weihao Fan; Xinyu Yang; Ying Wei; Li Xiao; Hongkun Yang; Linzhi Jiang; Jian Li; Kaiting Shi; Shuang Zhao; Lin Yang; Yi Ye; et al. (NeuroToxicology, 2026)

Effects of baking and steaming on volatile and non-volatile metabolites in Yanshu 25 juice before and after fermentation - Yunfan Wang; Xiaohe Li; Yanhui Kong; Congyu Lin; Xiulian Li; Xiangquan Zeng; Huamin Li; Wenli Liu; Hansheng Gong; Xinguang Fan (Food Research International, 2026)

Modulation of viscosity, swallowability, and stability of starch-based thickener: The effect of konjac gum and xanthan gum - Haoran Fan; Lin Sun; Xiaodan Liu; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Research International, 2026)

Carbon reduction potential of international secondary resource circulation: A case study among six major trading economies - Guannv Lin; Fan Wei; Jinhui Li; Li Liang; Hien Thi Thu Ngo; Zhengyang Zhang; Quanyin Tan (Environmental Impact Assessment Review, 2026)

Smart PVA/starch hydrogel for real-time monitoring and repair of skin–muscle defects - Yiming Sun; Longkang Li; Lijun Fan; Jinwen Wang; Xiao Lin; Huipeng Li; Huan Zhou; Lei Yang (Chemical Engineering Journal, 2026)

Unraveling the structure-selectivity nexus: electrode materials for selective phosphorus removal and recovery via capacitive deionization: A systematic review - Sheng Wen; Yu Ma; Yang Fan; Jinxing Lin; Jiaqi Chen; Simiao Li; Huakun Pan; Xinxi Teng; Shupeng Zhang (Chemical Engineering Journal, 2026)

Hybrid calcium carbonate nanoparticles incorporated with capsaicin for tumor therapy via calcium overload mediated mitochondria damage and endoplasmic reticulum stress - Yiling Li; Yiyin Zhang; Guoqiao Chen; Xiaolong Liu; Qiming Xia; Yixuan Li; Jing Yang; Guoqiao Xu; Jiayi Chen; Jun Chen; Guping Tang; Xiaoxiao Fan; et al. (Chemical Engineering Journal, 2026)

Soil moisture dynamics and rainfall infiltration across vegetation types in subtropical ecosystems in Southwest China - Qiao-Shun Yan; Yu-Xi Peng; Xiao-Jin Jiang; Pei-Li Fu; Zhi-Yun Lu; Xiao-Wen Hu; Yong-Jiang Zhang; Jiao-Lin Zhang; Ze-Xin Fan (CATENA, 2026)

Distribution characteristics of secondary embankment diseases in permafrost regions of Qinghai Province and their relationship with local factors - Peng Zhang; Lei Liu; Yangyang Xie; Xuyang Wu; Xingwen Fan; Wenjiao Li; Nuocheng Li; Xuhui Wang; Fujun Niu; Zhanju Lin (Cold Regions Science and Technology, 2026)

Study on the ground-air temperature relationship under microenvironmental differences in the warm permafrost region of the Tibetan Plateau - Nuocheng Li; Zhanju Lin; Xingwen Fan; Yanhe Wang; Wenjiao Li; Qiang Gu; Wenlong Pang; Xuhui Wang; Peng Zhang (Cold Regions Science and Technology, 2026)

Corrigendum to “Characterization of a novel Dye-Decolorizing peroxidase from Brevibacillus agri and its application in detoxification of textile industry wastewater”. [Bioresource Technol. 440 (2026) 133430] - Wenjing Lin; Wei Lin; Lizhen Yang; Chunfang Zhang; Xuehui Li; Jianbin Xiao; Xingtong Chen; Fan Cai; Chao Chen; Mingliang Zhang; Yan Zhang; Li Li (Bioresource Technology, 2026)

Characterization of a novel Dye-Decolorizing peroxidase from Brevibacillus agri and its application in detoxification of textile industry wastewater - Wenjing Lin; Wei Lin; Lizhen Yang; Chunfang Zhang; Xuehui Li; Jianbin Xiao; Xingtong Chen; Fan Cai; Chao Chen; Mingliang Zhang; Yan Zhang; Li Li (Bioresource Technology, 2026)

Promoting effect of aerobic starvation on enhancing biological phosphorus removal system - Zhiwei Fan; Zekai Ren; Yanling Guan; Ling Bai; Haoyu Lin; Ziqi Zhao; Hao Wang; Mingxing Lu; Meijie Zhou; Fuping Li; Wei Zeng (Bioresource Technology, 2026)

Differential contributions of microbial necromass to humification: Hyperthermophilic vs. conventional thermophilic composting - Minru Liu; Xuechang Ren; Zhenrong Lin; Kejing Fang; Kai Li; Qizhe Fan; Zhen Yu (Bioresource Technology, 2026)

Modeling of industrial biomass fluidized bed gasification system and optimization of operating conditions - Haodong Fan; Han Zhang; Geng Li; Xiong Zhang; Zixue Luo; Lin Huang; Shihong Zhang (Biomass and Bioenergy, 2026)

Brain Tissue-Derived Exosomal Proteomics Identifies Chemotaxis-Associated Protein Changes After Traumatic Brain Injury: An Exploratory Hippocampal Transcriptomic Comparison - Wei-can Chen; Xin-li Chen; Cheng-ye Lin; Yang-zi Huang; He-fan He; Yi-lin Zhou; Yi-bin Liu (Molecular Neurobiology, 2026)

Salvianolic Acid B Inhibits Ferroptosis Through ACSL4 Pathway Regulation in sepsis-associated encephalopathy Mice - Xingyao Li; Zhizhun Mo; Yumei Yang; Chunxia Zhao; Shuwen Zhang; Yan Lin; Yuxiang Liu; Ling Wang; Xiaolong Xu; Qingquan Liu; Kai Fan (Molecular Neurobiology, 2026)

CDGSH Iron Sulfur Domain 1 Relieves Neuronal Ferroptosis via Activating AMPK Pathway in Alzheimer’s Disease - Yuanlong Li; Hua Fan; Xiong Han; Ming Ni; Xiaodan Hou; Hailan Xia; Yinzhu Shi; Lin Zhang; Jun Sun (Molecular Neurobiology, 2026)

Correction: Role of tRNA-Derived Fragments and Their Modifications in the Pathogenesis and Treatment of Alzheimer’s Disease - Lin Li; Jianda Kong; Rao Fan; Yang Yuan; Lei Zhu (Molecular Neurobiology, 2026)

Role of tRNA-Derived Fragments and Their Modifications in the Pathogenesis and Treatment of Alzheimer’s Disease - Lin Li; Jianda Kong; Rao Fan; Yang Yuan; Lei Zhu (Molecular Neurobiology, 2026)

RRBP1 Inhibition Reduces Microglial M1 Polarization and Inflammation-Mediated Neuronal Loss and Oxidative Stress by Regulating ERK Pathway in Alzheimer’s Disease - Yuanlong Li; Hua Fan; Xiong Han; Ming Ni; Xiaodan Hou; Hailan Xia; Yinzhu Shi; Lin Zhang; Jun Sun (Molecular Neurobiology, 2026)

The centennial legacy of disturbances on sedimentation and carbon burial in an estuarine mangrove ecosystem, South China - Juan Su; Yaobei Lin; Penghui Li; Zhangcai Qin; Luhua Xie; Fan Wang; Weiguang Li; Jinghong Zhang (Journal of Oceanology and Limnology, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

Transcriptomic analysis reveals the toxic effects of Clothianidin on the embryonic development of zebrafish - Tingting Qian; Zhonghua Fan; Xiyue Liu; Ying Yang; Lin Cheng; Zhou Zhou; Ziheng Xiao; Lijuan Yuan; Li Wang; Hui Liu (Toxicology and Applied Pharmacology, 2025)

Surrogate-Assisted Niching Differential Evolution for hyperparameter optimization in Convolutional Neural Networks - Wenhao Du; Zhigang Ren; Fan Li; Yidi Lin (Swarm and Evolutionary Computation, 2025)

FGFR2-regulated cytoskeletal rearrangement disturbs autophagy flux induced by polystyrene nanoplastics - Huanpeng Liu; Ting Chen; Huiqi Li; Helei Cai; Qizhuan Lin; Changyong Gong; Fan Yu; Renyi Peng (Science of The Total Environment, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Mitigation of focused wave effects on the box girder coastal bridge using floating breakwaters and frictional rubber bearings - Lin Li; Bo Huang; Wenlong Luo; Shixiao Fan (Ocean Engineering, 2025)

Biogeochemical processes play a decisive role in determining the fate of marine PAHs: A case validation with field measuring and modelling in the Beibu Gulf, South China Sea - Jingwen Shi; Mengyang Liu; Lingxin Chen; Jiandong Ye; Wupeng Xiao; Jinyan Xie; Fajin Chen; Yi-Fan Li; Xuke Chen; Yan Lin; Lin Zhang; Mingjun Feng; et al. (Journal of Hazardous Materials, 2025)

A novel, clean and efficient two-stage leaching process for extracting niobium from clay weathered basaltic crust - Lin Wu; Zhilong Huang; Tao Wu; Zhengzhong Xiang; Taiyi Luo; Lin Ye; Hongpeng Fan; Qingyu Li (Journal of Cleaner Production, 2025)

Magnetic activated biochar prepared via a novel iron-loading method for efficient lead adsorption and recyclability - Li Chao; Bang Yao; Chenglong Liu; Yang Liu; Chunbao Zhou; Yingwen Zhang; Dekai Fan; Yunxiang Li; Pengfei Zhu; Wei Li; Yanran Lin; Jing Li; et al. (Journal of Environmental Chemical Engineering, 2025)

Remodelling membrane lipid composition through exogenous supplementation of stearic acid improves the survival rate of spray-dried Bifidobacterium animalis - Fengzhi Qiao; Jiadong Li; Zhi Duan; Fan Yang; Shichao Xuan; Wenhao Ding; Meijun Liu; Zhe Zhang; Tongjie Liu; Lanwei Zhang; Kai Lin (Food Research International, 2025)

Fabrication and characterization of starch-based edible films loaded with Lactiplantibacillus plantarum STB9b for pork preservation - Jianwei Zang; Yue Hu; Tao Lin; Xia Fan; Yimeng Kou; Yibo Shi; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Wei Li (Food Packaging and Shelf Life, 2025)

Leaf senescence and source-sink dynamics in soybean: Insights from maize-soybean intercropping systems - Zhen Fan; Binbin Qiang; Yanrong Lin; Pengzhao Liu; Zhipeng Li; Mengwei Cheng; Xining Zhao; Xiaolong Ren; Xiaoli Chen (Field Crops Research, 2025)

HFPO-TA induces liver damage and ferroptosis in zebrafish by disrupting iron metabolism homeostasis - Lin Cheng; Zhonghua Fan; Yu Zhang; Xu Fang; Yuanyuan Wu; Hongru Liu; Lanxi Ye; Li Wang; Hui Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Stepwise mechanochemical ball milling induced lattice destruction‑oxygen vacancy regulation promotes large-scale lithium leaching from spent lithium-ion battery cathodes - Jian Wang; Xingsheng Li; Zhikui Zhou; Yanyan Xia; Xinyu Liu; Zixiang Lin; Guanhua Jin; Xiaoyun Fan (Chemical Engineering Journal, 2025)

Synergistic modification of coal by coupled scCO2 and engineering chemical reagents: Effects on pore structure and micromechanical properties - Ke Li; Yuchen Liu; Chuanjie Zhu; Sheng Qian; Yongshuai Lai; Xuanye Fan; Baiquan Lin (Chemical Engineering Journal, 2025)

An enhanced nanoenzyme for remodeling the inflammatory microenvironment and low-temperature photothermal cascade therapy for rheumatoid arthritis - Sui Zhou; Yong Li; Yi-Tong Zhou; Meng-Wen Ma; Kai-Lin He; Kai Cheng; Jin-Xuan Fan; Bo Liu; Ling-Li Dong; Yuan-Di Zhao; Xin Liu (Chemical Engineering Journal, 2025)

Effects of gum incorporation on the properties of sodium alginate-based composite hydrogel beads for encapsulating lactic acid bacteria - Ying-Ying Jing; Yun-Cheng Li; Yong-Qi Luo; Long-Hua Zou; Yuan-Mou Tang; Yu-Xi Lin; Fan-Bing Meng (Carbohydrate Polymers, 2025)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

Lithospheric structure and geodynamics of oceanic transform fault - Fan Zhang; Jian Lin; Sanzhong Li; Yanhui Suo; Pengcheng Zhou; Yiming Luo; Caicai Zha; Xubo Zhang (Science China Earth Sciences, 2025)

Decline and redistribution of soil organic carbon fractions after conversion from subtropical Forest to farmland - Ruijie Qiu; Qianqian Ma; Jiewen Yang; Ruqin Fan; Shengsen Lin; Xiutong Li; Zhilong Liang; Xiaobo Li (Plant and Soil, 2025)

Immunoglobulin G4-related sclerosing mastitis: MRI findings and the literature review - Lishan Wang; Fan Yang; Xiaoyan Hu; Na Li; Jie Gou; Wei Lin; Shengjian Zhang (Immunologic Research, 2025)

Histological studies on the ontogeny of the big-belly seahorse (Hippocampus abdominalis) - Yuanyuan Xue; Lu Tang; Chunhui Lv; Fang Wang; Xiaolei Su; Mingzhu Li; Yuping Hou; Jie Dong; Chengde Fan; Jiezhou Wang; Lin Shi; Qunhao Zhou; et al. (Fish Physiology and Biochemistry, 2025)

Seawater Flow-Freezing Characteristics in Open Container Injection Under Low-Temperature Conditions - Yuhao Fan; Bei Peng; Puyu Jiang; Jiahui Ren; Yuesen Lin; Longlong Gao; Baoren Li (Journal of Marine Science and Engineering, 2025)
The phenomenon of seawater flow-freezing exists during ballast water injection and drainage in polar vessels, but the heat transfer and ice evolution behaviors under low-temperature flow conditions remain unclear. This study developed a computational model for ballast tank freezing using the volume of fluid (VOF) and enthalpy–porosity method, and constructed a scaled experimental platform for the simulation model validation. Based on this model, the flow-heat transfer and ice evolution process in the ballast tank are analyzed in detail, with a focus on the influence of injection velocity, pipe diameter, and position on seawater freezing characteristics. The results show that during low-temperature water injection, phase change occurs preferentially in the tank bottom region, with ice presenting as a slurry morphology; when injection velocity increases from 0.25 m/s to 3.5 m/s, the maximum ice-phase volume fraction increases by 48.9%, indicating faster flow accelerates phase-change freezing; compared to other diameters, DN150 piping exhibits the highest turbulent kinetic energy (0.054 m2/s2) and the maximum shear stress (12.49 Pa), demonstrating optimal freezing resistance; compared to bottom injection, sidewall injection intensifies heat transfer/icing near tank walls and increases ice-clogging risk around ports. This study reveals intrinsic mechanisms of dynamic ice-blockage evolution, providing theoretical basis for anti-clogging design in polar ship systems.

Effects of Nitrogen Deposition, Biodiversity and Climate on Productivity in a Large Temperate Forest Region - Jie Li; Senxuan Lin; Minhui Hao; Chunyu Fan; Juan Wang; Klaus von Gadow; Chunyu Zhang; Xiuhai Zhao (Global Ecology and Biogeography, 2025)
Aim Nitrogen deposition is a widespread global change driver that significantly affects terrestrial ecosystems. However, evidence on the specific mechanisms of productivity response to nitrogen deposition in temperate forests across ecological and climatic gradients is scarce. This study evaluates the effects of nitrogen deposition, multiple attributes of biodiversity and climate on productivity in a large temperate forest region. Location North‐eastern China. Time Period 2017. Major Taxa Studied Woody plants. Methods We assessed taxonomic, functional, and phylogenetic attributes of tree diversity and functional identity of forest communities across a wide range of ecological and climatic conditions. Using partial linear mixed models (LMMs), multivariate LMMs, and structural equation modelling, we investigated the effects and pathways of nitrogen deposition, biodiversity, and climate conditions on productivity. We also explored the relationship between nitrogen deposition and productivity across biotic and climatic gradients. Results Our results show that nitrogen deposition, phylogenetic diversity (PD), and the community‐weighted mean of maximum tree height (CWMHM) are significant positive drivers of productivity. Climate conditions primarily affected productivity indirectly through PD. In species‐poor high‐latitude forests characterised by cold and dry climates, nitrogen deposition had strong positive effects on productivity. That effect weakened towards warmer climatic conditions. Main Conclusions The findings of this study suggest that the response of productivity to nitrogen deposition depends on local ecological and climatic conditions. Our results underscore the importance of considering interactions among multiple global change drivers to improve the accuracy of ecosystem response predictions.

Two new amplisins with antibacterial activities from Akanthomyces attenuatus - Fan Cai; Wen Xie; Haoyu Yu; Xingtong Chen; Wei Lin; Jianbin Xiao; Chao Chen; Mingliang Zhang; Qin Li; Huaidong Zhang; Hui Zhang; Li Li (Natural Product Research, 2025)

Isolation, identification and characterization of Photobacterium leiognathi 10MKXP20 from sea cucumber (Apostichopus japonicus) cultured in Southeast China - Qiuhua Yang; Lili Wang; Yanfang Zhong; Ming Zhang; Huiyao Li; Yinhua Wang; Yilong Fan; Weiju Xing; Jianshao Wu; Shengkang Li; Ngoc Tuan Tran; Qi Lin (Frontiers in Marine Science, 2025)
In autumn 2020, cultured sea cucumbers ( Apostichopus japonicus ) in the Xiapu Sea area (Southeast China) exhibited ulcerative skin lesions. To identify the causative pathogen, the Gram-negative strain 10MKXP20 was isolated from the muscle tissue of diseased animals and identified as Photobacterium leiognathi through phenotypic and genetic analysis. The bacterium was sensitive to 14 antibiotics, including tetracycline and enrofloxacin, but resistant to gentamicin, neomycin, kanamycin, rifampicin, amikacin, and amoxicillin. Minimum inhibitory concentration (MIC) assays revealed varying efficacy among the tested antibiotics, with enrofloxacin, doxycycline, and florfenicol showing particularly low MICs, indicating strong inhibitory activity. Challenge experiments via immersion and intramuscular injection confirmed the pathogenicity of P. leiognathi 10MKXP20, with mortality rates being dose-dependent. This study is the first to identify P. leiognathi as the causative agent of ulcerative skin disease in sea cucumbers, providing crucial insights for disease diagnosis and antibiotic treatment.

Integrated single-reactor system merging biological phosphate removal, semi-nitritation, anammox and in-situ sludge fermentation (PR-SNA-SF) to treat actual domestic wastewater - Zhiwei Fan; Ziqi Zhao; Zhuyan Dong; Ling Bai; Haoyu Lin; Meijie Zhou; Hao Wang; Fuping Li; Wei Zeng (Process Safety and Environmental Protection, 2025)

Impact of acid mine drainage on water quality in receiving watersheds and associated potential adverse effects - Hao Wang; Guodong Chai; Heyun Yang; Kailong Li; Kai Chen; Yueyao Xue; Jiake Li; Zhe Wang; Chunbo Jiang; Huaien Li; Fan Yang; Yishan Lin; et al. (Process Safety and Environmental Protection, 2025)

Hypoglycemic cucurbitane-type triterpenoids from fruits of Citrullus colocynthis - Hua-Wei Lv; Yu Wan; Wen-Lin Fan; Meng-Di Zhu; Qiao-Liang Wang; Zhong-Bo Zhou; Chang-Chun Chen; Hong Wang; Xing-Nuo Li (Phytochemistry, 2025)

Synergistic strengthening of 3D‑printed ECC beams through steel-wire mesh and interfaces treatments - Manfang Lin; Yao Ding; Fan Yu; Lingzhi Li; Kequan Yu (Engineering Structures, 2025)

Pyraclostrobin disrupts ion regulation by suppressing mitochondrion-rich ionocyte differentiation in zebrafish embryos - Li-Yih Lin; Fan-Hsuan Yeh; Kuan-Yi Lee; Jiun-Lin Horng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Micro-finned nanostructured superhydrophobic surfaces for high-performance steam condensation heat transfer at high concentrations of non-condensable gases - Wen-Ze Yang; Tian-Yu Zhang; Zhen-Yu Lu; Xuan-Yi Lin; Li-Wu Fan (Chemical Engineering Journal, 2025)

Internally coupled concave nanobox@quantum dots nanoassemblies for SERS/fluorescence/colorimetric trimodal detection of prognostic biomarker in acute ischemic stroke - Wei-Bin Wang; Jian-Jun Li; Lin-Lin Fan; Jing-Yuan Wang; Guo-Jun Weng; Jian Zhu; Jun-Wu Zhao (Chemical Engineering Journal, 2025)

Establishment of succinic acid production in recombinant Kluyveromyces marxianus enhanced by AI-guided enzyme specificity engineering and redox-controlled fermentation optimization - Du-Wen Zeng; Yi-Fan Zhu; Yuan-Hong Jiang; Ya-Hao Ding; Zhen-Zhi Wang; Kai Li; Sha Liao; Ya-Chao Fan; Lin Zhang; Yu Guang Wang; Xin-Qing Zhao (Chemical Engineering Journal, 2025)

HFPO-TA exposure triggers hepatomegaly and lipid peroxidation via Nrf2/keap1 antioxidant dysregulation and ferroptosis activation in the liver - Xu Fang; Zhonghua Fan; Mengjiao Li; Zhi Li; Lin Cheng; Yuanyuan Wu; Li Wang; Hui Liu (Chemico-Biological Interactions, 2025)

Xanthouhumol relieves stress-induced depressive-like behaviors through the Sirt1/NF-κB/NLRP3 pathway - Gangqiang Lin; Yi Zhang; Jing Qin; Yong He; Li Fan; Qing Tan; Peng Xie (Psychopharmacology, 2025)

Co-encapsulation of an AKT Inhibitor Enhances the Tumor-cell Selectivity of STING Agonists in Co-delivery Liposomes - Ziyu Ge; Qiang Zhang; Yuming Wang; Lin Miao; Xinqi Wang; Ni Fan; LiLi Duan; Yunfei Li; Xue-Jie Qi (Pharmaceutical Research, 2025)

Protective Effects of Deinoxanthin on Brain Oxidative Damage and Gut Microbiota in the D-Galactose-Induced Aging Mice - Huijuan Su; Yutao Li; Jiayi Wan; Jieyu Lin; Jiayao Wang; Rui Fan; Dingming Liu; Jing Wei; Hongbo Xin; Yuejin Hua; Shengjie Li (Molecular Neurobiology, 2025)

COMPERA 2.0 risk stratification in patients with severe aortic stenosis: implication for group 2 pulmonary hypertension - Zongye Cai; Xinrui Qi; Dao Zhou; Hanyi Dai; Abuduwufuer Yidilisi; Ming Zhong; Lin Deng; Yuchao Guo; Jiaqi Fan; Qifeng Zhu; Yuxin He; Cheng Li; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Virtual screening and experimental validation of small-molecule compounds targeting AR in prostate cancer - Zhongqiang Fan; Xuexue Hao; Weiren Chen; Zhunan Xu; Qihua Wang; Muwei Li; Hao Zhang; Congzhe Ren; Yutong Chen; Jianping Lin; Xiaoqiang Liu (Molecular Diversity, 2025)

Biotransformation of oleanonic acid by circinella muscae to produce novel 11,12-epoxy-13,28-lactonized derivatives and their anti-neuroinflammatory activity - Wei Liu; Li Yang; Liu-Tong Guan; Jia-Hui Wang; Yao-Yu Liu; Yan Song; Jian-Lin Li; Wen-Li Wang; Bo-Yi Fan; Guang-Tong Chen (Natural Product Research, 2025)

CPK12 decodes effector-triggered calcium signaling and phosphorylates PIP2;1 to facilitate apoplastic ROS transport into the cytoplasm in Arabidopsis - Zhiyi Jia; Weiwei Yu; Xijie Guo; Jianwei Li; Fan Qi; Yayun Zhu; Xinzhong Cai; Xiaoting Li; Ning Li; Hansong Dong; Fucheng Lin; Yan Liang (Molecular Plant, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Identifying driving mechanisms and relationships between supply and demand of ecosystem services based on structural equation model in the upstream segment of the Yangtze River - Jingyang Fan; Shiliang Liu; Wanting Wang; Yetong Li; Zechen Wang; Miaomiao Liu; Yifei Zhao; Jiayi Lin; Ziang Tian; Gang Wu (Journal of Environmental Management, 2025)

Algal-bacterial granular sludge cultured with different inoculum: The discrepancy of granulation mechanism and greenhouse gas emissions - Xiongcheng Deng; Xiaoying Zheng; Zongshuo Han; Jiaqing Tao; Yunqing Li; Tianxing Hu; Yi Fan; Tao Lin (Journal of Environmental Chemical Engineering, 2025)

Mechanistic insights into H2O2 activation by high-density iron single-atom catalysts for efficient water treatment: Surface-bound radical and singlet oxygen - Fuhang Xu; Cui Lai; Mingming Zhang; Zuying Yao; Dengsheng Ma; Bisheng Li; Meng Qin; Huchuan Yan; Xiuqin Huo; Xing Fan; Biting Wang; Shiyu Liu; et al. (Journal of Environmental Chemical Engineering, 2025)

Preparation and numerical simulation of high burn rate microporous fireworks propellants using microfluidic technology - Yixin Li; Haixia Fan; Renming Pan; Xiangyang Lin (Journal of Environmental Chemical Engineering, 2025)

Bioreduction-assisted synthesis of Co nanoclusters for selective singlet oxygen generation in ciprofloxacin degradation - Yuning Fan; Wenqian Zhang; Yaping Geng; Jiangjun Lin; Yefei Su; Kai Teng; Jiajie wu; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2025)

Genome-wide identification of ApeC domain-containing protein and revealing the function of ChACP-1.10 in oyster mucosal immunity - Tianxiang Lin; Lu Liu; Liang Zeng; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; Zhiming Xiang; et al. (Fish & Shellfish Immunology, 2025)

Sources, temporal-spatial characteristics, exposure assessment and children health risk of phthalate esters (PAEs) in household dust in China from 2000 to 2023: a review and pool analysis - Wenying Zhang; Xiaotong Zhang; Xiaomin Xie; Tingting Liu; Fengjing Song; Chengyu Chen; Chao Wang; Linlin Jiang; Hang Du; Lin Fan; Xu Han; Yiming Sun; et al. (Environmental Pollution, 2025)

Regulation mechanism and resistant strain based bioaugmentation of anammox consortia in response to triclocarban - Jia-Hui Yang; Wei-Lin Guo; Zhe-Qi Lian; Qi Su; Xin-Yi Zhao; Wen-Li Guo; Nian-Si Fan; Ren-Cun Jin (Chemical Engineering Journal, 2025)

The threat of diaphragm closure to thermal runaway during battery charging - Jianqi Zhang; Tao Fan; Zhengnan Liu; Lin Yu; Yuhui Wang; FangZhou Li; Shuai Yuan; Chongye Chang; Kuo Wang; Ziwei Song; Xinming Qian; Qing Wang (Chemical Engineering Journal, 2025)

A 3D interwoven Pt@CNTs network embedded in ZnIn2S4 microspheres for Schottky-driven photothermal hydrogen evolution - Junjie Hao; Ning Li; Jingkai Lin; Chaorui Xue; Qing Chang; Xiangqian Fan; Huinian Zhang; Caihong Hao; Huayang Zhang; Shengliang Hu (Chemical Engineering Journal, 2025)

Enzymatic resistance of starch-polyphenol inclusion complexes: polyphenol inhibition and structural changes during in vitro digestion - Haoran Fan; Lin Sun; Xu Yao; Yangyang Wen; Xuesong Xiang; Hongyan Li; Jing Wang; Baoguo Sun (Carbohydrate Polymers, 2025)

Spatiotemporal dynamics of retrogressive thaw slumps on the Qinghai-Tibet Plateau: integrating UAV-LiDAR and GPR - Fan Yu; Jing Luo; Fujun Niu; Zhanju Lin; Bingyan Li; Yanhu Mu; Xin Ju; Minghao Liu; Guoan Yin; Zeyong Gao; Xiaolong Zhao; Chengming Zhang (Landslides, 2025)

Monitoring of axial force loss in Pre-tensioned anchors induced by turbidity currents erosion on underwater slopes and its failure criteria - Huan Sun; Qiaofeng Fan; Xiaoli Liu; Yi Lin; Guojie Li; Zhenni Ye (Bulletin of Engineering Geology and the Environment, 2025)

Anthropogenic land-use driven changes in soil stoichiometry reduce microbial carbon use efficiency - Xinle Tong; Lichao Fan; Mingda Wang; Jingjing Guo; Lei Bao; Lingzhi Hui; Yichao Chen; Zhengrong Li; Shuai Qian; Xiaodong Xu; Lin Ma; Xiangtian Meng; et al. (Agriculture, Ecosystems & Environment, 2025)

Root plasticity improves the potential of maize/soybean intercropping to stabilize the yield - Zhen Fan; Pengzhao Liu; Yanrong Lin; Binbin Qiang; Zhipeng Li; Mengwei Cheng; Qihang Guo; Jinpeng Liu; Xiaolong Ren; Xining Zhao; Xiaoli Chen (Soil and Tillage Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Prediction of asphalt rheological properties for paving and maintenance assistance using explainable machine learning - Fan Zhang; Augusto Cannone Falchetto; Di Wang; Zhenkun Li; Yuxuan Sun; Weiwei Lin (Fuel, 2025)

Optimization and characterization of dummy-template molecularly imprinted polymers as sorbents for the selective recognition of the polychlorinated biphenyls - Rui Wang; Lin Liang; Wenqin Yin; Ruiying Huang; Guanhui Li; Zexiang Lu; Liwei Fan (Environmental Research, 2025)

Methoxypoly(ethylene glycol)-poly(salicylic acid) nanoparticles alleviate intervertebral disc degeneration by inhibiting ferroptosis of nucleus pulposus cells - Jialiang Lin; Yinxue Liu; Wenjing Hou; Dongwei Fan; Weishi Li; Jing Yang (Chemical Engineering Journal, 2025)

Scalable synthesis of anatase TiO2 nano-in-micro spheres for hybrid sodium-ion capacitors - Zerui Yan; Sicheng Fan; Xia Zou; Qinyao Jiang; Dafu Tang; Kun Lan; Jiaxin Li; Yingbin Lin; Zhigao Huang; Dong-liang Peng; Qiulong Wei (Chemical Engineering Journal, 2025)

An inversion method for air to land surface temperature considering different slope orientations in a high-altitude permafrost region - Wenjiao Li; Zhanju Lin; Xingwen Fan; Lei Liu; Xuyang Wu; Nuocheng Li; Peng Zhang; Xuhui Wang (Atmospheric Research, 2025)

The Adhesion Characteristics of Fouling Organism on Two Kinds of Mesh Coat - Lei Li; Jinmeng Bao; Dagui Liao; Yanan Wei; Cong Yan; Xiaoxu Fan; Shen Lin; Dan Liu; Wei Tian; Yanming Sui; Mei Jiang (Thalassas: An International Journal of Marine Sciences, 2025)

Multidecadal modulation of multi-year El Niño events over the past millennium - Shuheng Lin; Keyan Fang; Hao Wu; Hanjie Fan; Feifei Zhou; Jinbao Li; Kaiqiang Deng; Hans W. Linderholm; Song Yang (Science China Earth Sciences, 2025)

Cold-Induced RNA-Binding Protein (CIRP) Affects Cerebral Ischemia–Reperfusion Injury Through NF-κB Pathway - Yong Fan; Jingjing Wei; Lili Lin; Jinying Lin; Xiaohua Li; Liyu Xu; Xiaohui Zhou; Yongkun Li; Yongkai Yang (Molecular Neurobiology, 2025)

Berberine attenuates the expression of NLRP3 and downstream inflammasome effectors in diabetic retinopathy - Na Li; Ji-Lin Chen; Yi-Jian Sun; Jia-Fan Sun; Ting-Hua Wang; Amy Yi Hsan Saik; Alan Han-Kiat Ong (Journal of Natural Medicines, 2025)

Environmental DNA reveals anthropogenic impacts on fish diversity in mountain streams and the increasing risk of species invasion - Yu Zhou; Yunchao Luo; Fan Yu; Zihong Zheng; Jidong Li; Yu Wang; Xu Wang; Jiale Cheng; Zhongqiu Li; Lin Wang; Aichun Xu (Anthropocene, 2025)

Evaluating the sustainability potential of perennial rice in southeastern China by comparing yield, environmental impacts and economic benefits - Hailong Xu; Bianhong Zhang; Bin Qin; Jinying Li; Chaojie Lan; Jingnan Zou; Yazhou Liu; Chunlin Guo; Zhimin Lin; Qiaohong Fan; Changxun Fang; Zhixing Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Responses of plant community drought resistance and resilience to warming and nitrogen addition vary with recurrent droughts in a semi-arid grassland - Haidao Wang; Jian Song; Yongge Fan; Jianyang Xia; Lin Jiang; Qingshan Zhang; Heng Li; Jingyi Ru; Jiayin Feng; Lingjie Kong; Jiajun Zhang; Xueli Qiu; et al. (Agriculture, Ecosystems & Environment, 2025)

Assessment of spatial and temporal variability in fecal contamination patterns within urbanized bay shellfish growing area utilizing community-based microbial source tracking approaches - Jiannan Lin; Hongxia Ming; Dongwei Li; Jiajie Li; Zhongzhi Chen; Ziqi Chen; Tingting Shi; Jie Su; Jingfeng Fan (Environmental Monitoring and Assessment, 2025)

Multi-perspective analysis of long-term vehicle emissions under intensive policy updates in China - Wentian Xu; Fangyuan Zheng; Zhouzhi Li; Junxia Gao; Hui Tong; Haomiao Niu; Bin Sun; Zhaoyang Fan; Lin Wu; Hongjun Mao (Transportation Research Part D: Transport and Environment, 2025)

Multi-omics analysis reveals BPF exposure causes hepatic glucose and lipid metabolism disorder in rats by disrupting energy homeostasis - Zhi Li; Yuanyuan Wu; Mingqing Qian; Bingya Zhang; Xinxin Deng; Penghui Mao; Zhonghua Fan; Xu Fang; Lin Cheng; Xuan Liu; Li Wang; Hui Liu (Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Contact-dependent antagonism is mediated by a T7SSb toxin effector–immunity protein pair via ADP-ribosylation - Hongxin Guan; Huan Wu; Mengrou Gan; Jing Zhang; Jiajun Wang; Siyao Liu; Shuyue Chen; Yindi Jiao; Fan Li; Shiqing Huang; Sihuang Lin; Hongwei Chen; et al. (Science Bulletin, 2025)

Comparative transcriptomic and metabolomic analyses reveal the role of acidic electrolyzed-oxidizing water in enhancing disease resistance in Phomopsis longanae Chi-infected longans - Meiling Li; Zhongqi Fan; Xiaoze Dai; Mengshi Lin; Yifen Lin; Hui Wang; Ruiling Zhuo; Yen-Con Hung; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2025)

Adaptive fuzzy event-triggered and precision trajectory tracking control for underwater tracked robot - Xiaolong Yao; Kelin Feng; Kewen Li; Yongming Li; Yu Wang; Wenxing Sun; Yazhou Fan; Zheng Wang; Guohai Lin (Ocean Engineering, 2025)

Organ-specific lithium accumulation and its toxic effects on female reproduction - Qigang Fan; Yi Sun; Qingjun Shen; Yuxin Wang; Jisheng Nie; Yanbing Lin; Shuaishuai Xing; Yan Li; Benhong Xu; Jianjun Liu; Xiaoting Shen; Guangbo Qu; et al. (Journal of Hazardous Materials, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

Differential effects of biochar and straw incorporation on soil organic carbon: A case study on paddy cultivation in Northeast China - Hechong Yuan; Yaman Wu; Yuanyuan Sun; Juying Liu; Li Lin; Fan Xia; Xu Su; Qiang Sun; Jun Meng (Journal of Environmental Management, 2025)

Revealing the characteristics and nitrogen metabolism mechanism of Anammox biofilm assisted by nanoscale zero-valent iron - Zongshuo Han; Xiaoying Zheng; Zhilin Zhao; Wenfei Li; Haidong He; Yi Fan; Tao Lin (Journal of Environmental Management, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

Metabolomics, E-tongue and HS-SPME-GC–MS reveal the smoking process of Prunus mume: Changes in flavor and chemical compositions - Yun-yi Hu; Jia-li Liao; Wen-zhang Qian; Shao-jun Fan; Xiao-yi Xiao; Yao Yang; Jin-lin Guo; Shun Gao (Food Chemistry, 2025)

Optimizing nitrogen fertilization to enhance wheat productivity by regulating canopy-root traits and photosynthesis under elevated atmospheric ammonia concentration - Pengzhao Liu; Mengwei Cheng; Zhipeng Li; Zhen Fan; Yanrong Lin; Zinan Yan; Xining Zhao; Enke Liu; Tie Cai; Xiaolong Ren; Xiaoli Chen (European Journal of Agronomy, 2025)

Layered hydroxide-supported nano zero-valent iron via nanoarchitectonic design: Enhanced stability and degradation of fluorescent whitening agents - Fei Li; Chen Wang; Pingning Jin; Yaqi Lin; Yan Zheng; Jing Fan (Chemical Engineering Journal, 2025)

Revolutionary photoelectrochemical water splitting performance of BiVO₄/Bi₂S₃ heterojunction photoanodes boosted by trace bio-Cr₂O₃ through multiple mechanisms - Yefei Su; Yang Yu; Tingting Xue; Kai Teng; Yuning Fan; Jiangjun Lin; Chang Liu; Qing Qu; Lei Li (Chemical Engineering Journal, 2025)

Dietary trehalose reduced liver glycogen accumulation and promoted protein deposition in hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) fed a high-carbohydrate diet - Yi Xiao; Xingbo Su; Jiaying Xie; Huiwen Zhang; Qiming Huang; Douglas R. Tocher; Fan Lin; Cuiying Chen; Shuqi Wang; Ruixin Li (Aquaculture, 2025)

Antitumor activity and mechanistic study of steroidal saponins from the rhizomes of Paris polyphylla var. yunnanensis - Yu Zhang; Yu-Chen Fan; Yu-Chen Zhang; Qing Li; Yun-Yun Su; Chen-Sen Xu; Hao-Lin Yu; Chao Wang; Jing Zhang; Zhi-Xin Liao (Phytochemistry, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Transfer patterns of human blood to follicular fluid of per- and polyfluoroalkyl substances with distinct molecular structures and physico-chemical properties - Yun-Ting Zhang; Michael S. Bloom; Yang Zhou; Saif Ur Rehman; Chu Chu; Kun Zhao; Biao Yin; Zhong Lin; Yuan-Yuan Fan; Li-Zi Lin; Ru-Qing Liu; Weihong Tan; et al. (Journal of Hazardous Materials, 2025)

Microbial-driven mechanisms of arsenic methylation during Chinese rice wine fermentation - Yanfang Liu; Jiashun Gong; Bei Fan; Lin Li; Yangyang Xiong; Xinrui Wang; Yatao Huang; Fengzhong Wang (Food Research International, 2025)

Unravelling the pathogenesis of Vibrio parahaemolyticus infection: impacts on antioxidant and innate immunity gene responses in Scylla paramamosain - Guangxin Liu; Ce Li; Sigang Fan; Hongling Ma; Yiqin Deng; Jianjun Jiang; Changhong Cheng; Juan Feng; Li Lin; Zhendong Qin; Zhixun Guo (Fish & Shellfish Immunology, 2025)

The response of crop yield, water and nitrogen use efficiency to organic fertilizer addition: A meta-analysis - Pengzhao Liu; Yanrong Lin; Xiantong Liu; Zhipeng Li; Zhen Fan; Zinan Yan; Yulin Wu; Xining Zhao; Xiaolong Ren; Xiaoli Chen (European Journal of Agronomy, 2025)

Bisphenol AF induces lipid metabolism disorders, oxidative stress and upregulation of heat shock protein 70 in zebrafish - Bingya Zhang; Zhonghua Fan; Xuan Liu; Yuanyuan Wu; Lin Cheng; Li Wang; Hui Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Emerging tumor hypoxia-relieving nanotherapeutics for boosting photodynamic therapy - Fujun Yang; Fei Chen; Shumeng Li; Shuang Wang; Lin Peng; Shishan Deng; Fan Zhang; Udo Jeschke; Yuequan Wang; Cong Luo (Chemical Engineering Journal, 2025)

Intrinsic flame-retardant flexible polyurethane foam based on phosphorus-containing polyol with Si-O-C segment: Simultaneously improving fire safety and mechanical property - Yongjiang Li; Ailing Zhang; Yanhui Wang; Donglei Fan; Yichao Lin; Jie Liu; Tao Tang (Chemical Engineering Journal, 2025)

Chaotic climate system forecasting using an improved echo state network with sparse observations - Lin Ding; Yulong Bai; Donghai Zheng; Xiaoduo Pan; Manhong Fan; Xin Li (Science China Earth Sciences, 2025)

Rice cultivation in saline-alkaline soil shifts the coupling of phosphorus functional genes and salt tolerance genes based on metagenomic analysis - Qilin Lv; Jingbiao Fan; Tairan Zhou; Xiaocheng Pan; Huixian Li; Xueqin Ren; Lin Zhang; Shuwen Hu (Applied Soil Ecology, 2025)

Assessment of the rat acute oral toxicity of quinoline-based pharmaceutical scaffold molecules using QSTR, q-RASTR and machine learning methods - Jianing Xu; Ting Ren; Feifan Li; Shuo Chen; Tengjiao Fan; Lijiao Zhao; Rugang Zhong; Guohui Sun; Ning Lin (Molecular Diversity, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Combined analyses of metabolomics and transcriptomics reveal the mechanism of DNP and ATP regulating the metabolisms of organic acids in pulp of longan fruit during storage - Zhe Li; Hetong Lin; Lingzhen Zeng; Shucheng Li; Yueying Sang; Zhongqi Fan; Yihui Chen; Yifen Lin; Wangjin Lu; Hui Wang (Postharvest Biology and Technology, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Characterization and sources of childhood PAEs exposure from residential airborne dust in China cities - Chao Wang; Shuhan Gong; Yun Cao; Mengmeng Liu; Wenying Zhang; Xiaotong Zhang; Lin Fan; Li Li; Hang Du; Mats Tysklind; Xu Yang; Xianliang Wang (Journal of Environmental Sciences, 2025)

Adsorption and oxidation of NO and N2O on soot surfaces: Evolution of functional groups - Shuo Jin; Chenyang Fan; Zheng Fu; Haizhao Li; Ye Liu; Bin Xu; Huiyong Du; Guorong Lin; Mingliang Wei (Fuel, 2025)

Enhancing ergothioneine production in Saccharomyces cerevisiae via protein fusion technology and gene integration optimization - Shuzhen Chen; Wenjing Lin; Yan Zhang; Fan Cai; Wei Lin; Jianbin Xiao; Xingtong Chen; Qin Li; Huaidong Zhang; Mingliang Zhang; Li Li (Food Bioscience, 2025)

Selective interfacial polymerization improves reversibility of Si anodes - Wen Yang; Shuwei Li; You Liu; Yanyan Li; Ping Jiang; Xiaobo Hong; Gaofeng Li; Bo Fan; Fang Chen; Liangdong Lin; Zhijun Qiao; Dianbo Ruan (Chemical Engineering Journal, 2025)

Perylene Diimide-Based A-D-A-Type Organic Additives for Efficient and Stable Inverted Perovskite Solar Cells - Shaojian Li; Kai Chen; Haiqian Ling; Desheng Li; Weixu Duan; Zedong Lin; Cong Liu; Xiangwen Guo; Liwei Zhou; Fan Wu; Tao Liu; Bingsuo Zou (Chemical Engineering Journal, 2025)

Microwave-assisted pyrolysis of spent bleaching clay: A study of pyrolysis characteristics, kinetics, and intrinsic mechanism - Bang Yao; Li Chao; Yingwen Zhang; Yang Liu; Chunbao Zhou; Dekai Fan; Yunxiang Li; Pengfei Zhu; Wei Li; Yanran Lin; Lei Gao; Chen Chen; et al. (Chemical Engineering Journal, 2025)

Identifying Novel QTLs and Candidate Genes for Tillering Ability in Sugarcane (Saccharum spp.) - Junteng Fang; Ruiqiang Lai; Zaid Chachar; Yiyun Gui; Lina Fan; Huanzhang Lin; Weijun Cai; Yueping Su; Weiwei Chen; Xiaoming Xue; Yucong Li; Liping Xu; et al. (Sugar Tech, 2025)

Integrative analysis based on CRISPR screen identifies apilimod as a potential therapeutic agent for cisplatin-induced acute kidney injury treatment - Yunpeng Chu; Muyun Wei; Zhongyu Cao; Luan Chen; Jie Tan; Wei Bao; Fan Yang; Yingtian Zhang; Yunxiao Lin; Yutong Zhang; Shiyi Li; Cai Lv; et al. (Science China Life Sciences, 2025)

The influences of mangrove grown on sedimentary nitrate reduction activities are more pronounced in sandy coasts compared to muddy coasts - Dongfan Tian; Xianbiao Lin; Pengfei Zheng; Guoling Zhang; Jing Li; Mingrui Wang; Kangwei Liu; Tiantian Kong; Shiyuan Fan; Peng Guo; Sumei Liu (Plant and Soil, 2025)

Identification and stability of QTLs for grain traits in the elite wheat variety ‘Chuanmai104’ - Zehou Liu; Hao Tang; Yuanyuan Lin; Xiaojiang Guo; Huixue Dong; Li Cai; Ying Liu; Qin Wang; Hongshen Wan; Fan Yang; Ning Yang; Jirui Wang; et al. (Cereal Research Communications, 2025)

Responses of carbon storage to thinning intensity of Larix principis-rupprechtii Mayr - Kuangji Zhao; Yifei Lin; Shilong He; Chuan Fan; Shun Gao; Fang He; Ziteng Luo; Guirong Hou; Gang Chen; Zhongkui Jia; Xianwei Li (Mitigation and Adaptation Strategies for Global Change, 2025)

Experimental study of acid couple microemulsion to release blockage in condensate gas reservoirs - Yi Lin; Xiangjun Liu; Xiangchen Li; Fan Zhang; Shan Yang (Geosciences Journal, 2025)

Dynamic Modeling and Experimental Validation of Shock Isolation Performance for Shipborne Stewart-Platform-Based Bumper - Yongqiang Tu; Haoran Zhang; Yintao Li; Wei Wang; Gang Lu; Hongwei Lin; Xinkai Chen; Yan Huang; Jianyu Fan (Journal of Marine Science and Engineering, 2025)
The Stewart-platform-based bumper plays a critical role in shipborne strap-down inertial navigation systems (SINSs), effectively mitigating shock-induced disturbances to ensure measurement accuracy. Dynamic modeling for the bumper under a huge impact is a key issue in predicting the shock isolation performance of the bumper. In this paper, the dynamic modeling of shock isolation performance for Stewart-platform-based bumpers under huge impacts is proposed and validated experimentally. Firstly, a model of a Stewart-platform-based bumper is established considering the geometric configuration and dynamic parameters of the bumper by calculating the Jacobian matrix, stiffness matrix, damping matrix and mass matrix. Secondly, an analytic simulation of the impact is presented based on the measured impact acceleration, and the impact force on the load is derived according to the non-displacement assumption in the impact stage. Then, the Lagrangian formulation was systematically applied to establish governing equations characterizing the six-degree-of-freedom (DOF) dynamics of the bumper, incorporating both inertial coupling effects and nonlinear shock energy dissipation mechanisms. Afterwards, dynamic equations were solved via the Runge–Kutta method to obtain the theoretical results. Finally, the proposed dynamic modeling and shock isolation performance analysis method was validated via impact experiments for the bumper.

COP1 Overexpression Attenuates Nociceptive Behaviors and Neuroinflammation in Cancer-Induced Bone Pain by Suppressing c/EBPβ - Dan-Yang Li; Lin Liu; Shao-Jie Gao; Dai-Qiang Liu; Long-Qing Zhang; Jia-Yi Wu; Fan-He Song; Xin-Yi Dai; Ya-Qun Zhou; Wei Mei (Journal of Neuroimmune Pharmacology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Integrative transcriptomic and metabolomic analyses reveal the mechanisms behind acidity differences in the pulp of fresh longan cv. ‘Fuyan’ and ‘Dongbi’ during storage - Lingzhen Zeng; Yueying Sang; Shucheng Li; Mengshi Lin; Yifen Lin; Hui Wang; Yihui Chen; Wangjin Lu; Zhongqi Fan; Hetong Lin (Postharvest Biology and Technology, 2025)

Unraveling the molecular transformation of textile-dyeing wastewater DOM: A key to optimizing full-scale TDWW treatment performance - Minru Liu; Xiaojun Niu; Zhenrong Lin; Xuechang Ren; Kejing Fang; Zhihua Tang; Qizhe Fan; Kai Li (Journal of Water Process Engineering, 2025)

Hierarchical PVA/SiO₂ hybrid coating constructs superhydrophilic/underwater superoleophobic polypropylene membranes for efficient emulsion separation - Shuang Man; Lin Yang; Xinyue Fan; Jie Chen; Zhengkang Shi; Ming Zhang; MeiTong Li (Journal of Water Process Engineering, 2025)

Disparities in residential PM2.5 and disease burden across urban and peri-urban: A 2018–2019 multicenter on-site survey in China - Lin Fan; Wenying Zhang; Xiaotong Zhang; Hang Du; Weiyi Zhang; Li Li; Xu Han; Chao Wang; Wenhao Wang; Xianliang Wang (Journal of Environmental Management, 2025)

Flexible self-decoupled pressure/proximity/temperature sensor for composite stimulus sensing with low signal crosstalk - Qi Hong; Junjie Qiu; Jianhong Hao; Zihan Lin; Ziyuan Zhou; Xishun Ruan; Tianxu Zhang; Fan Yao; Zhitong Wang; Zhaobin Li; Weiqiang Hong; Xianghui Li; et al. (Chemical Engineering Journal, 2025)

Specifically targeted antimicrobial cyclic peptide to staphylococcal protein A for the treatment of S. aureus infection - Xiao-Ling Lei; Yong Li; Xue-Ting Cheng; Jie Zhuang; Fang Zhang; Xiao-Ting Xie; Lin-Fang Tan; Jin-Xuan Fan; Yuan-Di Zhao; Chuan-Liu Wu; Kai Cheng (Chemical Engineering Journal, 2025)

Triethoxysilane-enhanced graphene/carbon nanoparticles conductive network for multifunctional fabric electronics with pressure, temperature and strain sensing capabilities - Yunong Zhao; Jianhong Hao; Zihan Lin; Shaowen Mou; Shujing Feng; Fan Yao; Ziyuan Zhou; Zhitong Wang; Zhaobin Li; Xianghui Li; Xiaowen Zhu; Tianxu Zhang; et al. (Chemical Engineering Journal, 2025)

Special functionalized binder chemistry boosting high-rate and long-life sodium ion batteries - Jing-Chao Liu; Xiao Liu; Tao You; Yi-Fan Zhao; Feng-Quan Liu; Chen Wang; Lin Li (Chemical Engineering Journal, 2025)

Mo isotope evidence for the significance of subducted continental crust in formation of post-collisional porphyry Cu deposits - Jing Jing Fan; Qiang Wang; Xiao Ping Long; Derek A. Wyman; Andrew C. Kerr; Jie Li; Zi Long Wang; Lin Gong; Dong Jing Xu; Qi Ji Yang; Le Zhang; Ze-Xian Cui (Chemical Geology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

One-step colorimetric immunosensing of foodborne bacteria using static magnet driven magnetophoretic separation and dual noble metal decorated magnetic nanobeads - Ying Ding; Jing Yuan; Nana Jin; Fengzhen Yang; Fan Jiang; Lei Wang; Yanbin Li; Jianhan Lin (Analytica Chimica Acta, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

An Approach to Optimize the Efficiency of an Air Turbine of an Oscillating Water Column Based on Adaptive Model Predictive Control - Yan Huang; Weixun Dong; Jianyu Fan; Shaohui Yang; Zhichang Du; Yongqiang Tu; Chenglong Li; Beichen Lin (Journal of Marine Science and Engineering, 2025)
Wave energy, as a vast renewable resource, remains underutilized despite its high potential. The oscillating water column (OWC) is one of the most efficient way to harvest wave energy. Due to the randomness of ocean wave excitation, a control strategy is needed to keep the conversion efficiency of OWC at a certain level. In this paper, an adaptive model predictive control (AMPC) method is proposed to optimize the efficiency of the air turbine and improve the overall efficiency of the OWC. Experiments were conducted in a wave flume to obtain realistic wave data, which were fed into the AMPC model for simulations. Results indicate that AMPC-optimized turbine efficiency exhibits improved performance under regular wave conditions and significantly enhances efficiency within certain intervals under short-period irregular waves. However, as the wave period increases, optimization becomes less stable. Overall, the study concludes that the adaptive MPC model effectively optimizes turbine efficiency under most conditions, highlighting its potential for enhancing OWC performance.

Minor protopanaxadiol type sapogenins from the alkali hydrolysate of stems-leaves of Panax notoginseng - Cong-Cong Jing; Jing-Min Wang; Pei Wang; Lin Guo; Shu-Min Zhang; Ke Liu; Zhen-Yuan Li; Hua-Ying Fan; Ze-Ping Xie (Natural Product Research, 2025)

Flow analysis and fate of mercury in Chinese polyvinyl chloride production - Dandan Liu; Gang Fang; Yuchen Lin; Fan Wang; Zixiu Li; Chunge Dang (Process Safety and Environmental Protection, 2025)

Phanerochaete chrysosporium hyphae bio-crack, endocytose and metabolize plastic films - Lele Li; Zhi Guo; Xingpan Guo; Dazhuang Dong; Ting Fan; Lin Yao; Yuanyuan Zha; Jianyu Kong; Yaodan Dai; Tao Pan (Journal of Hazardous Materials, 2025)

Recent advances in integrating solvent-based CO2 capture with electrochemical regeneration process: A review - Peng Liu; Hanming Liu; Kangkang Li; Zian Fan; Qichen Lu; Beiqi Sun; Lin Hu; Ling Yin; Xiaolong Wang; Lianbo Liu (Fuel, 2025)

Integrative analyzing the molecular basis of Clerodendranthus spicatus aqueous extract in hyperuricemia nephropathy via network pharmacology and experimental validation - Chuang Li; Danyao Lin; Jianting Ouyang; Junyi Liu; Shouhai Wu; Delun Li; Fan Yang; Haohao Quan; Yimeng Li; Qiaoru Wu; Guirui Huang; Wei Mao (Food Bioscience, 2025)

Natural borneol improves cellular uptake of curcumin to enhance its photodynamic bactericidal activity against Escherichia coli ATCC 8739 - Zhenlong Zhou; Ruoxin Chen; Pengzhen Li; Penghui Fan; Lin Ma; Xinyu Cai; Yuchao Hou; Binbin Li; Jianyu Su (Food Microbiology, 2025)

Characteristics of ozone pollution and VOCs source analysis in the northern cities of Zhejiang, China - Yinglong Zhang; Xiaoxia Yang; Xu Lin; Ye Lu; Li Li; Xiaopei Xu; Jing Yuan; Fan Zhang; Xinglong Pang; Huanhuan Zhao; Xinming Zhu; Yaozong Shen; et al. (Atmospheric Pollution Research, 2025)

The involvement of auxin response factor OsARF7 in positively regulating root development by mediating the expression of OsCRL1 in rice (Oryza sativa L.) - Congying Sun; Kai Fan; Xin Wang; Honghai Liu; Nuoping Guo; Wanyu Liu; Guixiang Ye; Weiwei Lin; Wenxiong Lin; Zhaowei Li (Plant Molecular Biology, 2025)

Differences in Pathogenetic Mechanism Between Tibetan and Han High-Altitude Polycythemia Based on a Whole Genome-Wide Association Study - Zhuoma Basang; Shixuan Zhang; Xianwei Ke; Zhuoma Duoji; La Yang; Danzeng Qiangba; Yang De; Deji Gesang; Zixin Hu; Yanyun Ma; Meng Hao; Ruidong Fan; et al. (Phenomics, 2025)

Regulation mechanisms of tea residue-based carbon dots in water-induced full-color emission and applications of visual ratio water sensors in organic solvents and WLEDs - Chao Yong; Ying Lei; Jian Du; Yinghui Liu; Yu Li; Fan Ye; Lin Xu; Guobin Ni; Shaowu Zhang (Analytica Chimica Acta, 2025)

Efficient conversion and highly sensitive detection of PAEs in milk based on hydrazinolysis reaction and hydrogen bonding using SERS technique - Lili Hua; Hongmei Li; Jing-Wen Zhou; Xiao-Feng Liu; Xian-Ming Guo; Zhao-Bing Zhang; Yichuan Kou; Tang-Tang Xie; Cuihong Sheng; Lin Zhang; Sheng-Hong Liu; Fan-Li Zhang; et al. (Analytica Chimica Acta, 2025)

Urea Amidolyase as an Enzyme for Urea Utilisation in Phytoplankton: Functional Display in Chlamydomonas reinhardtii - Honghao Liang; Tangcheng Li; Yuanhao Chen; Jingtian Wang; Muhammad Aslam; Huaizhi Qin; Wenkang Fan; Hong Du; Shuh‐ji Kao; Senjie Lin (Molecular Ecology, 2025)
Urea is an important source of nitrogen for many phytoplankton with the potential to stimulate harmful algal blooms, but the molecular machinery underpinning urea uptake and assimilation by algae is not fully understood. Urease (URE) is commonly regarded as the responsible enzyme, but urea amidolyase (UAL), albeit known to exist, has hardly been studied. Here, the species distribution, expression patterns and functional roles of UAL are examined. We found a widespread occurrence of UAL across six major phytoplankton lineages, along with evidence of a potential URE‐independent evolutionary trajectory and lineage‐specific losses. Quantitative analyses based on marine planktonic metagenomes and metatranscriptomes revealed that UAL is as prevalent as URE, but exhibits higher expression levels in phytoplankton than in bacteria, suggesting that UAL plays a crucial role in nitrogen nutrition in marine phytoplankton. Furthermore, using the CRISPR/Cas9 genome editing method and Chlamydomonas reinhardtii as the algal model, we showed that DUR2 in UAL is essential for urea utilisation, as its knockout completely abolishes the ability of algae to grow under urea as the sole nitrogen source. This study unveils an unappreciated mechanism in algae for utilising urea as a nutrient, underscores the need to consider both URE and UAL enzyme systems to model urea utilisation by algae and provides a crucial gene ( DUR2 ) as a potential genetic marker for detecting the contribution of UAL to urea utilisation in phytoplankton.

OncomiR mdv1-miR-M7-5p promotes avian lymphomatosis by modulating the BCL2/Bax mitochondrial apoptosis signaling pathway - Jun Zhou; Fan Yang; Congsen Zheng; Yanting Chen; Meiting Chen; Qiaoer Lin; Chuanzhe Chang; Shikai Cai; Zhaoyang Sun; Hua Li; Limei Qin; Yanfeng Chen (Veterinary Microbiology, 2025)

Frost heave evaluation and prediction of high-speed railway subgrade with coarse filler in high altitude seasonal frozen region, northwest China - Xuyang Wu; Zhanju Lin; Fujun Niu; Xingwen Fan; Minghao Liu; Chunqing Li; Yunhu Shang (Transportation Geotechnics, 2025)

Retrieval of 1 km surface soil moisture from Sentinel-1 over bare soil and grassland on the Qinghai-Tibetan Plateau - Zanpin Xing; Lin Zhao; Lei Fan; Gabrielle De Lannoy; Xiaojing Bai; Xiangzhuo Liu; Jian Peng; Frédéric Frappart; Kun Yang; Xin Li; Zhilan Zhou; Xiaojun Li; et al. (Remote Sensing of Environment, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Depositional evolution and sedimentary response to sea level changes of the lower Cambrian carbonate platform of the Wusonggeer Formation, Tarim Basin, northwest China - Xuqiao Wu; Changsong Lin; Wenfang Yuan; Hao Li; Xianzhang Yang; Fan Xu; Manli Zhang; Xiangyu Liu (Marine and Petroleum Geology, 2025)

How bedding-parallel fractures affect fluid activity in a relatively closed lacustrine shales system: Evidence from calcite veins - Zilong Li; Kelai Xi; Xiaobing Niu; Xiujuan Wang; Wenzhong Ma; Xiao Hui; Jiangyan Liu; Changyu Fan; Miruo Lin; Keyu Liu; Yingchang Cao (Marine and Petroleum Geology, 2025)

Complex cleavage of Ni(II)-EDTA in electroplating wastewater: Complex cleavage sites, degradation pathways and recovery of precipitates - Chengyang Nan; Qingjin Lin; Qiantong Liang; Tianyun Liang; Yu Huang; Zhijie Guan; Wencan Dai; Zhenhua Huang; Depeng Fan; Shuiyu Sun; Shoupeng Li (Journal of Water Process Engineering, 2025)

Coral-Symbiodiniaceae symbiotic associations under antibiotic stress: Accumulation patterns and potential physiological effects in a natural reef - Zhicong Yan; Xiaocong Cao; Hao Su; Changqing Li; Jiamin Lin; Kai Tang; Jiahua Zhang; Hangbo Fan; Qin Chen; Jia Tang; Zhi Zhou (Journal of Hazardous Materials, 2025)

Effects of different drying methods on the structure, bioaccessibility, and bioavailability of selenium-enriched peptides from soybean sprouts - Yangyang Xiong; Bei Fan; Lin Li; Yanfang Liu; Xinrui Wang; Chengxin Fei; Litao Tong; Fengzhong Wang; Yatao Huang (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Cholesterol suppresses AMFR-mediated PDL1 ubiquitination and degradation in HCC - Wei-Qing Shao; Yi-Tong Li; Xu Zhou; Sheng-Guo Zhang; Ming-Hao Fan; Dong Zhang; Zhen-Mei Chen; Chen-He Yi; Sheng-Hao Wang; Wen-Wei Zhu; Ming Lu; Ji-Song Chen; et al. (Molecular and Cellular Biochemistry, 2025)

α-asarone activates mitophagy to relieve diabetic encephalopathy via inhibiting apoptosis and oxidative stress - Xiao-dan Yan; Rong-hua Fan; Yu Wang; Xiao-xu Duan; Xuan Wei; Lin-sen Li; Qing Yu (Metabolic Brain Disease, 2025)

Taloring sawdust derived hydrochar via red mud for cadmium removal: Electron transfer insight and recyclability assessment - Ting Cui; Dingxiang Chen; Ran Duan; Fan Yang; Danting Li; Lin Tian; Yong Zhang; Huabin Wang; Rui Xu (Chemosphere, 2025)

Docosahexaenoic acid alleviated liver lipid deposition and health damage induced by cholesterol accumulation in hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) - Qiming Huang; Huiwen Zhang; Xingbo Su; Yi Xiao; Jiaying Xie; Douglas R. Tocher; Fan Lin; Cuiying Chen; Shuqi Wang; Ruixin Li (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Calcium and iron isotope fractionation during felsic magma differentiation - Qiu-Yun Guan; Jin-Xiang Li; Ya-Li Sun; Shi-Lei Tang; Noreen J. Evans; Zhao-Feng Zhang; Li-Yun Zhang; Fu-Long Cai; Wei-Ming Fan; Lin Ding (Lithos, 2025)

Light iron isotopes in high-silica granites record fluid evolution in magmatic-hydrothermal systems - Qi-Wei Li; Qiang Wang; Lin Ma; Andrew C. Kerr; Jing-Jing Fan; Jun-Hong Zhao; Hai-Ou Gu; Wei Wang; Zhi-Kun Su (Geochimica et Cosmochimica Acta, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Mitochondrial homeostatic imbalance-mediated developmental toxicity to H2S in embryonic zebrafish - Yinai Liu; Yu Cao; Huiqi Li; Huanpeng Liu; Ting Chen; Qizhuan Lin; Changyong Gong; Fan Yu; Helei Cai; Libo Jin; Renyi Peng (Environmental Pollution, 2025)

Sucrose non-fermenting 1-related protein kinase 2–14 participating in lipid elevating efficacy and biodiesel upgrade by Coccomyxa subllipsoidea - Yuanyuan Luo; Sisi Zhao; Zhixuan Fan; Yuqin Li; Zongfan Peng; Yulong Zhang; Siran Feng; Jinhua Mou; Zhenyao Wang; Carol Sze Ki Lin; Xuan Li (Chemical Engineering Journal, 2025)

Corrigendum to “Platelet-rich plasma/chitosan/chondroitin sulfate immunomodulatory hydrogel co-networks for diabetic wound repair: Functions and molecular mechanisms” [Chem. Eng. J. 491 (2024) 152138] - Zi-Lin Wang; Lin-Yue Li; Hong-Jie Liu; Ya-Ling Fan; Yu-Xue Shen; Fei Song; Li-Li Zhu (Chemical Engineering Journal, 2025)

Graphene bilayer film responsive to ultraviolet, humidity, and temperature - Lin Wang; Tao Wang; Yalong Li; Yi Huang; Rui Li; Jing Zhang; Jie Jiang; Pei Li; Yan Fan; Liang Chen (Chemical Engineering Journal, 2025)

A fully integrated, non-invasive, and multimodal wearable device for sweat stimulation, collection and multiple physiological signals analysis - Yuetao Zhang; Zijie Li; Xuejiao Fan; Yan Liu; Zhiqi Li; Ziwei Zheng; Zixin Lin; Wenshan Zhang; Qingci Mu; Guangquan Mo; Yong Xia; Lei Mou (Chemical Engineering Journal, 2025)

Charged defect management for high-efficiency planar solar cells: Reducing charge recombination and open-circuit voltage loss by employing donor-acceptor molecules to regulate perovskite electronic properties - Miao Yu; Lin Fan; Lixue Wang; Chuanlong Bi; Yuan Gao; Jiadong Liu; Fengyou Wang; Xin Li; Qiong Wu; Xiaoyan Liu; Huilian Liu; Lili Yang (Chemical Engineering Journal, 2025)

Membrane transport engineering for efficient yeast biomanufacturing - Xin-Yue Li; Ming-Hai Zhou; Du-Wen Zeng; Yi-Fan Zhu; Feng-Li Zhang; Sha Liao; Ya-Chao Fan; Xin-Qing Zhao; Lin Zhang; Feng-Wu Bai (Bioresource Technology, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

The independent and combined associations of nocturnal sleep duration, sleep midpoint, and sleep onset latency with global cognitive function in older Chinese adults - Xueyao Wu; Jiaqiang Liao; Xin Chen; Jinyu Xiao; Xinyang Dui; Tianpei Ma; Lin Hu; Xunying Zhao; Qian Bu; Mengyu Fan; Tao Zhang; Lu Long; et al. (GeroScience, 2025)

Evaluation of pollution potential in swine manure across growth stages: Impact of dietary nutrients and management strategies - Hongyong Fan; Chenghao Li; Wenxuan Zhang; Chaoxiang Liu; Olusegun K. Abass; Lin Liu; Xu Huang; Yingjie Sun; Huawei Wang; Maureen W. Gesiye; Wushan Chen (Science of The Total Environment, 2025)

Selective anchoring of phosphate groups coupled with swift interlayer cation exchange for record-high capacity cobalt adsorption - Lingrong Zeng; Ziwei Yao; Dewei Li; Qingying Xiao; Ziwen Chang; Jingjing Fan; Shuigen Li; Mengling Li; Lin Ding; Penghui Shao; Xubiao Luo; Shenglian Luo (Resources, Conservation and Recycling, 2025)

Sophflarines B−E, four distinctive matrine alkaloids from Sophora flavescens with potential neuroprotective activities - Ding Luo; Qian Xie; He Tian; Xin-Kai Zheng; Jia-Wen Zou; Yue-Hao Huang; Yan-Jun Chen; Chun-Lin Fan; Li-Jun Hu; Jian-Xin Chen; Hao Wang; Guo-Cai Wang; et al. (Phytochemistry, 2025)

Discovery of cycloheptapeptides phakefusins A−E from the marine sponge Phakellia fusca based on molecular networking - Ying Wu; Zhao-Ze Xu; Can Kong; Shuai-Shuai Zhang; Xin-Li Lin; Si Zhang; Li-Yun Liu; Fan Sun; Hou-Wen Lin; Shu-Ping Wang (Phytochemistry, 2025)

Grazing increases the complexity of networks and ecological stochastic processes of mycorrhizal fungi - Jiqiong Zhou; Pengsen Wang; Li Wei; Jianguo Zhang; Xuxu Li; Nan Huang; Gang Liu; Kun Zou; Rui Fan; Lin Liu; Xiao Ma; Ting Huang; et al. (Journal of Environmental Management, 2025)

The relationship between indoor airborne culturable bacteria with passenger flow in 132 traffic stations during 2019–2020, China - Li Li; Hang Du; Chong Meng; Lin Fan; Hang Liu; Xu Han; Tanxi Ge; Liqin Su; Xiaoyuan Yao; Xianliang Wang (Journal of Environmental Management, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Intelligent control of ginger far-infrared radiation and hot-air drying based on multi-sensor fusion technology - Yongsheng Pei; Lin Fan; Changzhi Wang; Guizhong Tian; Xiangyi Meng; Zhenfeng Li; Wanxiu Xu (Food and Bioproducts Processing, 2025)

Numerical investigations of the mechanical properties and energy characteristics of sandy cobble strata considering its internal stochastic structures - Fan Wang; Pengfei Li; Xiuli Du; Jianjun Ma; Lin Wang (Computers and Geotechnics, 2025)

Preparation of nanocellulose-silk fibroin stiff hydrogel and high absorbing-low expansion xerogel via polysaccharide-protein interactions - Yue Ma; Tian Huang; Zhixing Hu; Juan Yu; Liang Liu; Lin Lin; Meijuan Chen; Ruoxian Jia; Xin Li; Zhiguo Wang; Yimin Fan (Carbohydrate Polymers, 2025)

Developing filamentous fungal chassis for natural product production - Jie Fan; Peng-Lin Wei; Yuanyuan Li; Shengquan Zhang; Zedong Ren; Wei Li; Wen-Bing Yin (Bioresource Technology, 2025)

Identification of a dual functional betulinic acid analog for the treatment of osteoarthritis by phenotypic screening - Ze-Min Lin; Mai Xiang; Wen-Hui Wei; Shu-Hui Fan; Li Chen; Jie Wang; Xiao-Qian Yang; Chun-Hao Yang; Shi-Jun He; Jian-Ping Zuo (Science China Life Sciences, 2025)

Blocking the PD-1 signal transduction by occupying the phosphorylated ITSM recognition site of SHP-2 - Wenjie Li; Wenyi Mei; Hewei Jiang; Jie Wang; Xiaoli Li; Lina Quan; Yanyan Diao; Yanni Ma; Sisi Fan; Zhuwei Xie; Mengdie Gong; Huan Zhu; et al. (Science China Life Sciences, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Metagenomic Analysis of Gut Microbiome of Persistent Pulmonary Hypertension of the Newborn - Linli Han; Chuyang Lin; Yue Lan; Yimin Hua; Jinlin Wu; Zhenxin Fan; Yifei Li (Cardiovascular Toxicology, 2025)

The first genetically confirmed live sighting of the Deraniyagala's beaked whale ( Mesoplodon hotaula ), with insights into the diversity, phylogeny, and past demographic history - Wenzhi Lin; Hui Kang; Inge Seim; Binshuai Liu; Shenglan Chen; Mingming Liu; Lijun Dong; Mingli Lin; Yuhang Song; Mingyue Ouyang; Xiaoyu Huang; Yingxue Gao; et al. (Marine Mammal Science, 2025)
Beaked whales have recently been reported in the South China Sea but with taxonomic uncertainty due to their ambiguous morphological features. Here, we sequenced three genetic markers, the control region (CR) and cytochrome b ( cytb ) of the mitochondrial genome and the first intron of the nuclear muscle actin gene ACTA2 , of two biopsy samples collected in 2021, and revealed unambiguous clustering with sequences previously attributed to Deraniyagala's beaked whale ( Mesoplodon hotaula ). Phylogenetic analysis of complete mitogenomes strongly supported the close relationship between the Deraniyagala's beaked whale and the ginkgo‐toothed beaked whale ( M. ginkgodens ). Whole‐genome sequencing suggested a high degree of heterozygosity in the Deraniyagala's beaked whale. Ancient inbreeding may have had a greater impact than the recent inbreeding on Deraniyagala's beaked whales, but more samples are needed to draw a firm conclusion. The approximate effective population size of Deraniyagala's beaked whale was found lowest among seven examined ziphiids, which has been experiencing a steady decline since ~300,000 ya. Therefore, we suggest that the conservation status of Deraniyagala's beaked whales should be assessed when essential information is available. The results of our study provide genetic evidence of the live sighting of Deraniyagala's beaked whale in the South China Sea and are fundamental to understanding the morphological, behavioral, and ecological perspectives of this cetacean species.

Higher water content observed in smaller size fraction of Chang'e-5 lunar regolith samples - Honglei Lin; Rui Xu; Shuai Li; Rui Chang; Hejiu Hui; Yang Liu; Hengci Tian; Kai Fan; Zhiping He; Huaiyu He; Wei Yang; Yangting Lin; et al. (Science Bulletin, 2024)

Urban surface-emitted longwave radiation estimation from high spatial resolution thermal infrared images using a hybrid method - Songyi Lin; Huazhong Ren; Rongyuan Liu; Jinxiang Li; Shanshan Chen; Yuanjian Teng; Wenjie Fan; Baozhen Wang; Yu Liu (Remote Sensing of Environment, 2024)

Transitions between Chinese dynasties influenced by spatial-patterned precipitation - Haowen Fan; Chaoyong Hu; Zunyu Hu; Zherui Lin; Yuhui Liu; Lianlian Li; Rongbei Qin; Jingyun Zheng; Xuejia Wang; Deliang Chen (Quaternary Science Reviews, 2024)

Forms of rare earth loss and the function mechanism of acetic acid in the aluminum removal process of rare earth leaching liquor - Chen Xin; Chen Jin-fa; Xiao Xin-lei; Fan Lin; Xiao Yan-fei; Huang Li (Minerals Engineering, 2024)

Association between iron status, preeclampsia and gestational hypertension: A bidirectional two-sample Mendelian randomization study - Pengsheng Li; Haiyan Wang; Ting Chen; Gengdong Chen; Zixing Zhou; Shaoxin Ye; Dongxin Lin; Dazhi Fan; Xiaoling Guo; Zhengping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

“Nano knife” for efficient piezocatalytic inactivation of amoeba spores and their intracellular bacteria: Synergetic effect between physical damage and chemical oxidation - Huinan Zhao; Jianyi Zheng; Wei Huang; Zhenzhen He; Fan Huang; Lin Zhang; Tao Zhong; Yadi Li; Dehua Xia; Longfei Shu; Chun He (Journal of Hazardous Materials, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

Black soldier fly larvae promote the resource of cyanobacteria: Frass-mixed compost - Rui Li; YuFeng Jiang; ChangXue Wang; Kai Luo; XiaoLei Fan; TianHui Lin; RongBo Guo; ShanFei Fu (Journal of Environmental Chemical Engineering, 2024)

The rational design of ratiometric probe based on fluorescence carbon dots and its PVA film platform for the detection of Hg2+: Tunable mechanism and the performance - Qiuyan Hu; Haiying Lin; Qingge Feng; Xianghua Wu; Lixin Huang; Yu Duan; Wenlu Lan; Zixuan Chen; Lianghong Li; Jiatong Lv; Jie He; Chun Lv; et al. (Journal of Environmental Chemical Engineering, 2024)

Excellent antibiotic degradation through PMS activation via bio derived Fe-Mn oxides with tunable defect concentration: Synergy between singlet oxygen oxidation and electron transfer - Kai Teng; Jiajie Wu; Yuxi Chen; Lin Ge; Guang Li; Yuning Fan; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2024)

The key role of Sn in enhancing Rh recovery from spent automotive catalysts - Xiaoyun Jia; Duchao Zhang; Yongmi Wang; Tingying Li; Bing Fan; Lin Chen; Weifeng Liu (Journal of Environmental Chemical Engineering, 2024)

Inventory of active rock glaciers and their distribution characteristics on the Qinghai-Tibet Plateau and its adjacent mountainous regions - Nuocheng Li; Zhanju Lin; Huini Wang; Fujun Niu; Xingwen Fan; Jing Luo; Wenjiao Li; Xuyang Wu (Geomorphology, 2024)

A multimetallic nanozyme enhanced colorimetric biosensor for Salmonella detection on finger-actuated microfluidic chip - Fan Jiang; Nana Jin; Lei Wang; Siyuan Wang; Yanbin Li; Jianhan Lin (Food Chemistry, 2024)

Lignanamides: A comprehensive review of chemical constituents, biological activities, extraction methods and synthetic pathway - Jing Sun; Li-Tao Tong; Peng-Fei Tu; Lin-Lin Chen; Xin Xu; Ya Song; Xin-Xin Yang; Zi-Bin Guo; Xiang Zou; Chen-Xin Sun; Yan Mi; Bei Fan; et al. (Food Chemistry, 2024)

Phenolic compounds in dietary target the regulation of gut microbiota: Role in health and disease - Qinqiu Zhang; Yi Xu; Danka Bukvicki; Yue Peng; Fan Li; Qing Zhang; Jing Yan; Shang Lin; Shuxiang Liu; Wen Qin (Food Bioscience, 2024)

Acesulfame potassium induces hepatic inflammation and fatty acids accumulation via disturbance of carnitine metabolism and gut microbiota - Na Shou; Christopher Rensing; Qiwen Lin; Wenqian Xu; Keyi Fu; Xuefeng Yuan; Dandan Wu; Fan Wang; Yanzhong Li; Zunji Shi (Food Bioscience, 2024)

Unraveling the intrinsic mechanism of recyclable octahedral Fe3S4-triggered peroxydisulfate activation for contaminant degradation: The pivotal role of high-valent iron-oxo species - Jiaqu Tan; Zhuoxun Tian; Fengjie Qin; Qiaojuan Kong; Dongya Li; Fan Yang; Zhen Zhang; Yulong Zhang; Yongtao Li; Xueming Lin (Chemical Engineering Journal, 2024)

Two new furanone derivatives from the endophytic fungus Byssochlamys sp. and their cytotoxic activities - Jie Wang; Wen-Bin Gao; Fan-Wei Liu; Qi Liu; Bo Song; Jin Ye; Ying Chen; Cai-Lin Zhao; Wei Dong; Li-Na Guo; Bo Song (Natural Product Research, 2024)

EBV + B cell-derived exosomes promote EBV-associated T/NK-cell lymphoproliferative disease immune evasion by STAT3/IL-10/PD-L1 pathway - Wei Chen; Yao Xie; Fan Li; Pengfei Wen; Lin Wang (Immunologic Research, 2024)

Litter quality regulates cover crop litter decay alongside altered microbial facets - Guilong Li; Ke Leng; Wenjing Qin; Xiaofen Chen; Yongxin Lin; Ming Liu; Meng Wu; Jianbo Fan; Xiaoyue Wang; Yuji Jiang; Jia Liu (Applied Soil Ecology, 2024)

Mechanism of JNK action in oxidative stress–enhanced gut injury by Clostridium perfringens type A infection - Hailan Lin; Yifan Liu; Ling Zhang; Fan Yang; Yanqing Liu; Yuhang Li; Yuxuan Liu; Zhiyun Qiu; Hongyue Chen; Daoling He; Yan Zhu; Ling Gan (Veterinary Microbiology, 2024)

Carbon emission reduction model for sewage heat recovery and utilization in a northern Chinese city - Tongyu Xu; Yiming Fan; Pengxuan Wang; Yue Zhou; You Li; Jing Xie; Xiaoyang Wang; Jianing Hu; Yingzi Lin; Xindong Wei; Weijun Gao; Chunyan Shi (Sustainable Cities and Society, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Nitrogen isotope characteristics and importance of NOx from biomass burning in China - Zanfang Jin; Jiawen Li; Qiang Yang; Yasheng Shi; Xun Lin; Fan Chen; Qifang Chen; Zhili Chen; Feili Li (Science of The Total Environment, 2024)

Cannabidiol exposure during embryonic period caused serious malformation in embryos and inhibited the development of reproductive system in adult zebrafish - Lin Li; Bei Fan; Yifan Zhang; Mengying Zhao; Zhiqiang Kong; Fengzhong Wang; Minmin Li (Science of The Total Environment, 2024)

Unveiling the synergism and reaction pathway of ethyl acetate removal in DBD/absorption integrated reactor - Li-qiang Qi; Lin Huang; Jia-yue Lei; Rui Dai; Fan Du; Bo Wang; Jing-xin Li; Feng Liu (Process Safety and Environmental Protection, 2024)

Mrlac1, an extracellular laccase, is required for conidial morphogenesis as well as the well adaptability in field of Metarhizium rileyi - Yunlong Lin; Liqin Fan; Xi Gao; Xiaoli Li; Miao Lin; Qi Luo; Hongli Li; Zhongkang Wang; Guoxing Wu (Pesticide Biochemistry and Physiology, 2024)

Cyclic di-GMP incorporates the transcriptional factor FleQ03 in Pseudomonas syringae MB03 to elicit biofilm-dependent resistance in response to Caenorhabditis elegans predation - Xiaowen Sun; Fan Xiao; Yuwei Su; Zhi Li; Xun Yu; Rebecca E. Parales; Lin Li (Journal of Invertebrate Pathology, 2024)

Performance of carbon felt as cathodes in magnesium corrosion method to recover phosphate from swine wastewater - Ying Xiang; Weike Lin; Jinfeng Wei; Fan Yang; Meng Guo; Can Li; Jin Li; Fang Wang (Journal of Environmental Management, 2024)

One-stone-for-two-birds strategy to achieve effective electrochemical nitrate reduction towards ammonia synthesis with Ru doped cobalt tungstate - Xue Bai; Keyu Zhou; Lan Lin; Huiying Li; Qianggen Li; Guangyin Fan (Fuel, 2024)

Acrolein exposure affects ovarian function by interfering with glycolysis and mitochondrial energy metabolism in mouse - Yan-Zhu Chen; Wen-Ke Wang; Yi-Fan Yang; Si-Yao Cheng; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Yu Liu (Environmental Pollution, 2024)

Regulating cobalt-nitrogen function centers via Cu incorporation enhances ciprofloxacin destruction through peroxymonosulfate activation - Qiulin Li; Jieling Huang; Lan Lin; Guangyin Fan (Environmental Pollution, 2024)

Novel dopamine-derived carbon modified fe-based metal–organic framework enhanced aptasensor rendering ultrasensitive electrochemical detection of oxytetracycline - Jialing Song; Xiaoxuan Fan; Liang Ying Ee; Xuanhao Lin; Dengsong Zhang; Sam Fong Yau Li; Manhong Huang (Chemical Engineering Journal, 2024)

Automated counting and classifying Daphnia magna using machine vision - Yang Ma; Wenping Xiao; Jinguo Wang; Xiang Kuang; Rongqin Mo; Yanfang He; Jianfeng Feng; Hengling Wei; Liwen Zheng; Yufei Li; Peixin Liu; Hao He; et al. (Aquatic Toxicology, 2024)

Nitrogen addition modulates adaptive responses of Chinese fir roots to phosphorus deficiency and promotes nutrient absorption efficiency - Yawen Lin; Haishu Chen; Fan Chen; Yiwen Zhang; Jing Liu; Mulualem Tigabu; Xiangqing Ma; Ming Li (New Forests, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Reconstructing high-resolution gridded precipitation data in the southwest China highland canyon area using an improved (MGWR) downscaling method - Lihong Wang; Yuechen Li; Yushi Gan; Long Zhao; Lei Fan; Wei Qin; Lin Ding (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

An unusual winter bloom of dinoflagellates with notable damage to kelp cultivation around Shandong peninsula, China - Hui-Xia Geng; Fan-Zhou Kong; Jin-Xiu Wang; Qing-Chun Zhang; Fang Li; Xin Hong; Min-Jie Song; Ziru Lian; Yu-Lin Cai; Ren-Cheng Yu (Marine Environmental Research, 2024)

Rainwater-borne H2O2 accelerates roxarsone degradation and reduces bioavailability of arsenic in paddy rice soils - Kaiqing Fan; Liji Chen; Huashou Li; Jun Wei Lim; Chuxia Lin; Junhao Qin; Rongliang Qiu (Journal of Hazardous Materials, 2024)

Genome sequencing analysis and validation of infestation-related functional genes of Vibrio parahaemolyticus LG2206 isolated from the hepatopancreas of diseased mud crab (Scylla paramamosain) in South China - Liu Guangxin; Liu Guangfeng; Li Ce; Ma Hongling; Deng Yiqin; Cheng Changhong; Jiang Jianjun; Fan Sigang; Feng Juan; Lin Li; Qin Zhendong; Guo Zhixun (Fish & Shellfish Immunology, 2024)

Inflammatory microenvironment-responsive “double-insurance” nanoreactors for accurate sonodynamic-chemodynamic therapy of rheumatoid arthritis - Sui Zhou; Meng-Wen Ma; Shao-Zhe Cai; Kai-Lin He; Lin-Fang Tan; Kai Cheng; Jin-Xuan Fan; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2024)

Multimodal enhancement of ferroptosis for synergistic cascade colorectal cancer therapy - Ziying Wu; Kun Chen; Weisheng Mo; Yue Wang; Xiewei Lin; Zhien Lan; Caijing Mo; Haocheng Wang; Xiaoying Li; Xingdi Fan; Hungchen Chen; Zhilin Shu; et al. (Chemical Engineering Journal, 2024)

A One-Nano MOF-Two-Functions Strategy Toward Self-healing, Anti-inflammatory, and Antibacterial Hydrogels for Infected Wound Repair - Ya-Ling Fan; Hong-Jie Liu; Zi-Li Wang; Zi-Lin Wang; Li-Li Zhu; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Construction of negative electrostatic sugared gourd pore within nickel-based metal-organic framework for one-step purification acetylene from ethylene and carbon dioxide mixture - Xing-Zhe Guo; Bing Lin; Guang-Zu Xiong; Rajamani Krishna; Zhao-Rong Zhang; Qing-Zan Liu; Zhi-Xiong Zhang; Liming Fan; Jie Zhang; Bingwen Li (Chemical Engineering Journal, 2024)

Concentration characteristics and emission estimates of major HCFCs and HFCs at three typical fluorochemical plants in China based on a Gaussian diffusion model - Zehua Liu; Jing Wu; Tengfei Ma; Minde An; Tong Ye; Xingchen Zhao; Mingzhu Li; Fan Wang; Mao Yuan; Dongmei Hu; Yueling Zhang; Lin Peng (Atmospheric Environment, 2024)

Observation of Low-Level Jets in the Eastern Tropical Indian Ocean Based on Shipborne Coherent Doppler Lidar - Haiyuan Wang; Lin Liu; Mengqi Fan; Yang Yang; Guang Yang; Yongliang Duan; Baochao Liu; Qinglei Su; Binbin Zhang; Fengjun Wang; Xuliang Shi; Qiuchi Li; et al. (Journal of Ocean University of China, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Silicon balance in an integrated multi-tropical aquaculture ecosystem, Sanggou Bay, China - Ruihuan Li; Zengjie Jiang; Fan Lin; Yitao Zhang; Weixin Wang; Kai Zhang; Weiwei Li; Dongjie Wan; Yazhou Shi (Frontiers in Marine Science, 2024)
Farmed aquaculture species play an important role in regulating nutrient cycles in farming systems. Compared with nitrogen and phosphorus, the role of farmed species in the silicon (Si) cycle remains poorly understood. To help reduce this uncertainty, we clarified the sources and sinks of silicate and quantified the Si pools in an aquaculture system in Sanggou Bay (SGB). The results showed that dissolved inorganic nutrient levels were significantly lower during the dry season than during the wet. Dissolved silicate (DSi) is a potential limiting factor for phytoplankton growth during spring, and phosphorus limitation occurs during summer. The budget results indicated that large amounts of nitrogen, phosphate (DIP), and DSi were buried in the sediment or transformed into other forms during both the wet and dry seasons. The nitrogen and DIP cycles were strongly influenced by bivalve excretion and farmed species harvesting; however, these processes had little impact on the Si cycle. Si availability depends on both external inputs and internal recycling. DSi was primarily supplied from the Yellow Sea, with a minor contribution from the river due to river discharge during spring. However, during summer, riverine inflow (accounting for 83% of the total influx) was the major DSi source followed by benthic flux (12%). Biogenic silica (BSi) burial efficiency in the sediment was estimated to be 78% during spring and 23% during summer. The BSi preservation efficiency in bivalves during spring was high (53%), leading to a higher Si retention than in river discharge. Bivalves biodeposition plays an important role in the Si burial process. We suggest that this high retention is essentially controlled by the biodeposition mechanism, which is directly controlled by the exotic suspension feeders. Bivalves have the potential to alter Si retention in the bay by producing large amounts of biodeposits and accelerating the silica cycle, which may lead to more carbon dioxide being absorbed by diatoms.

Hormetic responses to cadmium exposure in wheat seedlings: insights into morphological, physiological, and biochemical adaptations - Qiujuan Jiao; Gezi Li; Lantao Li; Di Lin; Zhengyang Xu; Lina Fan; Jingjing Zhang; Fengmin Shen; Shiliang Liu; Chandra Shekhar Seth; Haitao Liu (Environmental Science and Pollution Research, 2024)

Rheological Behavior and Microstructures in the Hybrid Gel of Scallop ( Patinopecten yessoensis ) Male Gonad Hydrolysates Modified by κ-Carrageenan and Methyl-β-Cyclodextrin - Wen Sun; Xiao-Fan Cui; Jia-Nan Yan; Xin-Yu Jiang; Lin Li; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Green remediation of mercury-contaminated soil using iron sulfide nanoparticles: Immobilization performance and mechanisms, effects on soil properties, and life cycle assessment - Dongjiao Lin; Guanzhao Hu; Hongbo Li; Fan Wu; Liang Li; Guiqin Yang; Li Zhuang; Yanyan Gong (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Long-term exposure to ionic liquid [C8mim]Br induces the potential risk of anxiety and memory deterioration through disturbing neurotransmitter systems - Huangyingzi Wang; Xuhua Li; Jun Li; Fan Yu; Qi Li; Mijia Qin; Lin Gui; Yajie Qian; Manhong Huang (NeuroToxicology, 2024)

Divergent rainfall infiltration patterns on the Chinese Loess Plateau between growing and non-growing seasons after long-term revegetation - Ruoxuan Li; Bihang Fan; Zhao Jin; Mingkui Hao; Hu Liu; Yaling Zhang; Yanjia Jiang; Hongyu Yao; Ke Lin; Li Guo (Journal of Hydrology, 2024)

Utilizing spontaneous plants for sustainable development in residential green spaces: Insights from environmental drivers and niche analysis in Fuzhou City, China - Chengyu Ran; Junyi Pan; Yuxin Lin; Tongyan Li; Yaling Huang; Jingkai Huang; Shiyuan Fan; Wenqiang Fang; Shuang Zhao; Yuxiang Liu; Jiali Jin; Weicong Fu (Journal of Environmental Management, 2024)

Transcriptomics to evaluate the influence mechanisms of ethanol on the ester production of Wickerhamomyces anomalus with the induction of lactic acid - Wenqin Cai; Yin Wan; Yanru Chen; Haowei Fan; Mengxiang Li; Shengwen Wu; Pei Lin; Tingting Zeng; Huibo Luo; Dan Huang; Guiming Fu (Food Microbiology, 2024)

Xanthohumol combined with chitosan-oxidized starch film as a potential new strategy for food packaging: Characterization, physicochemical and biological properties - Fan Yang; Siyuan Chang; Lin Zhao; Jing Han; Hao Li; Sen Zhang; Sheng Guo; Jinao Duan (Food Packaging and Shelf Life, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Organelle synergy unleashed: Modulating mitochondrial-endoplasmic reticulum contacts with a self-assembled prodrug amplifies ferroptosis for innovative cancer therapy - Junyan Zhuang; Renming Fan; Weike Liao; Ruizhuo Lin; Aohua Deng; Ting Zhao; Yongrui Hai; Heran Li; Lei Tang; Gaofei Wei (Chemical Engineering Journal, 2024)

Enhanced acidic hydrogen evolution reaction kinetics via nitrogen-doped iridium nanosheet with optimized hydrogen adsorption energy - Qianyu Lin; Yixian Liu; Jiacheng Li; Kun Feng; Jun Zhong; Hui Huang; Mingwang Shao; Zhenglong Fan; Fan Liao; Yang Liu; Zhenhui Kang (Chemical Engineering Journal, 2024)

OsSPL11 positively regulates grain size by activating the expression of GW5L in rice - Xinhai Zeng; Kai Fan; Yu Shi; Rui Chen; Wanyu Liu; Xin Wang; Guixiang Ye; Wenxiong Lin; Zhaowei Li (Plant Cell Reports, 2024)

Annexin-A1 tripeptide enhances functional recovery and mitigates brain damage in traumatic brain injury by inhibiting neuroinflammation and preventing ANXA1 nuclear translocation in mice - Kai Lin; Yuejiao Hou; Ruxin Li; Fengyan Fan; Yinan Hao; Yuan Wang; Yue Huang; Peng Li; Lingling Zhu; Xin Huang; Yong-Qi Zhao (Metabolic Brain Disease, 2024)

Hipposponols A and B, two new 9, 11-secosterols from the marine sponge Hippospongia lachne de Laubenfels - Ya-Fang Ding; Li-Yun Liu; Jie Tang; Dong-Xue Fan; Yuan-Yuan Ji; Hou-Wen Lin; Jie Wang; Li-Li Hong (Natural Product Research, 2024)

Corrigendum to “Unveiling the role of pore characteristics in sludge dewatering: Visualization by Nano-CT and micromodel study” [Water Research 252 (2024) 12191] - Yue Wang; Jiawei Li; Fan Feng; Caiyan Qu; Chongjian Tang; Qingwei Wang; Wenchao Zhang; Xu Yan; Zhang Lin (Water Research, 2024)

Glucoconjugated monoterpene indole alkaloids with xanthine oxidase inhibitory activity from Ophiorrhiza japonica - Bao-Bao Shi; Fan Xu; Guang-Ru Zhang; Yu He; Qing Liu; Meng-Lin Feng; Zheng-Hui Li; Ji-Kai Liu (Phytochemistry, 2024)

The dominant-substrate driven the enhanced performance in co-digestion of Pennisetum hybrid and livestock waste - Lintong Zhong; Fan Lin; Defang Wo; Xin Yang; Yongming Sun; Xidan Feng; Lianhua Li (Journal of Environmental Management, 2024)

Acidic electrolyzed-oxidizing water treatment mitigated the disease progression in Phomopsis longanae Chi-infected longans by modulating ROS and membrane lipid metabolism - Meiling Li; Hetong Lin; Chao Wang; Yazhen Chen; Mengshi Lin; Yen-Con Hung; Yifen Lin; Zhongqi Fan; Hui Wang; Yihui Chen (Food Chemistry, 2024)

ChRIPK1 caused necroptosis signaling pathway deficiency in Crassostrea hongkongensis - Yucheng Yang; Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; et al. (Fish & Shellfish Immunology, 2024)

Deciphering the formation of granules by n-DAMO and Anammox microorganisms - Zhi-Cheng Zhao; Ruo-Lin Li; Sheng-Qiang Fan; Yang Lu; Bing-Feng Liu; De-Feng Xing; Nan-Qi Ren; Guo-Jun Xie (Environmental Research, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

pH-responsive coacervate with adrenergic nerve blockade function inhibits triple-negative breast cancer metastasis by blocking nerve-tumor-immune loop - Jieting Chen; Chaoming Mei; Yan Tan; Fan Yang; Shirui Yang; Xin Wen; Xin Peng; Yong Lin; Dan Li (Chemical Engineering Journal, 2024)

A novel player of methylotrophic methanogensis pathway in boosting anaerobic digestion of corn stover with effluents recycling - Lianhua Li; Fan Lin; Yan He; Quanlin Zhao; Yao Yubo; Yongming Sun; Wen Luo; Haiwei Ren; Ying Guo (Chemical Engineering Journal, 2024)

Injectable photocrosslinkable acellular cartilage matrix hydrogel loaded with exosomes for promoting growth plate injury repair - Xinxin Si; Quan Zhang; Bo Ning; Lei Qiang; Qiang Li; Yihao Liu; Minjie Fan; Jing Shan; Guanlu Shen; Zichen Lin; Pengfei Zheng (Chemical Engineering Journal, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

Genome-wide CRISPR screening identifies critical role of phosphatase and tensin homologous (PTEN) in sensitivity of acute myeloid leukemia to chemotherapy - Liming Lin; Jingjing Tao; Ying Meng; Yichao Gan; Xin He; Shu Li; Jiawei Zhang; Feiqiong Gao; Dijia Xin; Luyao Wang; Yili Fan; Boxiao Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Correction: Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

Metabolic engineering of Saccharomyces cerevisiae for high-level production of (+)-ambrein from glucose - Chumin Lin; Xiaopeng Zhang; Zhongju Ji; Baolian Fan; Yaman Chen; Yuhong Wu; Yuhong Gan; Zhengping Li; Yi Shang; Lixin Duan; Feng Wang (Biotechnology Letters, 2024)

Glaesserella parasuis serotype 5 induces pyroptosis via the RIG-I/MAVS/NLRP3 pathway in swine tracheal epithelial cells - Yuhui Li; Mengru Guo; Qing Wang; Hong Zhou; Wenda Wu; Huixing Lin; Hongjie Fan (Veterinary Microbiology, 2024)

Association between ambient air pollution and dry eye symptoms among Chinese individuals during the COVID-19 pandemic: A national-based study - Jia-Yan Kai; Yi-Bo Wu; Xing-Xuan Dong; Yi-Fan Miao; Dan-Lin Li; Dan-Ning Hu; Carla Lanca; Andrzej Grzybowski; Chen-Wei Pan (Science of The Total Environment, 2024)

Multifaceted leaf litter traits shape soil fauna communities: Evidence from subtropical monocultural plantations - Dangjun Wang; Wuyang Xie; Xiaoyuan Lin; Fan Li; Chaochao Deng; Xiangyu Zeng; Kuo Tan; Yiping Yuan; Zhirong Gu; Mingxi Jiang; Zhun Mao; Juan Zuo (Forest Ecology and Management, 2024)

Platelet-Rich Plasma/Chitosan/Chondroitin sulfate immunomodulatory hydrogel Co-Networks for diabetic wound Repair: Functions and molecular mechanisms - Zi-Lin Wang; Lin-Yue Li; Hong-Jie Liu; Ya-Ling Fan; Yu-Xue Shen; Fei Song; Li-Li Zhu (Chemical Engineering Journal, 2024)

Geoarchaeological evidence of an ancient landslide dam (13–4.7 ka) and consequent outburst flood on the Minjiang River near Wenchuan, China - Niannian Fan; Xingguo Yang; Michael J. Storozum; Xuefeng Cheng; Lan Li; Weiming Liu; Zhipeng Lin; Xingnian Liu (CATENA, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Occurrence, seasonal variations, and fate of household and personal care chemicals in a wastewater treatment plant with Bacillus bioreactor process - Lin-Hui Zhang; Wen-Long Li; Zi-Feng Zhang; Xi-Ze Min; Ming-Gang Cai; Hang Xiao; Qing Diao; Zhen Qiu; Yi-Fan Li (Chemosphere, 2024)

Optimizing the rate of straw returning to balance trade-offs between carbon emission budget and rice yield in China - Ruo-Chen Li; Yu-Gang Tian; Fan Wang; Yuan-Feng Sun; Bai-Jian Lin; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang; Zhi-Yu Xu (Sustainable Production and Consumption, 2024)

The origins of odor (β-cyclocitral) under different water nutrient conditions: Algae or submerged plants? - Yu Lin; Chaoyue Cheng; Yutai Dai; Weijie Li; Jiping Chen; Mo Chen; Ping Xie; Qiang Gao; Xiaoyue Fan; Xuwei Deng (Science of The Total Environment, 2024)

Experimental investigation for the effect of bust pressure on hydrogen explosion venting - Yawei Lu; Rujia Fan; Zhirong Wang; Xingyan Cao; Yongjun Li; Chendi Lin; Zhuohua Yang (Fuel, 2024)

Stereo-selective cardiac toxicity induced by metconazole via oxidative stress and the wnt/β-catenin signaling pathway in zebrafish embryos - Lulu Liu; Fengzhong Wang; Zhong Zhang; Bei Fan; Ying Luo; Lin Li; Yifan Zhang; Zhihui Yan; Zhiqiang Kong; Frédéric Francis; Minmin Li (Environmental Pollution, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

High-performance antibacterial tight ultrafiltration membrane constructed by co-deposition of dopamine and tobramycin for sustainable high-salinity textile wastewater management - Wenyuan Ye; Fan Yu; Zijian Yu; Na Kong; Xiaoyan Lin; Riri Liu; Jiale Du; Xuan Huang; Ailiang Gu; Sotto Arcadio; Wenyi Zhang; Xuewei Li; et al. (Desalination, 2024)

Engineering of local electron properties optimization in single-atom catalysts enabling sustainable photocatalytic conversion of N2 into NH3 - Tianren Liu; Wensheng Zhang; Qingmei Tan; Weilong Lian; Haiting Lin; Jianshen Li; Dongxue Han; Yingying Fan; Dongdong Qin; Li Niu (Chemical Engineering Journal, 2024)

Continuous selenite biotransformation and biofuel production by marine diatom in the presence of fulvic acid - Hui-Ying Xu; Ruo-Yu Li; Zi-Qiang Yang; Jia-Fan Qiu; Yu-Bin Su; Carol Sze Ki Lin; Wei-Dong Yang; Hong-Ye Li; Jian-Wei Zheng; Xiang Wang (Bioresource Technology, 2024)

Impacts of open biomass burning in Southeast Asia on atmospheric PM2.5 concentrations over south China from 2009 to 2018 - Jie Li; Wenxuan Fan; Jian Wu; Zhiwei Han; Jiawei Li; Chuwei Zhang; Lin Liang (Atmospheric Environment, 2024)

An Updated Review on Self-Healing Barrier Materials with Potential Application in Contaminated Soil / Groundwater Risk Control - Fuhao Fan; Haibo Li; Ying Lin; Yang Liu; Wei Yu; Yingying Wu (Water, Air, & Soil Pollution, 2024)

Influence of Pore Structure Characteristics of Low Permeability Coal on Gas Nonlinear Seepage - Min Yan; Fan Yang; Binbin Zhang; Haifei Lin; Shugang Li (Natural Resources Research, 2024)

A Novel Bacillus amyloliquefaciens Specifically Improving the Solubility and Antioxidant Activities of Edible Bird’s Nest - Xin-Lin Li; Jian-Mei Lian; Xiao-Ling Chen; Qun-Yan Fan; Ying Yan; Feng-Jie Cui (Current Microbiology, 2024)

Temporal dynamics of rhizosphere bacterial community in the Robinia pseudoacacia–Mesorhizobium loti symbiotic system for remediation of cadmium-contaminated soils - Le Yang; Xing Ma; Jing Wang; Kang Zhang; Zhen Yang; Jiajia Li; Xinyi Liu; Pengyue Wu; Yanbing Lin; Zhouping Shangguan; Miaochun Fan (Applied Soil Ecology, 2024)

Responses of different agricultural structures to nitrogen loss and agricultural green development in Northwest China - Jiaxin Liu; Xiangwen Fan; Xiuyuan Li; Yupin Zheng; Yan Li; Caixian Cui; Zhaohai Bai; Lin Ma; Bingnian Zhai; Ziyan Li (Agriculture, Ecosystems & Environment, 2024)

Hypoxia-inducible factor 1α inhibits heat stress-induced pig intestinal epithelial cell apoptosis through eif2α/ATF4/CHOP signaling - Hui Li; Gang Zhang; Yongqing Liu; Fan Gao; Xinyue Ye; Rutao Lin; Ming Wen (Science of The Total Environment, 2024)

Functional characterization of terpene synthases SmTPS1 involved in floral scent formation in Salvia miltiorrhiza - Xiaohong Li; Lin Liu; Jin Chu; Guo Wei; Jiaxue Li; Xu Sun; Honghong Fan (Phytochemistry, 2024)

Aniline antioxidants in road dust, parking lot dust, and green-belt soil in Harbin, a megacity in China: Occurrence, profile, and seasonal variation - Ye Zhang; Jin-Nong Li; Jian-Xin Wang; Jie Hu; Jia-Lin Sun; Yi-Fan Li; Wen-Long Li; Zhong-Hua Tang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

Micro-structure change and crystal-structure modulated of oxygen carriers for chemical looping: Controlling local chemical environment of lattice oxygen - Da Song; Tao Long; Cuiqin Li; Yang Li; Mingyang Fan; Yonghao Lu; Yuchao Zhou; Haitao Chen; Yan Lin; Zhen Huang; Fang He (Fuel, 2024)

Synthesis and characterization of a host–guest complex based on acetylated-β-cyclodextrin and its application in improving the viscosity of supercritical carbon dioxide - Wei-An Huang; Rui Su; Jing-Wen Wang; Yu Fan; Lin Jiang; Xuan Li; Jie Cao (Fuel, 2024)

In vitro digestion mimicking conditions in adults and elderly reveals digestive characteristics of pork from different cooking ways - Xiangyue Cao; Fan Zhao; Ziyi Lin; Xiaomei Sun; Xianming Zeng; Haoxi Liu; Yutong Li; Zihang Yuan; Yuan Su; Chong Wang; Guanghong Zhou (Food Research International, 2024)

Revealing the role of λ-carrageenan on the enhancement of gel-related properties of acid-induced soy protein isolate/λ-carrageenan system - Dongling Qiao; Yuyan Zhang; Lisong Lin; Kexin Li; Fan Zhu; Genfa Wang; Gaolei Xi; Fatang Jiang; Binjia Zhang; Fengwei Xie (Food Hydrocolloids, 2024)

Washable and stable coaxial electrospinning fabric with superior electromagnetic interference shielding performance for multifunctional electronics - Shu-Ting Fan; Dong-Lin Guo; Ye-Tao Zhang; Tao Chen; Bang-Jing Li; Sheng Zhang (Chemical Engineering Journal, 2024)

Lowing surface steric hindrance of strongly-confined perovskite quantum dots enables efficient pure-red light-emitting diodes - Shixu Yang; Jing Li; Junfeng Wang; Lin Zhang; Linhan Fan; Xiong Chen; Fei Huang; Jianjun Tian (Chemical Engineering Journal, 2024)

Investigating the influence of platform design on the distribution of traffic particulate matter at the bus stop - Kaixuan Liu; Xinyuan Lin; Jiamin Xu; Fan Ma; Wenbin Yang; Ruhui Cao; Xisheng Hu; Yiqiang Wei; Li Jiang; Zhanyong Wang (Building and Environment, 2024)

Photochemical pollution during summertime in a coastal city of Southeast China: Ozone formation and influencing factors - Gaojie Chen; Xiaoting Ji; Jinsheng Chen; Lingling Xu; Baoye Hu; Ziyi Lin; Xiaolong Fan; Mengren Li; Youwei Hong; Jinfang Chen (Atmospheric Research, 2024)

High-fat diet impairs gut barrier through intestinal microbiota-derived reactive oxygen species - Nianyi Zeng; Fan Wu; Junqi Lu; Xiang Li; Shaomei Lin; Lang Zhou; Zhongwei Wang; Guangyan Wu; Qingfa Huang; Daowen Zheng; Jie Gao; Shan Wu; et al. (Science China Life Sciences, 2024)

Polygonum cillinerve polysaccharide inhibits transmissible gastroenteritis virus by regulating microRNA-181 - Xueqin Duan; Huicong Li; Xuewen Tan; Nishang Liu; Xingchen Wang; Weimin Zhang; Yingqiu Liu; Wuren Ma; Yi Wu; Lin Ma; Yunpeng Fan (The Veterinary Journal, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Isolation and absolute configuration of alkylpyridine alkaloids from the marine sponge Hippospongia lachne - Dong-Xue Fan; Xiang-Chao Luo; Ya-Fang Ding; Li-Yun Liu; Xin Wang; Jia-Yan Pan; Yuan-Yuan Ji; Jie Wang; Cui Li; Li-Li Hong; Hou-Wen Lin (Phytochemistry, 2024)

Mechanical properties and constitutive model of high-abundance methane hydrates containing clayey–silt sediments - Fan Yang; Changjun Li; Na Wei; Wenlong Jia; Jie He; Shuoshuo Song; Yuanrui Zhang; Youzhi Lin (Ocean Engineering, 2024)

Mapping multi-omics characteristics related to short-term PM2.5 trajectory and their impact on type 2 diabetes in middle-aged and elderly adults in Southern China - Jia-ting Wang; Wei Hu; Zhangzhi Xue; Xue Cai; Shi-yu Zhang; Fan-qin Li; Li-shan Lin; Hanzu Chen; Zelei Miao; Yue Xi; Tiannan Guo; Ju-Sheng Zheng; et al. (Journal of Hazardous Materials, 2024)

Sources appointment and health risks of PM2.5-bound trace elements in a coastal city of southeastern China - Ziyi Lin; Xiaolong Fan; Gaojie Chen; Youwei Hong; Mengren Li; Lingling Xu; Baoye Hu; Chen Yang; Yanting Chen; Zhiqian Shao; Jinsheng Chen (Journal of Environmental Sciences, 2024)

Absorption and utilization of polysaccharides from Cordyceps militaris fruiting bodies and their protective effects against CCl4-induced acute liver injury in mice - Lin Lan; Jingxin Wang; Hao Luo; Min Cao; Nianhong Guo; Guiling Fan; Shengyu Wang; Zaixing Sun; QiaoLing He; Yufeng Li (Food Bioscience, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Performance boosting by induction heating for hydrolysis of carbonyl sulfide using magnetic ordered mesoporous alumina as catalyst - Chao Huang; Yunchuan Hong; Binchen Wu; Hongchao Yu; Xiangqian Du; Min Pan; Weiyi Fan; Fei Gao; Feng Wu; Yixin Zhong; Lin Li; Guoshu Deng; et al. (Chemical Engineering Journal, 2024)

An overview on the life cycle of lithium iron phosphate: synthesis, modification, application, and recycling - Tianyu Zhao; Harshit Mahandra; Rajashekhar Marthi; Xiaobo Ji; Wenqing Zhao; Sujin Chae; Michael Traversy; Weilun Li; Fan Yu; Lin Li; Yeonuk Choi; Ahmad Ghahreman; et al. (Chemical Engineering Journal, 2024)

Chemically tailored molecular surface modification of bamboo pulp fibers for manipulating the electret performance of electret filter media - Chunxia Pang; Huanhuan You; Sijie Lei; Fan Su; Lili Liang; Zhanguo Li; Xiaoyan Lin; Yaping Zhang; Hao Zhang; Xunhai Pan; Yang Hu (Carbohydrate Polymers, 2024)

Unveiling vertical ozone variation with UAV-Based monitoring and modeling: A new challenge for city-level ozone pollution control in the pearl river delta region - Haoxiang Xu; Ying Li; Changqing Lin; Zhi Ning; Chanfang Liu; Boru Mai; Xuejiao Deng; Shidong Fan; Jinlan Li (Atmospheric Environment, 2024)

A Pollution Barrier Self-Healing Material: Investigating the Effect of Individual Components on Its Performance and Determining Optimal Ratios and Healing Compositions - Fuhao Fan; Haibo Li; Liuyu Song; Ying Lin; Xiaofei Qin; Yang Liu; Sihan Li; Wei Yu; Yingying Wu (Water, Air, & Soil Pollution, 2024)

Environmental exposure to per- and polyfluoroalkyl substances mixture and asthma in adolescents - Yi-Fan Wang; Li Li; Xu Wang; Ya-Nan Yun; Xue-Lin Wang; En-Yang He; Ming-Kun Song; Xue-Hong Xia; Ying-Xue Zou (International Archives of Occupational and Environmental Health, 2024)

Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Bisphenol A Regulates the TNFR1 Pathway and Excessive ROS Mediated by miR-26a-5p/ADAM17 Axis to Aggravate Selenium Deficiency-Induced Necroptosis in Broiler Veins - Xue Fan; Yixuan Wang; Jintao Zhang; Hongjin Lin; Zhikun Bai; Shu Li (Biological Trace Element Research, 2024)

Will the Globe Encounter the Warmest Winter after the Hottest Summer in 2023? - Fei Zheng; Shuai Hu; Jiehua Ma; Lin Wang; Kexin Li; Bo Wu; Qing Bao; Jingbei Peng; Chaofan Li; Haifeng Zong; Yao Yao; Baoqiang Tian; et al. (Advances in Atmospheric Sciences, 2024)

Structural characteristics and tectonic division of the Zambezi Delta basin in the offshore East Africa: evidences from gravity and seismic data - Guozhang Fan; Wen Li; Liangbo Ding; Wanyin Wang; Hongping Wang; Dingding Wang; Lin Li; Hao Wang; Chaofeng Wang; Qingluan Wang; Ying Zhang (Acta Oceanologica Sinica, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Investigations of the Formation Mechanism and Pressure Pulsation Characteristics of Pipeline Gas-Liquid Slug Flows - Gaoan Zheng; Pu Xu; Lin Li; Xinghua Fan (Journal of Marine Science and Engineering, 2024)
The pipeline system is widely used in marine engineering, and the formation mechanism and flow patterns of two-phase slug flows are of great significance for the optimal design of and vibration prevention in a complex pipeline system. Aiming at the above problems, this paper proposes a modeling and solving method for gas-liquid slug flows. First, a VOF-PLIC-based coupling gas-liquid slug flow transport model is conducted. Second, to reduce the fuzzy boundary between the gas-liquid coupling interfaces, an artificial compression term is added to the transport equations, and the formation and evolution mechanism of severe slugging flow in piping systems is investigated. The pressure pulsation and gas content characteristics of the gas-liquid coupling process are explored. Research results found that the slugging phenomenon occurs at the gas-liquid interface, where liquid slugging frequency reaches its peak. The pipeline system has prominent periodic characteristics of the slugging phenomenon, and the period decreases when the gas-phase converted speed rises; pressure fluctuation amplitude increases, and the gas-phase velocity change is the inducing factor for the drastic change of pressure fluctuation. The research results can offer theoretical references for optimal designs of and vibration prevention in marine pipeline systems.

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Unveiling the role of pore characteristics in sludge dewatering: Visualization by Nano-CT and micromodel study - Yue Wang; Jiawei Li; Fan Feng; Caiyan Qu; Chongjian Tang; Qingwei Wang; Wenchao Zhang; Xu Yan; Zhang Lin (Water Research, 2024)

MicroRNA-194-5p/Heparin-binding EGF-like growth factor signaling mediates dexamethasone-induced activation of pseudorabies virus in rat pheochromocytoma cells - Chen Zhang; Yuxuan Liu; Fan Yang; Yifan Liu; Naixiu Wang; Yuhang Li; Yanqing Liu; Zhiyun Qiu; Lin Zhang; Xiaoyan You; Ling Gan (Veterinary Microbiology, 2024)

Meteorological impacts on the unexpected ozone pollution in coastal cities of China during the unprecedented hot summer of 2022 - Xiaoting Ji; Gaojie Chen; Jinsheng Chen; Lingling Xu; Ziyi Lin; Keran Zhang; Xiaolong Fan; Mengren Li; Fuwang Zhang; Hong Wang; Zhi Huang; Youwei Hong (Science of The Total Environment, 2024)

Mirror QCD phase transition as the origin of the nanohertz Stochastic Gravitational-Wave Background - Lei Zu; Chi Zhang; Yao-Yu Li; Yuchao Gu; Yue-Lin Sming Tsai; Yi-Zhong Fan (Science Bulletin, 2024)

Ornidazole degradation by PMS activated by Co-Zr-TiO2 with abundant oxygen vacancies: Performance, mechanism and degradation pathway - Xiaofei Qin; Haibo Li; Kaixuan Wang; Yang Liu; Liuyu Song; Ying Lin; Fuhao Fan; Sihan Li; Ting Ma (Process Safety and Environmental Protection, 2024)

FvDFR2 rather than FvDFR1 play key roles for anthocyanin synthesis in strawberry petioles - Xinyu Li; Xi Luo; Zhongchi Liu; Chong Wang; Anqi Lin; Kun Xiao; Minghao Cao; Junmiao Fan; Hongli Lian; Pengbo Xu (Plant Science, 2024)

Significance of phosphate adsorbed on the cellular surface as a storage pool and its regulation in marine microalgae - Xian-Yang Zhang; Zhuo-Fan Li; Hai-Feng Gu; Ai-Qin Han; Feng-Xian Han; Lin-Jian Ou (Marine Environmental Research, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Effect of EDDS on the rhizosphere ecology and microbial regulation of the Cd-Cr contaminated soil remediation using king grass combined with Piriformospora indica - Haixiang Zhang; Kailu Zhang; Yali Duan; Xiaoyan Sun; Li Lin; Qianli An; Muhammad Mohsin Altaf; Zhiqiang Zhu; Fan Liu; Yangqiu Jiao; Jing Yin; Can Xie; et al. (Journal of Hazardous Materials, 2024)

Cathepsin B degrades RbcL during freezing-induced programmed cell death in Arabidopsis - Gang Yang; Tao Chen; Ting-ting Fan; Xiang-yu Lin; Yu-qiong Cui; Wei-chao Dong; Li-zhe An; Hua Zhang (Plant Cell Reports, 2024)

Mining subsidence monitoring using distributed scatterers InSAR based on Goldstein filter and Fisher information matrix-weighted optimization - Zeming Tian; Lifeng Zhao; Hongdong Fan; Tao Lin; Tao Li (Natural Hazards, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Membrane lipid remodeling and autophagy to cope with phosphorus deficiency in the dinoflagellate Prorocentrum shikokuense - Da-Wei Li; Jin-Zhou Tan; Zhuo-Fan Li; Lin-Jian Ou (Chemosphere, 2024)

Stereoselective cardiotoxic effects of metconazole on zebrafish (Danio rerio) based on AGE-RAGE signalling pathway - Minmin Li; Lin Yang; Rui Wang; Lin Li; Yifan Zhang; Long Li; Nuo Jin; Yatao Huang; Zhiqiang Kong; Frédéric Francis; Bei Fan; Fengzhong Wang (Science of The Total Environment, 2024)

Screening of cadmium-chromium-tolerant strains and synergistic remediation of heavy metal-contaminated soil using king grass combined with highly efficient microbial strains - Fan Liu; Kailu Zhang; Yang Zhao; Dong Li; Xiaoyan Sun; Li Lin; Huiping Feng; Qing Huang; Zhiqiang Zhu (Science of The Total Environment, 2024)

Impacts of climate change and human activity on the potential distribution of Aconitum leucostomum in China - Li Xu; Yuan Fan; Jianghua Zheng; Jingyun Guan; Jun Lin; Jianguo Wu; Liang Liu; Rui Wu; Yujia Liu (Science of The Total Environment, 2024)

The CropGPT project: Call for a global, coordinated effort in precision design breeding driven by AI using biological big data - Wanchao Zhu; Rui Han; Xiaoyang Shang; Tao Zhou; Chengyong Liang; Xiaomeng Qin; Hong Chen; Zaiwen Feng; Hongwei Zhang; Xingming Fan; Weifu Li; Lin Li (Molecular Plant, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Bacteriocinogenic Lacticaseibacillus paracasei strains from Inner Mongolian fermented milk efficiently control pathogenic bacteria in model cheddar-like cheese - Zhuo Chen; Xiuqi Jiang; Lin Li; Dengyi Liu; Fan Zhao; Yuanfa Liu; Shan Wu; Xin Lü; Gang Wu; Yanglei Yi (Food Bioscience, 2024)

Structural engineering of rare earth metal-organic frameworks derivatives with high anisotropy for high-efficiency electromagnetic wave absorption - Lutong Li; Jiurong Liu; Fei Pan; Jing Qiao; Xue Zhang; Jingpeng Lin; Wei Liu; Qilei Wu; Shifei Tao; Fan Wu; Zhihui Zeng (Chemical Engineering Journal, 2024)

Diagenetic effects on strontium isotopes in shallow-water carbonate sediments from Middle Miocene to Recent - Xinran Chen; Mengchun Cao; Thomas J. Algeo; Na Li; Guang-yi Wei; Yi-bo Lin; Hua Zhang; Lei Xiang; Youhua Zhu; Changgui Xu; Caiwei Fan; Shuzhong Shen; et al. (Chemical Geology, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Interactive effects of dietary leucine and isoleucine affect amino acid profile and metabolism through AKT/TOR signaling pathways in blunt snout bream (Megalobrama amblycephala) - Mang-mang Wang; Yang-yang Huang; Wen-bin Liu; Kang Xiao; Xi Wang; Hui-xing Guo; Yi-lin Zhang; Jing-Wei Fan; Xiang-fei Li; Guang-zhen Jiang (Fish Physiology and Biochemistry, 2024)

Corrigendum to “Leaf hydraulic distance is a good predictor of growth within and across conifer species in a Taiga ecosystem” [AgriculturalandForestMeteorology342(2023)109710] - Xingyue Li; Dayong Fan; Zhengxiao Liu; Zengjuan Fu; Changqing Gan; Zeyu Lin; Chengyang Xu; Han Sun; Xiangping Wang (Agricultural and Forest Meteorology, 2024)

Design and analysis of an electro-adhesive hexapod robot with convertible limbs in microgravity - Ao Xiang; Lin Zhang; Li Fan (Advances in Space Research, 2024)

Positive impacts of dietary prebiotic inulin on growth performance, antioxidant capacity, immunity, and intestinal microbiota of red swamp crayfish (Procambarus clarkii) - Qian Wang; Yanbin Lin; Heng Zhang; Wenhao Fan; Shengxuan Li; Guoliang Ruan; Liu Fang (Aquaculture International, 2024)

Genetic Diversity and Population Structure of Chinese Longsnout Catfish (Leiocassis longirostris) Using Microsatellite DNA Markers - Yanling Hou; Huan Ye; Xinhua Song; Jiahui Fan; Junyi Li; Jian Shao; Yizhou Wang; Danqing Lin; Huamei Yue; Rui Ruan; Chuangju Li (Fishes, 2024)
The Chinese longsnout catfish (Leiocassis longirostris) is an economically important freshwater fish in China; however, its wild resources have declined dramatically in recent decades. Understanding the genetic structure of Chinese longsnout catfish populations is crucial to guide breeding programs and fishy restoration. In this study, 15 highly polymorphic microsatellite DNA loci were used to evaluate its genetic diversity and population structure. Chinese longsnout catfish populations show high genetic diversity; they do not show significant genetic differentiation or systematic geographic pattern of variation. From the upper to the lower reaches of the Yangtze River, the genetic diversity of Chinese longsnout catfish populations showed an increasing trend. The Gezhouba and Three Gorges dams, which physically divide the Yangtze River into upstream and mid-downstream sections, did not contribute to the genetic differentiation of Chinese longsnout catfish populations. Hence, the source of broodstock is not critical for within-river breeding programs and stock enhancement to restore the wild population. In addition, possible effects of dams on differentiation among populations are crucial and long-term evaluation is essential.

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

Porcine circovirus type 2 and Glaesserella parasuis serotype 4 co-infection activates Snail1 to disrupt the intercellular junctions and facilitate bacteria translocation across the tracheal epithelium - Mengru Guo; Jianan Zhang; Qing Wang; Jinsheng Tang; Yuhui Li; Hong Zhou; Huixing Lin; Zhe Ma; Hongjie Fan (Veterinary Microbiology, 2024)

Selenomethionine protects the liver from dietary deoxynivalenol exposure via Nrf2/PPARγ-GPX4-ferroptosis pathway in mice - Shijie Fan; Luxi Lin; Pingyang Li; Huihui Tian; Jialu Shen; Longzhu Zhou; Qingyu Zhao; Junmin Zhang; Yuchang Qin; Chaohua Tang (Toxicology, 2024)

CFD- and BPNN- based investigation and prediction of air pollutant dispersion in urban environment - Xisheng Lin; Yunfei Fu; Daniel Z. Peng; Chun-Ho Liu; Mengyuan Chu; Zengshun Chen; Fan Yang; Tim K.T. Tse; Cruz Y. Li; Xinxin Feng (Sustainable Cities and Society, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

Use of a new Tibetan Plateau network for permafrost to characterize satellite-based products errors: An application to soil moisture and freeze/thaw - Jingyao Zheng; Tianjie Zhao; Haishen Lü; Defu Zou; Nemesio Rodriguez-Fernandez; Arnaud Mialon; Philippe Richaume; Jianshe Xiao; Jun Ma; Lei Fan; Peilin Song; Yonghua Zhu; et al. (Remote Sensing of Environment, 2024)

The role of energy transport system in pericarp browning of harvested longan fruit - Meiling Li; Hetong Lin; Yazhen Chen; Yihui Chen; Yifen Lin; Zhongqi Fan; Hui Wang (Postharvest Biology and Technology, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Garnet geochemistry reveals late-stage oxidation of tin-bearing fractionated granite - Jin-Xiang Li; Lin Ding; Noreen J. Evans; Fang Xu; Wei-Ming Fan; Li-Yun Zhang; Fu-Long Cai; Qiu-Yun Guan; Ya-Hui Yue; Jing Xie (Lithos, 2024)

A clean method for gallium recovery and the coproduction of silica-potassium compound fertilizer and zeolite F from brown corundum fly ash - Gangan Wang; Chaoyi Chen; Junqi Li; Fan Yang; Linzhu Wang; Xin Lin; Hao Wu; Jun Zhang (Journal of Hazardous Materials, 2024)

Synthesis of gel crosslinked composite material from spent cathode carbon blocks and its application in modified asphalt binders - Xinyu Li; Denghui Ren; Shencheng Fan; Zibo Lin; Fanyu Meng; Haisheng Wu; Fang Lai; Jing Li (Journal of Cleaner Production, 2024)

Indoor air quality of urban public transportation stations in China: Based on air quality evaluation indexes - Lin Fan; Xu Han; Li Li; Hang Liu; Tanxi Ge; Xinqi Wang; Qin Wang; Hang Du; Liqin Su; Xiaoyuan Yao; Xianliang Wang (Journal of Environmental Management, 2024)

The use of urea hydrogen peroxide as an alternative N-fertilizer to reduce accumulation of arsenic in rice grains - Zhenni Peng; Chuxia Lin; Kaiqing Fan; Jidong Ying; Huashou Li; Junhao Qin; Rongliang Qiu (Journal of Environmental Management, 2024)

Regional complex system simulation optimization through linking governance and environment performance: A case study of water environmental carrying capacity based on the SDES model - An Huang; Li Tian; Yongfu Li; Binyu Xiong; Jianghao Yu; Yuan Gao; Qing Li; Chenjing Fan; Linxiner Liu; Xuejun Duan; Chen Lin (Environmental Impact Assessment Review, 2024)

Effects of salinity in food waste on the growth of black soldier fly larvae and global warming potential analysis - Rui Li; TianHui Lin; XiaoLei Fan; XiaoFeng Dai; JieHua Huang; YiFeng Zhang; RongBo Guo; ShanFei Fu (Chemical Engineering Journal, 2024)

Investigation and optimization of outdoor thermal comfort in elementary school campuses: Example from a humid-hot area in China - Tongye Guo; Zhaoxia Lin; Yang Zhao; Zhaosong Fang; Yini Fan; Xiang Zhang; Jiahao Yang; Yuankui Li (Building and Environment, 2024)

Matrine Mediated Immune Protection in MS by Regulating Gut Microbiota and Production of SCFAs - Mengmeng Dou; Yaojuan Chu; Xueliang Zhou; Mengru Wang; Xinyu Li; Rui Ma; Zhirui Fan; Xiaoyu Zhao; Wenbin Wang; Silu Li; Ying Lv; Lin Zhu (Molecular Neurobiology, 2024)

Observation of Arctic surface currents using data from a surface drifting buoy - Hongxia Chen; Lina Lin; Long Fan; Wangxiao Yang; Yinke Dou; Bingrui Li; Yan He; Bin Kong; Guangyu Zuo; Na Liu (Acta Oceanologica Sinica, 2024)

Investigations of the Mass Transfer and Flow Field Disturbance Regulation of the Gas–Liquid–Solid Flow of Hydropower Stations - Qing Yan; Xinghua Fan; Lin Li; Gaoan Zheng (Journal of Marine Science and Engineering, 2023)
With the continuous depletion of fossil fuels, all countries attach importance to clean and sustainable development. The real-time state monitoring of multiphase flows is vital for enhancing hydropower station energy conversion. However, the material mass transfer mechanism and flow field disturbance regulation strategy faces significant challenges. To solve these problems, a computational fluid mechanics and discrete element method (CFD-DEM) coupling modeling and solution method based on a particle porosity model was proposed, and the mass transfer mechanism of gas–liquid–solid mixing flows was obtained under dynamic whirl intensity regulations. Combined with the user-defined function (UDF), the interphase forces and void ratios of fluids and particles were calculated to obtain the material mass transfer laws under dynamic disturbance regulations. The evolution characteristics of the particle flow pattern were tracked during the material mixing process. The results show that the mixed flow field had a high material transport efficiency under intensive whirl regulation, especially for the particle aggregation in the center of the reaction vessel. The maximum peak velocity and energy values of the particle transport process were 3.30 m/s and 0.27 × 10−3 m2·s−2. The higher whirl regulation improved the material transport process and conveying efficiency and enhanced the particle mixing effect in the reaction space. Relevant research results can provide theoretical references for material mass transfer mechanisms, dynamic regulation strategies, and particle flow pattern identifications and can also provide technical support for hydropower energy conversion.

Association of glyphosate exposure with multiple adverse outcomes and potential mediators - Wenxiang Li; Daizai Lei; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yunru Lin; Fan Xu; Yuan-jun Qin (Chemosphere, 2023)

Benefits, potential and risks of China's grassland ecosystem conservation and restoration - Jiahui Li; Lin Huang; Wei Cao; Jian Wang; Jiangwen Fan; Xinliang Xu; Haijing Tian (Science of The Total Environment, 2023)

Short-term mediating effects of PM2.5 on climate-associated COPD severity - Huan Minh Tran; Yuan-Chien Lin; Feng-Jen Tsai; Kang-Yun Lee; Jer-Hwa Chang; Chi-Li Chung; Kian Fan Chung; Kai-Jen Chuang; Hsiao-Chi Chuang (Science of The Total Environment, 2023)

Exploring the potential of magnetic persimmon tannins-based bio-adsorbent for Cd (II) ions removal from water: Experiment and DFT study - Fan Zhou; Lin Gao; Shunyan Cui; Jing Tian; Tong Wang; Guiyin Li; Zhongmin Wang; Chaoke Qin; Dahong Lin; Weijiang Gan; Zhaojin Ran (Journal of Water Process Engineering, 2023)

N-doped porous carbon material derived by MOFs calcined in proper oxygen atmosphere as high-performance catalyst for the low-temperature NH3-SCR - Jiexuan Zhu; Donghai Mo; Lin Tao; Jinfeng Li; Shiying Fu; Lihui Dong; Bin Li; Zhengjun Chen; Minguang Fan (Journal of Environmental Chemical Engineering, 2023)

Discovery of the large-scale Eocene Xiwu Pb–Zn–Ag deposit in the Tethyan Himalaya: Geochronology, geochemistry, and C–H–O–S–Pb–Sr–Nd isotopes - Hua-Wen Cao; Qiu-Ming Pei; Xiao Yu; M. Santosh; Guang-Ming Li; Lin-Kui Zhang; Hao Zou; Lei Dong; Ke Gao; Zuo-Wen Dai; Jin-Biao Ai; Shuang-Shuang Lan; et al. (Gondwana Research, 2023)

Multifunctional graphene/Ag hydrogel with antimicrobial and catalytic properties for efficient solar-driven desalination and wastewater purification - Lin Lin; Wenrui Wang; Danyi Li; Siyi Xu; Ying Sun; Linfan Li; Kai Fan; Chenyang Xing; Lan Zhang; Jihao Li (Chemical Engineering Journal, 2023)

Fe-single-atom catalyst nanocages linked by bacterial cellulose-derived carbon nanofiber aerogel for Li-S batteries - Xueyan Lin; Wenyue Li; Vy Nguyen; Shu Wang; Shize Yang; Lu Ma; Yonghua Du; Bin Wang; Zhaoyang Fan (Chemical Engineering Journal, 2023)

STAT6 promoting oxalate crystal deposition-induced renal fibrosis by mediating macrophage-to-myofibroblast transition via inhibiting fatty acid oxidation - Tianhui Yuan; Yuqi Xia; Shengyu Pan; Bojun Li; Zehua Ye; Xinzhou Yan; Weimin Hu; Lei Li; Baofeng Song; Weimin Yu; Haoyong Li; Ting Rao; et al. (Inflammation Research, 2023)

Multifunctional regulation of NADPH oxidase in growth, microsclerotia formation and virulence in Metarhizium rileyi - Liqin Fan; Bingjie Li; Jiahui Wang; Xinxin Li; Feilong Ma; Fang Du; Hongli Li; Yunlong Lin (Biotechnology Letters, 2023)

Novel amino-modified bamboo-derived biochar-supported nano-zero-valent iron (AMBBC-nZVI) composite for efficient Cr(VI) removal from aqueous solution - Xiaobin Zhou; Yingxue Wang; Huili Liu; Yanan Zhang; Yinming Fan; Shengpeng Mo; Huaxia Li; Junyi Wang; Hua Lin (Environmental Science and Pollution Research, 2023)

Removal of Microcystis aeruginosa by manganese activated sodium percarbonate: Performance and role of the in-situ formed MnO2 - Nan Li; Fan Chen; Shunkai Xu; Shumin Zhu; Lingjun Bu; Lin Deng; Zhou Shi; Shiqing Zhou (Chemosphere, 2023)

Photochemistry in the urban agglomeration along the coastline of southeastern China: Pollution mechanism and control implication - Gaojie Chen; Qiao Shi; Lingling Xu; Shaocai Yu; Ziyi Lin; Xiaoting Ji; Xiaolong Fan; Youwei Hong; Mengren Li; Fuwang Zhang; Jinfang Chen; Jinsheng Chen (Science of The Total Environment, 2023)

Development of a duplex PCR for the simultaneous detection of EHP and IHHNV and analysis of the correlation between these two pathogens - Yang Gao; Cai-Yi Chen; Zheng Cao; Ru-Qing Yuan; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan; Fan Li (Journal of Invertebrate Pathology, 2023)

Long-term PM2.5 concentration prediction based on improved empirical mode decomposition and deep neural network combined with noise reduction auto-encoder- A case study in Beijing - Mengfan Teng; Siwei Li; Jie Yang; Shuo Wang; Chunying Fan; Yu Ding; Jiaxin Dong; Hao Lin; Shansi Wang (Journal of Cleaner Production, 2023)

Stability evaluation of salt cavern hydrogen storage and optimization of operating parameters under high frequency injection production - De-Peng Li; Wei Liu; Pan Fu; Lin Li; Fan-Sheng Ban; Qi-Hang Li; Jin-Yang Fan; De-Yi Jiang; Zhi-Xin Zhang (Gas Science and Engineering, 2023)

The metabolism of membrane lipid participates in the occurrence of chilling injury in cold-stored banana fruit - Qian Li; Han Lin; He-tong Lin; Meng-shi Lin; Hui Wang; Wei Wei; Jian-ye Chen; Wang-jin Lu; Xing-feng Shao; Zhong-qi Fan (Food Research International, 2023)

Tea polyphenols coated sodium alginate-gelatin 3D edible scaffold for cultured meat - Xiaohong Chen; Linzi Li; Lin Chen; Wei Shao; Yan Chen; Xiaojing Fan; Yaping Liu; Changbo Tang; Shijie Ding; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

A novel approach for predicting the concentration of exhaled aerosols exposure among healthcare workers in the operating room - Zhijian Liu; Zhenzhe Huang; Jiaqi Chu; Haochuan Li; Junzhou He; Chaofan Lin; Chuan Jiang; Guangpeng Yao; Shuanghuai Fan (Building and Environment, 2023)

Differences in the chemical compositions and formation mechanisms of PM2.5 between urban and rural areas in Xinxiang, Central China around the Beijing Winter Olympics - Guangqi Wang; Meiyuan Wang; Leitao Sun; Wenpeng Zhao; Lin Ma; Hongliang Li; Haomin Huang; Liya Fan; Daiqi Ye (Atmospheric Environment, 2023)

Leaf hydraulic distance is a good predictor of growth response to climate aridity within and across conifer species in a Taiga ecosystem - Xingyue Li; Dayong Fan; Zhengxiao Liu; Zengjuan Fu; Changqing Gan; Zeyu Lin; Chengyang Xu; Han Sun; Xiangping Wang (Agricultural and Forest Meteorology, 2023)

Paternal lipopolysaccharide exposure induced intrauterine growth restriction via the inactivation of placental MEST/PI3K/AKT pathway in mice - Pei-Ying Jiang; Shuai Lin; Jie-Ru Liu; Yan Liu; Li-Ming Zheng; Qiang Hong; Yi-Jun Fan; De-Xiang Xu; Yuan-Hua Chen (Archives of Toxicology, 2023)

Effects of heavy metal exposure on hypertension: A machine learning modeling approach - Wenxiang Li; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yuanjun Qin; Yunru Lin; Fan Xu; Daizai Lei (Chemosphere, 2023)

Identification of a novel crustacean vascular endothelial growth factor b-like in the mud crab Scylla paramamosain, and examination of its role in lipid accumulation - Wenjie Zhong; Chuangsi Chen; Senyue Tan; Xianda He; Shuqi Wang; Douglas R. Tocher; Fan Lin; Zhijie Sun; Xiaobo Wen; Yuanyou Li; Khor Waiho; Xugan Wu; et al. (Aquaculture, 2023)

Efficacy of a porcine reproductive and respiratory syndrome virus 1 (PRRSV-1) natural recombinant against a heterologous PRRSV-1 isolate both clustered within the subgroup of BJEU06-1-like isolates - Chen Li; Shuai Li; Shubin Li; Ming Qiu; Hong Lin; Zhe Sun; Yuejia Qiu; Wenhao Qi; Binghui Feng; Jixiang Li; Wanglong Zheng; Xiuling Yu; et al. (Veterinary Microbiology, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Assessment of 9 km SMAP soil moisture: Evidence of narrowing the gap between satellite retrievals and model-based reanalysis - Zanpin Xing; Xiaojun Li; Lei Fan; Andreas Colliander; Frédéric Frappart; Patricia de Rosnay; Roberto Fernandez-Moran; Xiangzhuo Liu; Huan Wang; Lin Zhao; Jean-Pierre Wigneron (Remote Sensing of Environment, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

A new model to accurately measure the radon exhalation rate from soil using AlphaGUARD - Shuaibin Liu; Tao Hu; Fen Lin; Zhongkai Fan; Ruomei Xie; Shuai Yuan; Jiulin Wu; Haibo Yi; Yixiang Mo; Jiale Sun; Linquan Chen; Huiying Li; et al. (Journal of Environmental Radioactivity, 2023)

Effect of different agricultural conditions, practices, and processing on levels of total arsenic and species in cereals and vegetables: A review - Yanfang Liu; Yatao Huang; Lin Li; Yangyang Xiong; Litao Tong; Fengzhong Wang; Bei Fan; Jiashun Gong (Food Control, 2023)

Damage detection of bridges subjected to moving load based on domain-adversarial neural network considering measurement and model error - Zhi-Dong Li; Wen-Yu He; Wei-Xin Ren; Yi-Lin Li; Yi-Fan Li; Hua-Cai Cheng (Engineering Structures, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Insight into the selective oxidation behavior of organic pollutants via Ni-N4-C mediated electron transfer pathway - Huchuan Yan; Cui Lai; Shiyu Liu; Dongbo Wang; Xuerong Zhou; Mingming Zhang; Ling Li; Dengsheng Ma; Fuhang Xu; Xiuqin Huo; Lin Tang; Ming Yan; et al. (Chemical Engineering Journal, 2023)

Different B Mo isotopic fractionation processes controlled by redox conditions in the subduction zone - Yang Yu; Xiao-Long Huang; Yu-Ming Lai; Jie Li; Yi-Gang Xu; Sun-Lin Chung; Iwan Setiawan; Fan Yang (Chemical Geology, 2023)

Rhizosphere microbiome assembly mediated by consecutive monoculture triggers the replant disease of Rehmannia glutinosa - Qian Li; Sisi Cai; Yuan Fang; Muhammad Umar Khan; Bianhong Zhang; Xuzhong Duan; Shutong Fan; Cuihong Lu; Mingjie Li; Li Gu; Juanying Wang; Jun Xiong; et al. (Applied Soil Ecology, 2023)

DJ-1-mediated p62 degradation delays intervertebral disc degeneration by inhibiting apoptosis of nucleus pulposus cells - Jialiang Lin; Xuanqi Zheng; Zhencheng Xiong; Qian Xiang; Yongzhao Zhao; Shuai Jiang; Zhuoran Sun; Dongwei Fan; Chuiguo Sun; Weishi Li (Apoptosis, 2023)

Tigliane-and daphnane-type diterpenoids from the buds of Daphne genkwa with their cytotoxic activities - Ying Chen; Cai-Lin Zhao; Wei Dong; Fei-Fan Song; Li-Na Guo; Hong-Lian Zhang; Lv Zhen; Li Li; Jin Ye; Bo Song (Natural Product Research, 2023)

Association between co-exposure to phenols, phthalates, and polycyclic aromatic hydrocarbons with the risk of frailty - Wenxiang Li; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yuanjun Qin; Yunru Lin; Fan Xu; Daizai Lei (Environmental Science and Pollution Research, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

The effect of nitrous acid (HONO) on ozone formation during pollution episodes in southeastern China: Results from model improvement and mechanism insights - Baoye Hu; Gaojie Chen; Jinsheng Chen; Lingling Xu; Xiaolong Fan; Youwei Hong; Mengren Li; Ziyi Lin; Mingqiang Huang; Fuwang Zhang; Hong Wang (Science of The Total Environment, 2023)

Response of rare and abundant rhizosphere microbial communities to inoculated rhizobium in cadmium-contaminated soil phytoremediation - Le Yang; Zhen Yang; Xing Ma; Jing Wang; Jiajia Li; Yanbing Lin; Miaochun Fan; Zhouping Shangguan (Rhizosphere, 2023)

Diesel exhaust particles exposure induces liver dysfunction: Exploring predictive potential of human circulating microRNAs signature relevant to liver injury risk - Lin Xu; Yanting Li; Wanli Ma; Xueying Sun; Rongrong Fan; Yuan Jin; Ningning Chen; Xiaoxiao Zhu; Huan Guo; Kunming Zhao; Jiao Luo; Chuanhai Li; et al. (Journal of Hazardous Materials, 2023)

Adsorption of Pd(II) ions by electrospun fibers with effective adsorption sites constructed by N, O atoms with a particular spatial configuration: Mechanism and practical applications - Min Li; Mingyue Wang; Lin Zhang; Yuzhu Fan; Liang Xu; Zhiyuan Ma; Zhidong Wen; Haichao Wang; Nianshou Cheng (Journal of Hazardous Materials, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

Satellite evidence for small biophysical effects of transport infrastructure in the Qinghai-Tibet Plateau - Decheng Zhou; Liangxia Zhang; Lin Huang; Jiangwen Fan; Yuzhe Li; Haiyan Zhang (Journal of Cleaner Production, 2023)

Hydrocarbon accumulation controlled by early stage rifting and late stage orthogonal subduction, the Madura Sub-Basin, Indonesia as example - Xiwu Luan; Lin Li; Yintao Lu; Guozhang Fan; Xinyuan Wei; Peter Lunt (Journal of Asian Earth Sciences, 2023)

A new xanthene-based platform for developing NIR fluorogenic probes for in vivo bioimaging - Xiao-Fan Zhang; Lin Shen; Sheng Wang; Qian Chen; Xiao-Qun Cao; Shi-Li Shen; Xiaohua Li (Chemical Engineering Journal, 2023)

Performance and mechanism of calcium peroxide reducing H2S production from sludge anaerobic fermentation - Yunhao Xu; Qizi Fu; Wenming Wang; Fan Yang; Xuemei Li; Fengming Song; Yanguang Qing; Ziqi Lin; Weiqi Long; Dongbo Wang (Chemical Engineering Journal, 2023)

Higher impact resistance and lower antibiotic resistance genes proliferation rate in shortcut nitrification-denitrification process under long-term antibiotics selection pressure - Chong Yang; Zhouliang Tan; Lin Wang; Hongyan Zhang; Wenwei Li; Fan Wang; Xin Li; Houzhen Zhou; Yangwu Chen (Chemical Engineering Journal, 2023)

Genome-Wide Identification, Evolution Analysis of PI-PLC Family and Their Expression Patterns in Response to Different Hormones and Growth in Banana (Musa L.) - Qiuzhen Wu; Zhengyang Fan; Feng Qi; Dan Li; Zihao Zhang; Yukun Chen; Yuji Huang; Yuling Lin; Zhongxiong Lai (Tropical Plant Biology, 2023)

IRAK-M Ablation Promotes Status Epilepticus-Induced Neuroinflammation via Activating M1 Microglia and Impairing Excitatory Synaptic Function - Xiao-Shan Liang; Ting-Lin Qian; Yi-Fan Xiong; Xiao-Tao Liang; Yue-Wen Ding; Xiao-Yu Zhu; Yun-Lv Li; Jie-Li Zhou; Le-Yi Tan; Wei-Peng Li; Wei Xie (Molecular Neurobiology, 2023)

Integrated metabolomics and transcriptomics analyses reveal the key genes regulating differential metabolites of longissimus dorsi muscle in castrated South Sichuan black goats (Capra hircus) - Nanchi Zhang; Feng Xu; Li Wang; Quzhe Emu; Yong Wei; Lin Zhang; Yuan Xu; Jingsheng Fan; Yan Sun; Shuobu Shama; Hongyan Zhou; Chunmei Li; et al. (Functional & Integrative Genomics, 2023)

New progress of tuberculosis scar carcinoma - Wenwen Sun; Yujin Liu; Lishu Zhao; Hao Wang; Li Ye; Xinyue Liu; Kandi Xu; Yu Chen; Lin Fan (Cancer and Metastasis Reviews, 2023)
It has been demonstrated that scar tissue and fibrosis may increase the likelihood of developing malignancies. Specifically, scar tissue has been linked to the occurrence and progression of lung cancer (LC), though the precise mechanisms necessitate further research for explanation. Lung scarring can stem from various causes, with carcinogenesis on scarring lesions in pulmonary tuberculosis (PTB) being the most frequent (accounting for approximately 75% of cases). Notably, having previously cured, PTB is the second most common risk factor for LC after smoking, with approximately 3% of PTB patients experiencing LC as a secondary condition. This essay will delve into the mechanisms, treatment, and prognosis of tuberculosis scar carcinoma (TSC).

Potential biomarkers for immunotherapy in non-small-cell lung cancer - Xing Wang; Ziyun Qiao; Beatrice Aramini; Dong Lin; Xiaolong Li; Jiang Fan (Cancer and Metastasis Reviews, 2023)

Visualize intracellular β-galactosidase using an asymmetric near-infrared fluorescent probe with a large Stokes shift - Shijun Chen; Xiaodong Ma; Haijie Wang; Lin Wang; Yuanyuan Wu; Yaping Wang; Yiyi Li; Wenkang Fan; Caoyuan Niu; Shicong Hou (Analytica Chimica Acta, 2023)

Four organosulfur compounds from the seeds of Capsella bursa-pastoris and their anti-inflammatory activities - Zhen-Zhen Wei; Ti-Qiang Zhou; Zi-Ming Xia; Si-Fan Liu; Min Li; Guang-Jie Zhang; Ying Tian; Bin Li; Lin Wang (Natural Product Research, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

Can China achieve its 2030 and 2060 CO2 commitments? Scenario analysis based on the integration of LEAP model with LMDI decomposition - Yimin Huang; Yuan Wang; Jiaoting Peng; Fan Li; Lin Zhu; Huihui Zhao; Rui Shi (Science of The Total Environment, 2023)

Antimicrobial mechanisms of ZnO nanoparticles to phytopathogen Pseudomonas syringae: Damage of cell envelope, suppression of metabolism, biofilm and motility, and stimulation of stomatal immunity on host plant - Guangjin Fan; Qingli Xiao; Qian Li; Yinling Xia; Hui Feng; Xiaozhou Ma; Lin Cai; Xianchao Sun (Pesticide Biochemistry and Physiology, 2023)

The AMPK-dependent inhibition of autophagy plays a crucial role in protecting photoreceptor from photooxidative injury - Yu-Lin Li; Tian-Zi Zhang; Li-Kun Han; Chang He; Yi-Ran Pan; Bin Fan; Guang-Yu Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Neuroprotective Effects of Oxymatrine via Triggering Autophagy and Inhibiting Apoptosis Following Spinal Cord Injury in Rats - Jian Li; Yang Cao; Lin-Na Li; Xin Chu; Yan-Song Wang; Jia-Jun Cai; Jin Zhao; Song Ma; Gang Li; Zhong-Kai Fan (Molecular Neurobiology, 2023)

Lab-on-chip separation and biosensing of pathogens in agri-food - Li Xue; Fan Jiang; Xinge Xi; Yanbin Li; Jianhan Lin (Trends in Food Science & Technology, 2023)

Sodium selenite inhibits proliferation of lung cancer cells by inhibiting NF-κB nuclear translocation and down-regulating PDK1 expression which is a key enzyme in energy metabolism expression - Xiao Xu; Yaqin Hou; Shumeng Lin; Kai Wang; Yanbei Ren; Tiansheng Zheng; Xi Zhang; Ming Li; Lihong Fan (Journal of Trace Elements in Medicine and Biology, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

Variation in microbiological heterogeneity in Chinese strong-flavor Baijiu fermentation for four representative varieties of sorghum - Mao-Ke Liu; Yu-Ming Tang; Cheng-Yuan Liu; Xin-Hui Tian; Ji-Wei Zhang; Xiao-Li Fan; Kai-Feng Jiang; Xian-Lin Ni; Xin-Yu Zhang (International Journal of Food Microbiology, 2023)

Composition and transcriptional activity of oil reservoir microorganisms under different gas/liquid ratios - Li-Bin Shou; Zhao-Wei Hou; Yi-Fan Liu; Ying Wang; Lei Zhou; Jin-Feng Liu; Shi-Zhong Yang; Ji-Dong Gu; Xiao-Lin Wu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2023)

Soy protein isolate-citrus pectin-gallic acid ternary composite high internal phase Pickering emulsion for delivery of β-carotene: Physicochemical, structural and digestive properties - Xinyu Xu; Lin Li; Chunmin Ma; Dan Li; Yang Yang; Xin Bian; Jing Fan; Na Zhang; Feng Zuo (Food Research International, 2023)

Metabolomic characteristics in human CD34+ hematopoietic stem/progenitor cells exposed to polystyrene nanoplastics - Xiaoli Guo; Cheng Cheng; Lin chen; Changsong Cao; Dongbei Li; Ruihua Fan; Xudong Wei (Food and Chemical Toxicology, 2023)

N-doped biochar mediated peroxydisulfate activation for selective degradation of bisphenol A: The key role of potential difference-driven electron transfer mechanism - Jiaqu Tan; Xinmin Chen; Mengru Shang; Jiannan Cui; Dongya Li; Fan Yang; Zhen Zhang; Haotian Zhang; Qitang Wu; Yongtao Li; Xueming Lin (Chemical Engineering Journal, 2023)

Seasonal variation of aerosol optical properties in a coastal city of southeast China: Based on one year of measurements - Lingjun Li; Mengren Li; Siqing Zhang; Liqian Yin; Xiaoting Ji; Yuping Chen; Chao Dong; Lingling Xu; Xiaolong Fan; Gaojie Chen; Ziyi Lin; Youwei Hong; et al. (Atmospheric Environment, 2023)

Selenium Deficiency Induces Inflammatory Response and Decreased Antimicrobial Peptide Expression in Chicken Jejunum Through Oxidative Stress - Yujiao He; Lin Peng; Xiaochun Zhao; Xue Fan; Xinyu Tang; Guangliang Shi; Shu Li (Biological Trace Element Research, 2023)

Study on the Classification Perception and Visibility Enhancement of Ship Navigation Environments in Foggy Conditions - Chiming Wang; Boyan Fan; Yanan Li; Jingjing Xiao; Lanxi Min; Jing Zhang; Jiuhu Chen; Zhong Lin; Sunxin Su; Rongjiong Wu; Shunzhi Zhu (Journal of Marine Science and Engineering, 2023)
Based on ship navigational requirements and safety in foggy conditions and with a particular emphasis on avoiding ship collisions and improving navigational abilities, we constructed a fog navigation dataset along with a new method for enhancing foggy images and perceived visibility using a discriminant deep learning architecture and the EfficientNet neural network by replacing the SE module and incorporating a convolution block attention module and focal loss function. The accuracy of our model exceeded 95%, which meets the needs of an intelligent ship navigation environment in foggy conditions. As part of our research, we also determined the best enhancement algorithm for each type of fog according to its classification.

Enantioselective activity and toxicity of chiral acaricide cyflumetofen toward target and non-target organisms - Yifan Zhang; Zhiqiang Kong; Noel Gregoire; Lin Li; Lin Yang; Mengying Zhao; Nuo Jin; Fengzhong Wang; Bei Fan; Frédéric Francis; Minmin Li (Chemosphere, 2023)

The effect of microplastics on the depuration of hydrophobic organic contaminants in Daphnia magna: A quantitative model analysis - Wei Lin; Yu Li; Xiaoying Xiao; Fuqiang Fan; Jiakun Jiang; Ruifen Jiang; Yong Shen; Gangfeng Ouyang (Science of The Total Environment, 2023)

Valorization of thermally hydrolyzed sludge with clay for sintering of ceramic tiles - Lei Wen; Lin Lin; Yi-ang Fan; Yang Luo; Sheng-shou Ma; Ying Zhou; Chao Yang; Kaimin Shih; Xiao-yan Li (Science of The Total Environment, 2023)

Overexpression of OsNF-YB4 leads to flowering early, improving photosynthesis and better grain yield in hybrid rice - Meifang Peng; Feng Gan; Xiaomin Lin; Run Yang; Shaoyi Li; Wei Li; Lan Wu; Xiaoli Fan; Kegui Chen (Plant Science, 2023)

Stelleratenoids A−F, macrocyclic daphnane orthoesters with anti-HIV activity from the roots of Stellera chamaejasme L. - Kang Ding; Zi-Yao Wu; Nuan Zhang; Jun He; Fan Zhang; Jing-Jing Wu; Hong-Jin Bai; Wei-Ku Zhang; Lin Li; Jie-Kun Xu (Phytochemistry, 2023)

Calcium-dependent activation of CPK12 facilitates its cytoplasm-to-nucleus translocation to potentiate plant hypoxia sensing by phosphorylating ERF-VII transcription factors - Biao Fan; Ke Liao; Lin-Na Wang; Li-Li Shi; Yi Zhang; Ling-Jing Xu; Ying Zhou; Jian-Feng Li; Yue-Qin Chen; Qin-Fang Chen; Shi Xiao (Molecular Plant, 2023)

Drought stress reduces the feeding preference of Nilaparvata lugens due to the accumulation of abscisic acid and callose deposition in rice - Guangrong Liao; Jitong Li; Wenyan Fan; Lin Chen; Jinglan Liu (Journal of Asia-Pacific Entomology, 2023)

Highly effective recovery of palladium from a spent catalyst by an acid- and oxidation-resistant electrospun fibers as a sorbent - Nianshou Cheng; Lin Zhang; Mingyue Wang; Jiancheng Shu; Penghui Shao; Liming Yang; Xiaojing Meng; Yuzhu Fan; Min Li (Chemical Engineering Journal, 2023)

Inchworm-Inspired soft robot with magnetic driving based on PDMS, EGaIn and NdFeB (PEN) combination - Yanfang Guan; Yansheng Liu; Qilong Wang; Hao Geng; Tangyong Cui; Yuang Hu; Qing Luo; Aonan Li; Wujie Li; Yang Lin; Lin Zhang; Guangyu Liu; et al. (Chemical Engineering Journal, 2023)

An injectable antibacterial hydrogel to regulate ocular immune for endophthalmitis treatment - Zunzhen Ming; Lin Han; Huanhuan Zhu; Meiyu Bao; Qiangyuan Fan; Shaobo Xue; Kesheng Wang; Yue Zhang; Meiling Lu; Chongshun Xu; Qi Wu; Tingting Li; et al. (Chemical Engineering Journal, 2023)

Genome-wide Association Study of Root Hair Length in Maize - Li Xuhui; Lu Siqi; Chen Weiwei; Zhu Hang; Lin Huanzhang; Fu Danwen; Fan Lina; Fang Junteng; Hu Yuanqiang; Zhang Xiangbo; Chang Hailong; Qi Yongwen (Tropical Plant Biology, 2023)

Decrease levels of bone morphogenetic protein 6 and noggin in chronic schizophrenia elderly - Lin Sun; Qi Qiu; Chunxia Ban; Sijia Fan; Shifu Xiao; Xia Li (Cognitive Neurodynamics, 2023)

Geostatistical inversion method based on seismic waveform similarity - Xue-Bin Ni; Jia-Jia Zhang; Kang Chen; Guang-Zhi Zhang; Bao-Li Wang; Zhuo-Fan Liu; Ying Lin (Applied Geophysics, 2023)

Short-term exposure of Cannabidiol on Zebrafish (Danio Rerio): Reproductive Toxicity - Lin Li; Bei Fan; Zhiqiang Kong; Yifan Zhang; Mengying Zhao; Jesus Simal-Gandara; Fengzhong Wang; Minmin Li (Environmental Science and Pollution Research, 2023)

Correction: PTEN-induced kinase 1 enhances the reparative effects of bone marrow mesenchymal stromal cells on mice with renal ischaemia/reperfusion-induced acute kidney injury - Chenyu Lin; Wen Chen; Yong Han; Yujie Sun; Xiaoqiong Zhao; Yuan Yue; Binyu Li; Wenmei Fan; Tao Zhang; Li Xiao (Human Cell, 2023)

Distribution of polycyclic aromatic hydrocarbons in indoor/outdoor window films and the indoor film/air partition of northeastern Chinese college dormitories - Yu Sun; Li-Yan Liu; Lin-Lin Lv; Xi-Xi Zhou; Yu-Yan Luo; Jin-Ze Qu; Wan-Li Ma; Zi-Feng Zhang; Li Song; Li Wang; Yi-Fan Li (Chemosphere, 2023)

Levels, distribution, childhood exposure assessment, and influencing factors of polybrominated diphenyl ethers (PBDEs) in household dust from nine cities in China - Jing Qi; Xiaoli Wang; Lin Fan; Shuhan Gong; Xinqi Wang; Chong Wang; Li Li; Hang Liu; Yun Cao; Mengmeng Liu; Xu Han; Liqin Su; et al. (Science of The Total Environment, 2023)

Polybrominated diphenyl ethers and bromophenols in paired serum, hair, and urine samples of e-waste dismantlers: Insights into hair as an indicator of endogenous exposure - Meiqing Lin; Shengtao Ma; Jian Tang; Yingxin Yu; Guiying Li; Ruifang Fan; Guoxia Zhang; Bixian Mai; Taicheng An (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Ceria-Promoted and stabilized copper and iron oxides cooperatively catalyze NO efficient degradation by CO - Xiaobing Shi; Lin Tao; Zhangfa Tong; Minguang Fan; Lihui Dong; Bin Li (Fuel, 2023)

Experimental study on cotton stalk pyrolysis tar degradation by oxidation in combination with K-containing semi-coke - Fanrui Meng; Qianwang Cheng; Chunyu Fan; Jianting Lin; Yuejun Liu; Xianchun Li (Fuel, 2023)

Mechanisms of acidic electrolyzed water killing bacteria - Fan Wang; Yan-Ning Lin; Yu Xu; Yong-Bing Ba; Zhao-Huan Zhang; Li Zhao; Wing Lam; Fu-Lan Guan; Yong Zhao; Chang-Hua Xu (Food Control, 2023)

Migration behavior and dietary exposure risk assessment of pesticides residues in honeysuckle (Lonicera japonica Thunb.) based on modified QuEChERS method coupled with tandem mass spectrometry - Qianqian Li; Jialin Zhang; Tao Lin; Chunlin Fan; Yi Li; Zijuan Zhang; Jianxun Li (Food Research International, 2023)

A fast stop-flow two-dimensional liquid chromatography tandem mass spectrometry and its application in food-derived protein hydrolysates - Wu Li; Junhong Huang; Lin Zheng; Wanshun Liu; Liqi Fan; Baoguo Sun; Guowan Su; Jucai Xu; Mouming Zhao (Food Chemistry, 2023)

Lactobacillus plantarum isolated from kefir enhances immune responses and survival of white shrimp (Penaeus vannamei) challenged with Vibrio alginolyticus - Kuo-Chun Tseng; Huai-Ting Huang; Shu-Ning Huang; Fang-Yi Yang; Wen-Hsiung Li; Fan-Hua Nan; Yu-Ju Lin (Fish & Shellfish Immunology, 2023)

A novel N-arachidonoyl-l-alanine-catabolizing strain of Serratia marcescens for the bioremediation of Cd and Cr co-contamination - Xiaoyan Sun; Huiping Feng; Jialiang Luo; Li Lin; Haixiang Zhang; Yali Duan; Fan Liu; Kailu Zhang; Baijie Wang; Dong Li; Yueming Hu; Zhiqiang Zhu (Environmental Research, 2023)

A novel 4-O-endosulfatase with high potential for the structure-function studies of chondroitin sulfate/dermatan sulfate - Lin Wei; Yingying Xu; Min Du; Ying Fan; Ruyi Zou; Xiangyu Xu; Qingdong Zhang; Yu-Zhong Zhang; Wenshuang Wang; Fuchuan Li (Carbohydrate Polymers, 2023)

Assessment of exhaled pathogenic droplet dispersion and indoor-outdoor exposure risk in urban street with naturally-ventilated buildings - Jian Hang; Xia Yang; Cui-Yun Ou; Zhi-Wen Luo; Xiao-Dan Fan; Xue-Lin Zhang; Zhong-Li Gu; Xian-Xiang Li (Building and Environment, 2023)

Quantitative characterization of filamentous fungal promoters on a single-cell resolution to discover cryptic natural products - Peng-Lin Wei; Jie Fan; Jingwen Yu; Zihui Ma; Xian Guo; Nancy P. Keller; Erwei Li; Chunbo Lou; Wen-Bing Yin (Science China Life Sciences, 2023)

Amnion-derived serum amyloid A1 participates in sterile inflammation of fetal membranes at parturition - Yi-kai Lin; Fan Zhang; Wen-jia Lei; Xiao-wen Gan; Meng-die Li; Fan Pan; Wang-sheng Wang; Kang Sun (Inflammation Research, 2023)

Genome-wide investigation of the WRKY transcription factor gene family in weeping forsythia: expression profile and cold and drought stress responses - Ya-Lin Yang; Samuel A. Cushman; Shu-Chen Wang; Fan Wang; Qian Li; Hong-Li Liu; Yong Li (Genetica, 2023)

Impact of Tropical Cyclones over the North Indian Ocean on Weather in China and Related Forecasting Techniques: A Review of Progress - Ying Li; Chuanhai Qian; Xiaoting Fan; Beiyao Liu; Wei Ye; Jialu Lin (Journal of Meteorological Research, 2023)

The impacts of extreme marine weather and marine scientific and technological innovation on marine economic development: Evidence form China’s coastal regions - Chenggang Li; Hongye Jia; Yikang Wan; Yongxiang Hu; Bingying Zeng; Wanyue Zhang; Xiangbo Fan; Tao Lin; Guofei Shang; Weiyan Wang (Frontiers in Marine Science, 2023)
The extreme marine weather is a very vital factor and has important implications for of marine economic development. However, there is a lack of systematic and quantitative analyses of its impact on the marine economic development. Here, we study the impacts of extreme marine weather on marine economic development of 11 coastal regions in China, using the dynamic panel model. We found that extreme marine weather exerts a significant negative impact on the marine economic development. The marine scientific and technological innovation promotes marine economic development in a prominent manner. The marine scientific and technological innovation slows down the unfavorable impact of extreme marine weather on the marine economy. After considering different industries for marine economic development and heterogeneity, we found that extreme marine weather and marine scientific and technological innovation have a great impact on marine economic development in the tertiary industry and the areas with high development concerning marine economy level, while deliver a small impact on the marine economic development in the primary industry and the areas low development level. This paper empirically studies the relationship between the two variables of marine extreme weather and marine science and technology innovation and its impact on marine economic development, enriches the research perspective of extreme weather on marine economic development, and provides new method evidence for improving the level of marine scientific and technological innovation and promoting the development of marine economy.

Using fluorescence index (FI) of dissolved organic matter (DOM) to identify non-point source pollution: The difference in FI between soil extracts and wastewater reveals the principle - Yuye Lin; En Hu; Changshun Sun; Ming Li; Li Gao; Linhua Fan (Science of The Total Environment, 2023)

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

Levels, distribution, sources and children health risk of PAHs in residential dust: A multi-city study in China - Xinqi Wang; Xiaoli Wang; Jing Qi; Shuhan Gong; Chong Wang; Li Li; Lin Fan; Hang Liu; Yun Cao; Mengmeng Liu; Xu Han; Liqin Su; et al. (Science of The Total Environment, 2023)

Associations of per- and polyfluoroalkyl substances and their alternatives with bone mineral density levels and osteoporosis prevalence: A community-based population study in Guangzhou, Southern China - Shujun Fan; Yan Wu; Michael S. Bloom; Jiayun Lv; Li Chen; Weiping Wang; Zhi Li; Qinqin Jiang; Li Bu; Jie Shi; Tongxing Shi; Xiaowen Zeng; et al. (Science of The Total Environment, 2023)

The impact of Russia-Ukraine conflict on global food security - Faqin Lin; Xuecao Li; Ningyuan Jia; Fan Feng; Hai Huang; Jianxi Huang; Shenggen Fan; Philippe Ciais; Xiao-Peng Song (Global Food Security, 2023)

A 13 million-year record of Li isotope compositions in island carbonates: Constraints on bulk inorganic carbonate as a global seawater Li isotope archive - Guang-Yi Wei; Feifei Zhang; Yi-Sheng Yin; Yi-Bo Lin; Philip A.E. Pogge von Strandmann; Mengchun Cao; Na Li; Guolin Xiong; Xinran Chen; Caiwei Fan; Changgui Xu; Fei Tan; et al. (Geochimica et Cosmochimica Acta, 2023)

The material basis of astringency and the deastringent effect of polysaccharides: A review - Jun Liu; Jin Xie; Junzhi Lin; Xingliang Xie; Sanhu Fan; Xue Han; Ding-kun Zhang; Li Han (Food Chemistry, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Effect of antifreeze protein on the quality and microstructure of frozen chicken breasts - Junlin Chen; Yaqi Fan; Xingguo Zhang; Zimeng Yuan; Hairu Zhang; Xinglian Xu; Jun Qi; Guoyuan Xiong; Lin Mei; Yuan Zhu; Linwei Yang; Chao Li (Food Chemistry, 2023)

Component characteristics and reactive oxygen species scavenging activity of anthocyanins from fruits of Lonicera caerulea L. - Lili Fan; Li Lin; Ye Zhang; Sining Li; Zhonghua Tang (Food Chemistry, 2023)

Unveiling the interaction mechanism between facet-dependent pyrite nanoparticles and Cr(VI) under anaerobic environment: adsorption, redox, and phase transformation - Chenrui Liu; Yun Liu; Wentao Shen; Shuangyi Lin; Hao He; Fan Li; Feng Li; Jiang Tian (Chemical Engineering Journal, 2023)

Effect of landing disturbance caused by capping materials on the control efficiency of contaminated sediment capping - Bin Wang; Wei Zhu; Yong Wu; Hao Hou; Lin Cheng; Xiaoge Xu; Yuehong Li; Xiaowei Lin; Chengxin Fan (Journal of Soils and Sediments, 2023)

Enhanced Lipid Productivity in Low-Starch Mutant of Monoraphidium sp. for Biodiesel Production - Yimeng Lin; Yunye Zhang; Yang Fan; Chang Li; Hongzhi Ling; Wenxiang Ping; Jingping Ge (BioEnergy Research, 2023)

Chromosome-Level Genome Assembly of the Rough-Toothed Dolphin (Steno bredanensis) - Haiyu Gao; Hui Kang; Yaolei Zhang; Jiahao Wang; Wenzhi Lin; Peijun Zhang; Mingli Lin; Mingming Liu; Guangyi Fan; Songhai Li (Journal of Marine Science and Engineering, 2023)
The rough-toothed dolphin (Steno bredanensis), the single extant species of the genus Steno, inhabits tropical and subtropical oceans. It is an attractive species for studying aquatic adaptation and evolution. The latest advances in high-throughput sequencing are transforming the study of marine mammals and contributing to understanding various phenomena at the species and population level by determining high-quality genomes. Here, to comprehensively understand the genetic features and explore the molecular basis of aquatic adaption, the chromosome-level genome assembly and comparative genomics analyses of S. bredanensis were performed. The 2.30 Gb final genome assembly of S. bredanensis (scaffold N50 length of 105.53 Mb) was obtained using single-tube long fragment read (stLFR) and Hi-C technologies. The genome assembly clearly revealed the preservation of large chromosomal fragments between S. bredanensis and the melon-headed whale (Peponocephala electra). The S. bredanensis genome contained 19,451 predicted protein-coding genes, of which about 92.33% have functional annotations. The genome assembly and gene sets showed high completeness, with a BUSCO score of 90.6% and 97.3%, respectively. We also identified several positively selected genes specific to S. bredanensis, which may be related to fat cell differentiation, tooth morphogenesis, and immunoregulatory activity. Finally, the demographic dynamics of S. bredanensis were estimated by the pairwise sequentially Markovian coalescent (PSMC) model and found that the population was affected by the climate at the time. We demonstrated that improved continuity and accuracy of the assembled sequence warranted the adoption of this chromosome-level genome as the reference genome and advanced the understanding of genetic features of the rough-toothed dolphin, which will be essential for future evolutionary studies and the protection of this species.

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Pollution mechanisms and photochemical effects of atmospheric HCHO in a coastal city of southeast China - Taotao Liu; Yiling Lin; Jinsheng Chen; Gaojie Chen; Chen Yang; Lingling Xu; Mengren Li; Xiaolong Fan; Fuwang Zhang; Youwei Hong (Science of The Total Environment, 2023)

Contaminant characterization at pesticide production sites in the Yangtze River Delta: Residue, distribution, and environmental risk - Mei Li; Qiang Chen; Lu Yang; Ya Zhang; Jinlin Jiang; Shaopo Deng; Jinzhong Wan; Tingting Fan; Tao Long; Shengtian Zhang; Yusuo Lin (Science of The Total Environment, 2023)

Acid-free mechanochemical process to enhance the selective recycling of spent LiFePO4 batteries - Qiyue Zhang; Ersha Fan; Jiao Lin; Sisheng Sun; Xiaodong Zhang; Renjie Chen; Feng Wu; Li Li (Journal of Hazardous Materials, 2023)

Graphitic carbon nitride-based photocatalysts in the applications of environmental catalysis - Hongxia Lin; Jinmo Wu; Fan Zhou; Xiaolong Zhao; Pengfei Lu; Guanghui Sun; Yuhan Song; Yayun Li; Xiaoyong Liu; Hongxing Dai (Journal of Environmental Sciences, 2023)

Construction of 1D/0D CdS nanorods/Ti3C2 QDs Schottky heterojunctions for efficient photocatalysis - Chengqun Xu; Dezhi Li; Haiyang Liu; Dongyu Wang; Xiaolu Liu; Shiyin Lin; Yuchen Yang; Donghua Fan; Hui Pan (Journal of Environmental Chemical Engineering, 2023)

Supply reliability-driven joint optimization of maintenance and spare parts inventory in a gas pipeline system - Lin Fan; Huai Su; Enrico Zio; Yuejun Li; Li Zhang; Shiliang Peng; Yuxuan He; Yucheng Hao; Jinjun Zhang (Gas Science and Engineering, 2023)

Catalytic pyrolysis of 5-Amino-1H-Tetrazole with copper and its oxide: A deep insight into the combustion mechanism for high nitrogen compound - Si-Yuan Zhou; Jiu Chen; Xuan Li; Fan Jia; Dan Zhang; Li-Feng Xie; Bin Li; Lin Jiang (Fuel, 2023)

Studies on micromorphology and permeability of hydrate-bearing porous media - Gang Li; Yi-Fan Weng; Xiao-Sen Li; Ze-Lin Xu; Qiu-Nan Lv; Chun-Gang Xu (Fuel, 2023)

Selenium alleviates cadmium-induced mitophagy through FUNDC1-mediated mitochondrial quality control pathway in the lungs of sheep - Shixuan Lin; Fan Yang; Mingwen Hu; Jing Chen; Guiping Chen; Aiming Hu; Xiong Li; Danghua Fu; Chenghong Xing; Zhiwei Xiong; Yunhui Wu; Huabin Cao (Environmental Pollution, 2023)

Solvent-free oxidation of toluene to benzaldehyde using electron-rich Au clusters confined in Silicalite-1 - He Huang; Huahua Fan; Yuzhen Ge; Wanyue Ye; Yingcen Liu; Caicheng Song; Hua Lin; Xiaotong Zhang; Bing Li; Xiaowa Nie; Shufen Zhang; Rongwen Lu (Chemical Engineering Journal, 2023)

NIR-responsive hollow germanium nanospheres mediate photothermal/photodynamic therapy and restrain immunosuppression to cooperatively eradicate primary and metastatic tumors - Qilin Li; Huiling Fan; Yunruo Xu; Miaodeng Liu; Jia Liu; Luming Xu; Meizhen Zou; Qian Cheng; Yan Zhang; Tao Liang; Lin Shi; Xianluo Hu; et al. (Chemical Engineering Journal, 2023)

Compound Probiotic Ameliorates Acute Alcoholic Liver Disease in Mice by Modulating Gut Microbiota and Maintaining Intestinal Barrier - Haixia Liu; Xing Kang; Xiaodan Yang; Hao Yang; Xiaoyu Kuang; Peng Ren; Huan Yan; Xiaorong Shen; Yongbo Kang; Lin Li; Xiaohui Wang; Linzhi Guo; et al. (Probiotics and Antimicrobial Proteins, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

AIFM1 variants associated with auditory neuropathy spectrum disorder cause apoptosis due to impaired apoptosis-inducing factor dimerization - Yue Qiu; Hongyang Wang; Huaye Pan; Jing Guan; Lei Yan; Mingjie Fan; Hui Zhou; Xuanhao Zhou; Kaiwen Wu; Zexiao Jia; Qianqian Zhuang; Zhaoying Lei; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Selenium deficiency increased duodenal permeability and decreased expression of antimicrobial peptides by activating ROS/NF-κB signal pathway in chickens - He Yujiao; Tang Xinyu; Fan Xue; Li Zhe; Peng Lin; Shi Guangliang; Li Shu (BioMetals, 2023)

A prognostic cuproptosis-related lncRNA predictive signature for bladder cancer patients - Shaoqin Jiang; Jili Zhang; Qi Fan; Zhihao Li; Ruiling Dou; Zequn Lin; Zhenlin Chen; Yue Xu; Zhangcheng Huang; Jingyuan Lan; Wenwen Lin; Sijie Xu; et al. (Human Cell, 2023)

Nitrogen mineralization and immobilization in surface sediments of coastal reclaimed aquaculture ecosystems - Xianbiao Lin; Genmei Lin; Yijie Zheng; Wenjing Li; Peng Guo; Shiyuan Fan; Tiantian Kong; Dongfan Tian; Dongyao Sun; Zhuo Shen (Frontiers in Marine Science, 2023)
Sediment nitrogen (N) mineralization and immobilization are two crucial processes driven by microorganisms, which may play significant roles in the regulation of water quality in aquaculture ecosystems. However, limited information is available about the quantitative importance of sedimentary N mineralization and immobilization in coastal aquaculture systems. Here, a combination of incubation experiments with a 15 N isotope dilution technique were employed, aiming to quantify N mineralization and immobilization processes in surface sediments (0–5 cm) of three types of aquaculture ecosystems (seabass, white shrimp, and green crab ponds) reclaimed within the western bank of the Pearl River Estuary. Our results showed that no significant difference in sediment N mineralization and immobilization rates, microbial abundances, and organic matter among different aquaculture types on small-scale range. Meanwhile, prolonged pond-drying significant reduced sediment N mineralization and immobilization rates, bacterial abundances, organic matter, moisture content, ferrous ion (Fe 2+ ), Fe 2+ /Fe 3+ , and ammonium (NH 4 + ), while not strongly altered sediment percentage of NH 4 + mineralized per day (PAM), relative ammonium immobilization (RAI), fungal abundances, TOC/TN, nitrate (NO 3 − ), and δ 13 C org . N mineralization and immobilization rates were both significantly related to overlying water NO 3 − , as well as sediment moisture content, bulk density, organic matter, Fe 2+ , and microbial abundances. In addition, the total mineralized and immobilized N in aquaculture surface sediments from the Guangdong-Hong Kong-Macao Greater Bay Area were estimated to be approximately 4.55×10 4 and 3.68×10 4 t N yr -1 , respectively. Higher N mineralization relative to N immobilized fluxes indicated that the sediment serves as an important source of eutrophication in reclaimed aquaculture system of coastal wetlands.

Soil organic carbon content increase in the east and south of China is accompanied by soil acidification - Xiao-Lin Sun; Budiman Minasny; Yun-Jin Wu; Hui-Li Wang; Xiao-Hui Fan; Gan-Lin Zhang (Science of The Total Environment, 2023)

Artificial clickase-triggered fluorescence “turn on” based on a click bio-conjugation strategy for the immunoassay of food allergenic protein - Xianlong Zhang; Lihua Fan; Zhuoqun Su; Qinfeng Xu; Lingyi Xi; Lin Li; Yongning Wu; Guoliang Li (Food Chemistry, 2023)

Enhancing hydrodeoxygenation-isomerization of FAME over M-SAPO-11 in one-step process: Effect of in-situ isomorphic substitution of transition metals and synergy of PtxSny alloy - Xingyong Li; Qiyuan Fan; Yankun Wu; Xin Lin; Sihan Ma; Shuirong Li; Yueyuan Ye; Dechao Wang; Jun Cheng; Zhifeng Zheng; Jianchun Jiang (Chemical Engineering Journal, 2023)

Activate whole-body passivation ability of small isomeric D-π-A molecules via amino position effect to improve the photovoltaic performance of perovskite solar cells - Zonghan Guo; Tongxin Xue; Xiaoxu Sun; Dan Li; Fengyou Wang; Lin Fan; Xiaoyan Liu; Lili Yang; Maobin Wei (Chemical Engineering Journal, 2023)

Response of performance, antibiotic resistance genes and bacterial community exposure to compound antibiotics stress: Full nitrification to shortcut nitrification and denitrification - Lin Wang; Zhaoli Wang; Fan Wang; Yue Guan; Dan Meng; Xin Li; Houzhen Zhou; Xudong Li; Yangwu Chen; Zhouliang Tan (Chemical Engineering Journal, 2023)

Conserved and divergent evolution of the bZIP transcription factor in five diploid Gossypium species - Fangting Ye; Xiaogang Zhu; Shaofang Wu; Yunyue Du; Xinfeng Pan; Yuchen Wu; Zhengyi Qian; Zhaowei Li; Wenxiong Lin; Kai Fan (Planta, 2023)

Biodynamic responses of adolescent idiopathic scoliosis exposed to vibration - Shaowei Jia; Liying Lin; Hufei Yang; Junde Xie; Zefeng Liu; Tianyou Zhang; Jie Fan; Li Han (Medical & Biological Engineering & Computing, 2023)

Size-specific particulate matter and outpatient visits for allergic conjunctivitis in children: a time-stratified case-crossover study in Guangzhou, China - Jin Zhou; Lijun Fan; Hualiang Lin; Dehui Zheng; Lihong Yang; Dan Zhuo; Jiayang Zhuoma; Huan Li; Shiyu Zhang; Zengliang Ruan (Environmental Science and Pollution Research, 2022)

Golden 2-like transcription factor contributes to the major QTL against rice black-streaked dwarf virus disease - Xuejuan Li; Feng Lin; Chenyang Li; Linlin Du; Zhiyang Liu; Wenjuan Shi; Jianying Lv; Xiaoyan Cao; Ying Lan; Yongjian Fan; Yijun Zhou; Tong Zhou (Theoretical and Applied Genetics, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Co-axial Projective Imaging for Augmented Reality Telementoring in Skin Cancer Surgery - Fan Zhang; Carlo M. Contreras; Pengfei Shao; Liping Zhao; Bingxuan Wu; Chenmeng Li; Feng Lin; Xiaohong Zhong; Zhongliang Lang; Peng Liu; Ronald X. Xu (Annals of Biomedical Engineering, 2022)

The association between ethylene oxide exposure and asthma risk: a population-based study - Ziye Li; Pingfan Shi; Zhibo Chen; Wenjia Zhang; Shumeng Lin; Tiansheng Zheng; Ming Li; Lihong Fan (Environmental Science and Pollution Research, 2022)

Circular RNA expression profile of systemic lupus erythematosus and its clinical significance as a potential novel biomarker - Wenyu Li; Runge Fan; Cheng Zhou; Yue Wei; Shunsheng Lin; Sijian Wen; Wen Zeng; Wei Hou; Cheng Zhao; Youkun Lin (Genes & Genomics, 2022)
Background Circular RNAs (circRNAs) are a class of endogenous noncoding RNAs that are more abundant, specific, and highly organized than linear RNAs. Increasing evidence supports that circRNAs may serve as diagnostic biomarkers in many diseases, but their potential as biomarkers in systemic lupus erythematosus (SLE) remains unclear. Objective We investigated the critical circRNAs involved in SLE progression and explored their potential application as biomarkers in SLE. Method RNA sequencing was conducted on peripheral blood mononuclear cells (PBMCs) from 4 SLE patients and 4 healthy volunteers. CircRNA profile data were analyzed to identify differentially expressed circRNAs and visualized via R software. After screening, qPCR analysis of target circRNA expression was performed using PBMCs from 31 SLE patients and 35 healthy volunteers. Correlations between circRNA expression levels and the SLEDAI score were assessed via Spearman correlation analysis. Finally, the performance of circRNAs as biomarkers in SLE was examined by receiver operating characteristic curve analysis. Results The result identified six differentially expressed circRNAs between SLE patients and healthy controls: hsa_circ_0006689, hsa_circ_0070562, hsa_circ_0006117, hsa_circ_0007683, hsa_circ_0042519, and hsa_circ_0008647. The validation analysis showed differing relative expression levels of hsa_circ_0007683, hsa_circ_0042519, hsa_circ_0008647, and hsa_circ_0006689 between SLE patients and healthy volunteers (P < 0.05), and hsa_circ_0006689 expression in PBMCs correlated with the SLEDAI score (P < 0.05). Furthermore, addition of hsa_circ_0006689 expression increased the sensitivities of anti-dsDNA antibody and anti-Sm antibody levels for SLE diagnosis (from 29.03 to 61.30% and 32.26–71.00%, respectively). Conclusion Our results suggest hsa_circ_0006689 may be a useful circRNA biomarker for SLE diagnosis and prognosis.

Complete genome sequence of Aconitum amalgavirus 1, a distinct member of the genus Amalgavirus - Jie Yang; Ping-Xiu Lan; Jin-Ming Li; Xiao-Jiao Chen; Guan-Lin Tan; Tai-Yun Wei; Ru-Hui Li; Fan Li (Archives of Virology, 2022)

Theoretical analysis on influence factors of anchor cable internal force under over-excavation considering earth berm - Jiayong Lin; Feicong Zhou; Wenhao Fan; Mao Chen; Jinyi Li; Yifan Jiang; Ming Lin; Ping Zhou; Zhijie Wang (Arabian Journal of Geosciences, 2022)

Genome-wide identification of black pepper (Piper nigrum L.) Dof gene family and the differential gene screening in resistance to Phytophthora capsici - Fenju Zhang; Rui Fan; Lin Yan; Lisong Hu; Fan Su; Dewei Yang; Jing Li (Biologia, 2022)

Identification of terrigenous and autochthonous organic carbon in sediment cores from cascade reservoirs in the upper stream of Pearl River and Wujiang River, southwest China: lignin phenol as a tracer - Li Gao; Xin Lin; Jun Fan; Ming Yang; Xueping Chen; Fushun Wang; Jing Ma (Acta Geochimica, 2022)

The differential impact of air pollutants on acute urticaria and chronic urticaria: a time series analysis - Jiawei Li; Guoqiang Song; Zhenzhen Mu; Xiaoou Lan; Fan Yang; Lin Li; Xiuping Han (Environmental Science and Pollution Research, 2022)

Proteomic analysis of the spineless cuttlefish Sepiella japonica: Exploratory analyses on the phenomenon of death after spawning - Hongfei Li; Shuangrui Lin; Pengzhi Qi; Jingtian Wang; Meihua Fan; Hongwei Huang; Zhenyu Dong; Kaida Xu; Baoying Guo (Frontiers in Marine Science, 2022)
To better understand the physiological events involving death after spawning in S. japonica (Japanese spineless cuttlefish), we have presently generated a proteomic data set to properly examine this phenomenon. As such, a proteomic-based approach was employed to identify differentially expressed proteins (DEPs) in the optic glands of S. japonica , at three distinct growth stages: pre-spawning after sexual maturity (group A); spawning (group B) and postspawning before death (group C). About 955, 1000, and 1024 DEPs were identified for each comparative group analysis (i.e., group B vs A, group B vs C, and group C vs A). We further discovered that the function of these newly identified DEPs was mostly related to molecular events such as gene translation and signal transduction. According to the enriched GO terms obtained by Gene Ontology analysis, the function of most DEPs was correlated with structural molecule activity, ribosome function and gene expression. The majority of DEPs were known to be involved in signal transduction and energy metabolism, interestingly, some aging-related DEPs were also identified. Putting together, our study provides new insights, at the protein level, in the phenomenon of death after spawning in S. japonica , by referring to anti-aging effects conserved in other cephalopoda species.

Correction: Co-axial Projective Imaging for Augmented Reality Telementoring in Skin Cancer Surgery - Fan Zhang; Carlo M. Contreras; Pengfei Shao; Liping Zhao; Bingxuan Wu; Chenmeng Li; Tao Lin; Xiaohong Zhong; Zhongliang Lang; Peng Liu; Ronald X. Xu (Annals of Biomedical Engineering, 2022)

PTEN-induced kinase 1 enhances the reparative effects of bone marrow mesenchymal stromal cells on mice with renal ischaemia/reperfusion-induced acute kidney injury - Chenyu Lin; Wen Chen; Yong Han; Yujie Sun; Xiaoqiong Zhao; Yuan Yue; Binyu Li; Wenmei Fan; Tao Zhang; Li Xiao (Human Cell, 2022)
Acute kidney injury (AKI) is a common severe acute syndrome caused by multiple factors and is characterized by a rapid decline in renal function during a short period. Bone marrow mesenchymal stromal cells (BMSCs) are effective in treating AKI. However, the mechanism of their beneficial effects remains unclear. PTEN-induced kinase 1 (PINK1) may play an important role in kidney tissue repair. In this study, we explored the effect of PINK1 overexpression on enhancing BMSC-mediated repair of AKI. In this study, ischaemia/reperfusion-induced AKI (IRI-AKI) in mice and a hypoxia-reoxygenation model in cells were established, and the indices were examined by pathology and immunology experiments. After ischaemia/reperfusion, PINK1 overexpression reduced apoptosis in injured kidney tissue cell, decreased T lymphocyte infiltration, increased macrophage infiltration, and alleviated the inflammatory response. PINK1 relieved the stress response of BMSCs and renal tubular epithelial cells (RTECs), reduced apoptosis, altered the release of inflammatory factors, and reduced the proliferation of peripheral blood mononuclear cells (PBMCs). In conclusion, BMSCs and RTECs undergo stress responses in response to hypoxia, inflammation and other conditions, and overexpressing PINK1 in BMSCs could enhance their ability to resist these stress reactions. Furthermore, PINK1 overexpression can regulate the distribution of immune cells and improve the inflammatory response. The regulation of mitochondrial autophagy during IRI-AKI maintains mitochondrial homeostasis and protects renal function. The results of this study provide new strategies and experimental evidence for BMSC-mediated repair of IRI-AKI.

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Characterization of Fine-Scale Turbulence Generated in a Laboratory Orbital Shaker and Its Influence on Skeletonema costatum - Lin Yu; Yifan Li; Zhongzhi Yao; Long You; Zong-Pei Jiang; Wei Fan; Yiwen Pan (Journal of Marine Science and Engineering, 2022)
Turbulence is one of the ubiquitous aspects of aquatic systems and affects many physical and biological processes. Based on direct velocity measurements and a computational fluid dynamics (CFD) simulation, we characterized the distribution of the turbulent kinetic dissipations rates (ε) in an orbital shaker system within a range of rotation frequencies. CFD was able to estimate the ε distribution in containers accurately, which was confirmed by other two methods and was independent of velocity measurement. The results showed that ε was linearly correlated with the rotational frequencies. Despite the existence of gradients of ε and the fact that a mean circular horizontal flow was formed within the tank, the energy levels of the whole tank varied spatially within an order of magnitude and the ε distributions at different rotational frequencies were similar, suggesting that the ε distribution in the whole tank could be seen as quasi-homogeneous. To investigate the influence of turbulence on algae growth, culture experiments of a typical diatom—Skeletonema costatum were carried out under different turbulence conditions. Our results suggested turbulence mixing promoted nutrient uptake and growth of Skeletonema costatum, which could be attributed to the break of the diffusion-limited resource concentration boundary layer surrounding phytoplankton.

A Novel Preparation Method for Effervescent Tablets of Xianganfang Containing Fresh Juice using a Semi-Solid Extrusion 3D Printer with Three Cartridge Holders - Xiangru Dong; Wenfang Zhang; Xiaoting Wang; Sijia Liu; Jiawei Liang; Chunqiao Liufu; Shaofeng Zeng; Jiali Pang; Siting Li; Lingjuan Xiong; Guoyan Zhou; Weixing Zhu; et al. (AAPS PharmSciTech, 2022)

Production and Evaluation of a Novel Multi-Epitope Bivalent Vaccine Against Echinococcus multilocaularis Metacestode - Runle Li; Mingyuan Xin; Kunmei Liu; Bingwen Hu; Jingwei Ma; Pei Zhou; Lin Feng; Mingquan Pang; Ri-li Ge; Haining Fan; Le Guo; Feng Tang (International Journal of Peptide Research and Therapeutics, 2022)

Derivation of water quality criteria for glyphosate and its formulations to protect aquatic life in China - Yili Fan; Kaibo Zhang; Ruiqing Zhang; Guanghui Guo; Huixian Li; Yingchen Bai; Ying Lin; Ting Cai (Environmental Science and Pollution Research, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Electrospun Polysaccharides for Periodontal Tissue Engineering: A Review of Recent Advances and Future Perspectives - Jiao Wang; Yi Chen; Jialing Li; Zhen Chen; Min Fan; Fanjing Lin; Yonglin Xie (Annals of Biomedical Engineering, 2022)

Building a predictive model to identify clinical indicators for COVID-19 using machine learning method - Xinlei Deng; Han Li; Xin Liao; Zhiqiang Qin; Fan Xu; Samantha Friedman; Gang Ma; Kun Ye; Shao Lin (Medical & Biological Engineering & Computing, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Nanosecond pulsed electric fields prime mesenchymal stem cells to peptide ghrelin and enhance chondrogenesis and osteochondral defect repair in vivo - Kejia Li; Litong Fan; Jianjing Lin; Boon Chin Heng; Zhantao Deng; Qiujian Zheng; Jue Zhang; Yangzi Jiang; Zigang Ge (Science China Life Sciences, 2022)

Entrainment of Astrocytic and Neuronal Ca2+ Population Dynamics During Information Processing of Working Memory in Mice - Zhu Lin; Feng You; Ting Li; Yijia Feng; Xinyue Zhao; Jingjing Yang; Zhimo Yao; Ying Gao; Jiang-Fan Chen (Neuroscience Bulletin, 2022)

Heat Shock Procedure Affects Cell Division-Associated Genes in Gynogenetic Manipulation - Fan Yu; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Pao Xu; Huan Zhong (Marine Biotechnology, 2022)

Spinal epidural angiolipoma with a special pattern of calcification misdiagnosed as meningioma - Jie Liu; Yu Lin; Jiabo Li; Jikang Fan; Xuejun Yang (Acta Neurologica Belgica, 2022)

Functional traits explain the consistent resistance of biodiversity to plant invasion under nitrogen enrichment - Shao‐peng Li; Pu Jia; Shu‐ya Fan; Yingtong Wu; Xiang Liu; Yani Meng; Yue Li; Wen‐sheng Shu; Jin‐tian Li; Lin Jiang (Ecology Letters, 2022)
Elton's biotic resistance hypothesis, which posits that diverse communities should be more resistant to biological invasions, has received considerable experimental support. However, it remains unclear whether such a negative diversity–invasibility relationship would persist under anthropogenic environmental change. By using the common ragweed ( Ambrosia artemisiifolia ) as a model invader, our 4‐year grassland experiment demonstrated consistently negative relationships between resident species diversity and community invasibility, irrespective of nitrogen addition, a result further supported by a meta‐analysis. Importantly, our experiment showed that plant diversity consistently resisted invasion simultaneously through increased resident biomass, increased trait dissimilarity among residents, and increased community‐weighted means of resource‐conservative traits that strongly resist invasion, pointing to the importance of both trait complementarity and sampling effects for invasion resistance even under resource enrichment. Our study provides unique evidence that considering species’ functional traits can help further our understanding of biotic resistance to biological invasions in a changing environment.

Extensive sequence divergence between the reference genomes of Taraxacum kok-saghyz and Taraxacum mongolicum - Tao Lin; Xia Xu; Huilong Du; Xiuli Fan; Qingwen Chen; Chunyan Hai; Zijian Zhou; Xiao Su; Liquan Kou; Qiang Gao; Lingwei Deng; Jinsheng Jiang; et al. (Science China Life Sciences, 2022)

Salicylic acid alleviates selenium stress and promotes selenium uptake of grapevine - Zhiyu Li; Rong Fan; Xuemei Peng; Junjiang Shu; Lei Liu; Jin Wang; Lijin Lin (Physiology and Molecular Biology of Plants, 2022)

Genomic characterization of a new enamovirus infecting common bean - Ruo-bin Lu; Ping-xiu Lan; Ru-jing Kang; Guan-lin Tan; Xiao-jiao Chen; Ruhui Li; Fan Li (Archives of Virology, 2022)

Cytotoxic α-pyrone derivatives from Cryptocarya yunnanensis - Qian He; Yue Fan; Yu Liu; Yun-Xia You; Li Rao; Yu Su; You-Kai Xu; Bin Lin; Chuan-Rui Zhang (Natural Product Research, 2022)

Transcriptome Analysis Reveals Molecular Mechanisms Underlying Methyl Jasmonate-mediated Biosynthesis of Protopanaxadiol-type Saponins in Panax notoginseng Leaves - Ying Li; Yuan Lin; Bing Jia; Geng Chen; Huineng Shi; Rui Xu; Xuejiao Li; Junrong Tang; Qingyan Tang; Guanghui Zhang; Jianli Yang; Wei Fan; et al. (Journal of Plant Biology, 2022)

New paraconic acids from the endophytic fungus Xylariaceae sp. J4 - Chao Yuan; Xue-Chun Shu; Lin Fan; Ying-Bo Zhang; Ling-Liang Guan; Fu-Lai Yu; Xiao-Lu Chen; Gang Li (Natural Product Research, 2022)

Effect of Sodium Salicylate on Calcium Currents and Exocytosis in Cochlear Inner Hair Cells: Implications for Tinnitus Generation - Ting Fan; Meng-Ya Xiang; Ruo-Qiao Zhou; Wen Li; Li-Qin Wang; Peng-Fei Guan; Geng-Lin Li; Yun-Feng Wang; Jian Li (Neuroscience Bulletin, 2022)

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Analysis of Timing Effect on Flow Field and Pulsation in Vertical Axial Flow Pump - Fan Yang; Pengcheng Chang; Yao Yuan; Na Li; Rongsheng Xie; Xiaowen Zhang; Zhikang Lin (Journal of Marine Science and Engineering, 2021)
Vertical axial flow pump device has the characteristics of large flow and low head, which is widely used in pumping station projects with head of 3–9 m. In order to study the influence of the timing effect of the impeller relative flow channel and guide vane on the flow field and pulsation in the axial flow pump device, the whole flow channel of the vertical axial flow pump device was taken as the research object. The reliability of the numerical simulation was verified by physical model test. The flow field characteristics and pressure pulsation characteristics of the inlet and outlet regions of the impeller, the guide vane and the campaniform inlet conduit at different timing positions of the impeller under different flow rates were analyzed. The results show that the pressure coefficient distribution of the impeller inlet of the vertical axial flow pump device presents four high-pressure areas and four low-pressure areas with the rotation of the impeller. The pressure pulsation at the inlet and outlet of the impeller is mainly affected by the rotation of the impeller, and the main frequency is 4 times the rotation frequency amplitude of pressure pulsation decreases with the increase of flow rate. When the flow rate increased from 0.8 Qbep to 1.2 Qbep, the average velocity circulation at the guide vane outlet decreased by 12%; there is an obvious negative value region of the internal regularized helicity of the guide vane. When the flow rate increases from 0.8 Qbep to 1.2 Qbep, the amplitude of the pressure pulsation coefficient at the outlet of the guide vane decreases gradually, with a decrease of 94%. When the flow rate is 1.2 Qbep, the main frequency and the secondary frequency of the pressure pulsation are both low-frequency, with obvious low-frequency pulsation characteristics. Under the small flow condition of 0.8 Qbep, the outlet flow fluctuation of seven guide vane was 18.9% on average, and the flow variation of each guide vane was large. Under the optimal flow condition of 1.0 Qbep and large flow condition of 1.2 Qbep, the outlet flow fluctuation of 7 guide vane is 4.7% and 0.56% on average, and the flow change of each guide vane is stable. The outlet flow of the guide vane is mainly concentrated in two guide vane slots of the guide vane, and the flow ratios are 30.56%, 30.14% and 29.16% under three flow conditions, respectively. The research results provide a scientific basis for the optimization design and stable operation of vertical axial flow pump device.

Heat Insulation and Dissipation Processes in Nordic Seas in the Summer - Lin Gao; Jinping Zhao; Shimin Li; Xiutao Fan; Shixuan Liu (Journal of Ocean University of China, 2021)

Negative‐pressure irrigation improves water and fertilizer use efficiencies and fruit yield of greenhouse tomato on the North China Plain* - Yinkun Li; Xuzhang Xue; Fan Xu; Wenzhong Guo; Minjie Duan; Sen Lin; Youli Li; Zhan Wang (Irrigation and Drainage, 2021)
Water and fertilizer supply are the main factors limiting greenhouse vegetable production on the North China Plain. This study tested the hypothesis that negative‐pressure irrigation is advantageous for reducing water and fertilizer application compared with drip irrigation in a greenhouse. Three treatments (drip irrigation + optimal fertilizer [DOF], drip irrigation + Yamazaki tomato nutrient solution [DNS], and negative‐pressure irrigation + Yamazaki tomato nutrient solution [NNS]) were applied in a greenhouse tomato double‐cropping system conducted in consecutive spring–summer and autumn–winter seasons. Soil moisture content, nitrate‐nitrogen (N) concentration, fruit yield, total N uptake ( N u ), irrigation water productivity, and partial factor productivity of applied fertilizer were analysed. The seasonal variation of soil moisture and nitrate‐N contents in the 0–20‐cm soil layer for NNS treatment was stable. Nitrate‐N accumulated after the final harvest in the autumn–winter season of NNS treatment was significantly less than under DOF and DNS. Despite lower water and nutrient inputs, NNS showed higher N u and fruit yield than DOF and DNS. These results demonstrated that negative‐pressure irrigation can reduce irrigation water and nutrient inputs and nitrate‐N accumulation in the soil, and significantly improve water and fertilizer use efficiency in greenhouse‐grown tomato compared with those under drip irrigation.

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

Linking circular intronic RNA degradation and function in transcription by RNase H1 - Xiang Li; Jia-Lin Zhang; Yun-Ni Lei; Xiao-Qi Liu; Wei Xue; Yang Zhang; Fan Nan; Xiang Gao; Jun Zhang; Jia Wei; Li Yang; Ling-Ling Chen (Science China Life Sciences, 2021)

Dexmedetomidine Alleviates Lipopolysaccharide-Induced Hippocampal Neuronal Apoptosis via Inhibiting the p38 MAPK/c-Myc/CLIC4 Signaling Pathway in Rats - Yongping Chen; Lin Li; Jiuyan Zhang; Hailin Cui; Jiucheng Wang; Chuqiao Wang; Mingxian Shi; Honggang Fan (Molecular Neurobiology, 2021)

Rockburst response in hard rock owing to excavation unloading of twin tunnels at great depth - Fan Feng; Xibing Li; Lin Luo; Xingdong Zhao; Shaojie Chen; Ning Jiang; Wanpeng Huang; Yajun Wang (Bulletin of Engineering Geology and the Environment, 2021)

Experimental study on integrated and autonomous conductivity-temperature-depth (CTD) sensor applied for underwater glider - Bin Lv; Hai-lin Liu; Yi-fan Hu; Cheng-xuan Wu; Jie Liu; Hai-jing He; Jie Chen; Jian Yuan; Zhao-wen Zhang; Lin Cao; Hui Li (Marine Georesources & Geotechnology, 2021)

Size Effect and Anisotropy in a Transversely Isotropic Rock Under Compressive Conditions - Kaihui Li; Zhen-Yu Yin; Dongya Han; Xiang Fan; Rihong Cao; Hang Lin (Rock Mechanics and Rock Engineering, 2021)

Coupling effects of hydrological characteristics and nutrient load in sediments on the trophic state of reservoirs - Fan Xinyi; Yue Yihong; Mei Lin; Li Xiaoying; Hu Zhehui; Luo Jiajie; Liu Liu; Wang Fushun (Acta Geochimica, 2021)

MicroRNA-9 rescues hyperglycemia-induced endothelial cell dysfunction and promotes arteriogenesis through downregulating Notch1 signaling - Huang Chen; Zhihai Feng; Lieyou Li; Lin Fan (Molecular and Cellular Biochemistry, 2021)

Human papillomavirus prevalence among men who have sex with men in China: a systematic review and meta-analysis - Yiguo Zhou; Yi-Fan Lin; Lei Gao; Jianghong Dai; Ganfeng Luo; Lanying Li; Tanwei Yuan; Peiyang Li; Yuewei Zhan; Yanxiao Gao; Huachun Zou (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Dissociable plasticity of visual-motor system in functional specialization and flexibility in expert table tennis players - Dazhi Yin; Xuefei Wang; Xiaoyou Zhang; Qiurong Yu; Yu Wei; Qing Cai; Mingxia Fan; Lin Li (Brain Structure and Function, 2021)

Biosynthesis and preparation of phycoerythrobilin in recombinant Escherichia coli - Wenjun Li; Chengbo Ma; Baosheng Ge; Fan Zang; Song Qin; Jian Lin (Journal of Applied Phycology, 2021)

Exposed to Mercury-Induced Oxidative Stress, Changes of Intestinal Microflora, and Association between them in Mice - Yulan Zhao; Changming Zhou; Xiaoquan Guo; Guoliang Hu; Guyue Li; Yu Zhuang; Huabin Cao; Lin Li; Chonghong Xing; Caiying Zhang; Fan Yang; Ping Liu (Biological Trace Element Research, 2021)

Clinical phenotypes combined with saturation genome editing identifying the pathogenicity of BRCA1 variants of uncertain significance in breast cancer - Qiting Wan; Li Hu; Tao Ouyang; Jinfeng Li; Tianfeng Wang; Zhaoqing Fan; Tie Fan; Benyao Lin; Ye Xu; Yuntao Xie (Familial Cancer, 2021)

Neuroprotective Effect of Fractalkine on Radiation-induced Brain Injury Through Promoting the M2 Polarization of Microglia - Jiaojiao Wang; Huijiao Pan; Zhenyu Lin; Chunjin Xiong; Chunhua Wei; Huanhuan Li; Fan Tong; Xiaorong Dong (Molecular Neurobiology, 2021)
Radiation-induced brain injury (RIBI) is a serious complication in cancer patients receiving brain radiotherapy, and accumulating evidence suggests that microglial activation plays an important role in its pathogenesis. Fractalkine (FKN) is a crucial mediator responsible for the biological activity of microglia. In this study, the effect of FKN on activated microglial after irradiation and RIBI was explored and the underlying mechanisms were investigated. Our study demonstrated treatment with exogenous FKN diminished radiation-induced production of pro-inflammatory factors, such as IL1-β and TNFα, promoted transformation of microglial M1 phenotype to M2 phenotype after irradiation, and partially recovered the spatial memory of irradiated mice. Furthermore, upregulation of FKN/CX3CR1 via FKN lentivirus promoted radiation-induced microglial M2 transformation in the hippocampus and diminished the spatial memory injury of irradiated mice. Furthermore, while inhibiting the expression of CX3CR1, which exclusively expressed on microglia in the brain, the regulatory effect of FKN on microglia and cognitive ability of mice disappeared after radiation. In conclusion, the FKN could attenuate RIBI through the microglia polarization toward M2 phenotype by binding to CX3CR1 on microglia. Our study unveiled an important role of FKN/CX3CR1 in RIBI, indicating that promotion of FKN/CX3CR1 axis could be a promising strategy for the treatment of RIBI.

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Deep Placement of Nitrogen Fertilizer Affects Grain Yield, Nitrogen Recovery Efficiency, and Root Characteristics in Direct-Seeded Rice in South China - Yunyan Chen; Pingshan Fan; Zhaowen Mo; Leilei Kong; Hua Tian; Meiyang Duan; Lin Li; Liji Wu; Zaimang Wang; Xiangru Tang; Shenggang Pan (Journal of Plant Growth Regulation, 2021)

First report of natural infection of tomato by pepper mild mottle virus in China - Wen Peng Zhou; Yue Yue Li; Fan Li; Guan Lin Tan (Journal of Plant Pathology, 2021)

A drug-tunable Flt23k gene therapy for controlled intervention in retinal neovascularization - Jinying Chen; Fan-Li Lin; Jacqueline Y. K. Leung; Leilei Tu; Jiang-Hui Wang; Yu-Fan Chuang; Fan Li; Hsin-Hui Shen; Gregory J. Dusting; Vickie H. Y. Wong; Leszek Lisowski; Alex W. Hewitt; et al. (Angiogenesis, 2021)

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

KASP markers to detect sub-chromosomal arm translocations between 6VS of Haynaldia villosa and 6AS of wheat - Shujie Zhang; Chaolan Fan; Jiangtao Luo; Lei Huang; Die Xie; Yazhou Li; Zhuo Chen; Bo Jiang; Shunzong Ning; Zhongwei Yuan; Lin Huang; Lianquan Zhang; et al. (Euphytica, 2021)

Inversion analysis of the shear strength parameters for a high loess slope in the limit state - Xiao-yan Lin; Lin-fan Zhang; Ze Yang; Ping Li; Tong-lu Li (Journal of Mountain Science, 2021)

Adakitic rocks at convergent plate boundaries: Compositions and petrogenesis - Qiang Wang; Lulu Hao; Xiuzheng Zhang; Jinsheng Zhou; Jun Wang; Qiwei Li; Lin Ma; Long Zhang; Yue Qi; Gongjian Tang; Wei Dan; Jingjing Fan (Science China Earth Sciences, 2020)

The origin of arc basalts: New advances and remaining questions - Yigang Xu; Qiang Wang; Gongjian Tang; Jun Wang; Hongyan Li; Jinsheng Zhou; Qiwei Li; Yue Qi; Pingping Liu; Lin Ma; Jingjing Fan (Science China Earth Sciences, 2020)

Straw Incorporation Coupled with Deep Placement of Nitrogen Fertilizer Improved Grain Yield and Nitrogen Use Efficiency in Direct-Seeded Rice - Yunyan Chen; Pingshan Fan; Lin Li; Hua Tian; Umair Ashraf; Zhaowen Mo; Meiyang Duan; Qiantong Wu; Zheng Zhang; Xiangru Tang; Shenggang Pan (Journal of Soil Science and Plant Nutrition, 2020)

Lycium barbarum polysaccharide protects against Homocysteine-induced Vascular smooth muscle cell proliferation and phenotypic transformation via PI3K/Akt pathway - Minghao Zhang; Fan Li; Smritee Pokharel; Ting Ma; Xiuyu Wang; Yiyong Wang; Weirong Wang; Rong Lin (Journal of Molecular Histology, 2020)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Transcellular Model for Neutral and Charged Nanoparticles Across an In Vitro Blood–Brain Barrier - Lin Zhang; Jie Fan; Guanglei Li; Zhaokai Yin; Bingmei M. Fu (Cardiovascular Engineering and Technology, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

LMDS-1, a potential TrkB receptor agonist provides a safe and neurotrophic effect for early-phase Alzheimer’s disease - Chia-Hao Fan; Chia-Wei Lin; Hei-Jen Huang; Guey-Jen Lee-Chen; Ying-Chieh Sun; Wenwei Lin; Chiung-Mei Chen; Kuo-Hsuan Chang; Ming-Tsan Su; Hsiu Mei Hsieh-Li (Psychopharmacology, 2020)

Key factors affecting sustained business operations after an earthquake: a case study from New Beichuan, China, 2013–2017 - Fan Li; Lin Wang; Zhigang Jin; Lifang Huang; Bo Xia (Natural Hazards, 2020)

Preparation of high-purity R-phycoerythrin and R-phycocyanin from Pyropia yezoensis in membrane chromatography - Fan Zang; Song Qin; Chengbo Ma; Wenjun Li; Jian Lin (Journal of Applied Phycology, 2020)

Identification of Cyt2Ba from a New Strain of Bacillus thuringiensis and Its Toxicity in Bradysia difformis - Fan-Fan Wang; Shao-Xuan Qu; Jin-Sheng Lin; Hui-Ping Li; Li-Juan Hou; Ning Jiang; Xin Luo; Lin Ma (Current Microbiology, 2020)
Bradysia difformis is one of the most damaging pests in mushroom production in China. In this study, eight Bacillus thuringiensis strains were analyzed for insecticidal activity in B. difformis . The strain JW-1 showed the highest insecticidal activity against B. difformis larvae, but did not inhibit the mycelial growth of Pleurotus ostreatus and P. geesteranus . The 16S rRNA gene (1397 bp) and cyt2 gene (792 bp) were obtained from strain JW-1. The phylogenetic tree based on 16S rRNA gene and Cyt2 toxin showed that strain JW-1 was a member of B. thuringiensis and Cyt2 toxin belonged to Cyt2Ba toxin cluster. The Cyt2Ba toxin from strain JW-1 was overexpressed in E. coli as a fusion protein and the fusion protein (70 kDa) was purified by Ni-IDA affinity chromatography. The purified Cyt2Ba fusion protein was toxic to B. difformis larvae (LC 50 was 2.25 ng/mL). The identification of Cyt2Ba from strain JW-1 and confirmation of the insecticidal activity of Cyt2Ba in B. difformis provided a new means of biological control of the important pest in mushroom production.

Irregular structural networks of gray matter in patients with type 2 diabetes mellitus - Chuanlong Cao; Wanqing Liu; Qing Zhang; Jian-lin Wu; Yumei Sun; Danyang Li; Hongyu Fan; Feifei Wang (Brain Imaging and Behavior, 2020)

Psychroflexus maritimus sp. nov., isolated from coastal sediment - Yan-Lin Zhong; Rui Zhang; Xiao-Yu Zhang; Li-Xue Yu; Meng-Fan Zhao; Zong-Jun Du (Archives of Microbiology, 2020)

Simulation of oyster ecological carrying capacity in Sanggou Bay in the ecosystem context - Yaping Gao; Jianguang Fang; Fan Lin; Fengxue Li; Wenhao Li; Xiaoqin Wang; Meirong Du; Jinghui Fang; Weiwei Jiang; Hui Liu; Yitao Zhang; Junwei Wang; et al. (Aquaculture International, 2020)

Impaired Parahippocampal Gyrus–Orbitofrontal Cortex Circuit Associated with Visuospatial Memory Deficit as a Potential Biomarker and Interventional Approach for Alzheimer Disease - Lin Zhu; Zan Wang; Zhanhong Du; Xinyang Qi; Hao Shu; Duan Liu; Fan Su; Qing Ye; Xuemei Liu; Zheng Zhou; Yongqiang Tang; Ru Song; et al. (Neuroscience Bulletin, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Gastric smooth muscle cells manifest an abnormal phenotype in Parkinson’s disease rats with gastric dysmotility - Xiao-Lin Xiu; Li-Fei Zheng; Xiao-Yu Liu; Yan-Yan Fan; Jin-Xia Zhu (Cell and Tissue Research, 2020)

Assessment of nutrient and heavy metal contamination in surface sediments of the Xiashan stream, eastern Guangdong Province, China - Weijie Li; Shu Lin; Wencai Wang; Zhiwei Huang; Hailong Zeng; Xianglin Chen; Fantang Zeng; Zhongya Fan (Environmental Science and Pollution Research, 2020)

Optimum Design of a Seawater Intrusion Monitoring Scheme Based on the Image Quality Assessment Method - Yue Fan; Wenxi Lu; Tiansheng Miao; Jiuhui Li; Jin Lin (Water Resources Management, 2020)

Mixed secondary chromatin structure revealed by modeling radiation-induced DNA fragment length distribution - Wenzong Ma; Chenyang Gu; Lin Ma; Caoqi Fan; Chao Zhang; Yujie Sun; Cheng Li; Gen Yang (Science China Life Sciences, 2020)

Multiobjective optimization of the groundwater exploitation layout in coastal areas based on multiple surrogate models - Yue Fan; Wenxi Lu; Tiansheng Miao; Jiuhui Li; Jin Lin (Environmental Science and Pollution Research, 2020)

Influence of canopy and topographic position on soil moisture response to rainfall in a hilly catchment of Three Gorges Reservoir Area, China - Muxing Liu; Qiuyue Wang; Li Guo; Jun Yi; Henry Lin; Qing Zhu; Bihang Fan; Hailin Zhang (Journal of Geographical Sciences, 2020)

MiR-145 alleviates Hcy-induced VSMC proliferation, migration, and phenotypic switch through repression of the PI3K/Akt/mTOR pathway - Minghao Zhang; Fan Li; Xiuyu Wang; Jian Gong; Yushan Xian; Guan Wang; Zihan Zheng; Chenxu Shang; Bo Wang; Yanhao He; Weirong Wang; Rong Lin (Histochemistry and Cell Biology, 2020)

Integrated fate assessment of aromatic amines in aerobic sewage treatment plants - Lin Jun Zhou; Zhi Yi Rong; Wen Gu; De Ling Fan; Ji Ning Liu; Li Li Shi; Yan Hua Xu; Zhi Ying Liu (Environmental Monitoring and Assessment, 2020)
The fate and exposure of chemicals in sewage treatment plants (STPs) are major considerations in risk assessment and environmental regulation. The biodegradability and removal of seven aromatic amines were systematically evaluated using a three-tiered integrated method: a standard ready biodegradability test, an aerobic sewage treatment simulation method, and model prediction. In tier 1, the seven aromatic amines were not readily biodegraded after 28 days. In adapted aerobic active sludge, 4-isopropyl aniline, 2,4-diaminotoluene, and 4-nitroaniline among them exhibited the degradation half-life time less than 20 h, the other four aromatic amines exhibited persistent with degradation half-life of > 60 h. In tier 2 of the aerobic sewage treatment simulation testing, 2,4-diaminotoluene, 4-nitroaniline, and 4-isopropylaniline demonstrated moderately to high overall removal. Hydraulic retention time (HRT) affects the removal with the optimum HRT was determined to be 12 h to 24. 2,6-Dimethyl aniline, 2-chloro-4-nitroaniline, 2,6-diethylaniline, and 3,4-dichloroaniline were not removed during the test, indicting these four aromatic amines will enter surface water and hence pose a potential risk to aquatic ecology. Considering the lack of an STP model in China for regulation purposes, in tier 3, we developed a Chinese STP (aerobic) (abbreviated as C-STP(O)) model that reflects a universal scenario for China to predict the fate. The predicted degradation, volatilization, and absorption showed a close relationship to the physicochemical properties of the chemicals, and had same tendency with tier 2 simulation test. The prediction showed that biodegradation rather than absorption or volatilization was the main removal process of aromatic amines in aerobic STP. With the combination of modified kinetics test with C-STP (O) model, the chemical fate can be more accurately predicted than using only the readily biodegradation result.

Photoprotection capacity of microalgae improved by regulating the antenna size of light-harvesting complexes - Guang-Rong Hu; Yong Fan; Yan-Lin Zheng; Feng Xu; Lei Zhang; Fu-Li Li (Journal of Applied Phycology, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

Accounting for Mine Water in Coal Mining Activities and its Spatial Characteristics in China - Gang Lin; Donglin Dong; Xiang Li; Peiwei Fan (Mine Water and the Environment, 2020)

High prevalence and viremia of human pegivirus 2 in the HIV-infected population in Honghe Prefecture, Yunnan Province - Tianyi Li; Shixing Tang; Yingying Su; Zuoyi Bao; Xiaolin Wang; Yongjian Liu; Hanping Li; Jingwan Han; Zhichao Pei; Zhengwei Wan; Hang Fan; Yigang Tong; et al. (Archives of Virology, 2020)

Simulation of Yesso scallop, Patinopecten yessoensis, growth with a dynamic energy budget (DEB) model in the mariculture area of Zhangzidao Island - Weiwei Jiang; Fan Lin; Meirong Du; Jianguang Fang; Jinghui Fang; Yaping Gao; Xiaoqin Wang; Fengxue Li; Shipeng Dong; Xing Hou; Zengjie Jiang (Aquaculture International, 2020)

Feature extraction method based on spectral dimensional edge preservation filtering for hyperspectral image classification - Zhijian Li; Qing Zhu; Yaonan Wang; Zhenjun Zhang; Xianen Zhou; Anping Lin; Jingmin Fan (International Journal of Remote Sensing, 2020)

Applying Iterative Method to Solving High-Order Terms of Seafloor Topography - Diao Fan; Shanshan Li; Shuyu Meng; Yi Lin; Zhibin Xing; Chi Zhang; Junjun Yang; Xiaoyun Wan; Zhenhao Qu (Marine Geodesy, 2020)

Soil particle-size distribution and aggregate stability of new reconstructed purple soil affected by soil erosion in overland flow - Feng-Lin Zuo; Xiao-Yan Li; Xiao-Fan Yang; Yang Wang; Yu-Jun Ma; Yu-Han Huang; Chao-Fu Wei (Journal of Soils and Sediments, 2020)

Microbiological analysis of cadmium-contaminated sediments during biostabilization with indigenous sulfate-reducing bacteria - Weihua Peng; Xiaomin Li; Manli Lin; Wenhong Fan (Journal of Soils and Sediments, 2020)

Mechanistic examination of methimazole-induced hepatotoxicity in patients with Grave’s disease: a metabolomic approach - Xuesong Li; Jialin Yang; Shasha Jin; Yu Dai; Yujuan Fan; Xiaofang Fan; Zhigang Li; Jianhua Yang; Wai-Ping Yau; Haishu Lin; Weimin Cai; Xiaoqiang Xiang (Archives of Toxicology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Microfluidic tools for lipid production and modification: a review - Jin-Zheng Wang; Lin-Lin Zhu; Fan Zhang; Richard Ansah Herman; Wen-Jing Li; Xue-Jiao Zhou; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2019)

Molecular evolution and lineage-specific expansion of the PP2C family in Zea mays - Kai Fan; Shuna Yuan; Jie Chen; Yunrui Chen; Zhaowei Li; Weiwei Lin; Yongqiang Zhang; Jianping Liu; Wenxiong Lin (Planta, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Leaf Senescence can be Induced by Inhibition of Root Respiration - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zhu-yu Gu; Fan-jiang Zeng (Journal of Plant Growth Regulation, 2019)

Steroid-Enriched Fraction of Achyranthes bidentata Protects Amyloid β Peptide 1–40-Induced Cognitive Dysfunction and Neuroinflammation in Rats - Li-Wei Lin; Fan-Hsuan Tsai; Wan-Cheng Lan; Yih-Dih Cheng; Sheng-Chi Lee; Chi-Rei Wu (Molecular Neurobiology, 2019)

Evaluation of the eco-efficiency of four major urban agglomerations in coastal eastern China - Yufei Ren; Chuangling Fang; Xueqin Lin; Siao Sun; Guangdong Li; Beili Fan (Journal of Geographical Sciences, 2019)

CNOT3 contributes to cisplatin resistance in lung cancer through inhibiting RIPK3 expression - Lin Jing; Meng-En Zhai; Jian Cui; Xin-Yu Fan; Yuan-Yuan Cheng; Jian-Li Jiang; Zhi-Nan Chen (Apoptosis, 2019)

Network Analysis of Depression-Related Transcriptomic Profiles - Xiao Miao; Bin Fan; Rongqun Li; Shaoping Zhang; Honghuang Lin (NeuroMolecular Medicine, 2019)

Exosomal long non-coding RNAs: biological properties and therapeutic potential in cancer treatment - Jie Luo; Yan Xiong; Pei-fen Fu; En-chun Li; Lei Qu; Xiao Fan; Zhi-jian Cai; Ai-fu Lin (Journal of Zhejiang University-SCIENCE B, 2019)

Effects of intercropping with Bidens species plants on the growth and cadmium accumulation of Ziziphus acidojujuba seedlings - Qian Deng; Qunxian Deng; Yang Wang; Lei Li; Xingyu Long; Si Ren; Yue Fan; Lijin Lin; Hui Xia; Dong Liang; Jin Wang; Huifen Zhang; et al. (Environmental Monitoring and Assessment, 2019)

Fluids discrimination by ray-path elastic impedance inversion: A successful case from Sulige tight gas field - Da-Xing Wang; Hao-Fan Wang; Jin-Feng Ma; Yong-Gang Wang; Na Zhang; Lin Li (Applied Geophysics, 2019)

Two new steroids with cytotoxicity from the marine sponge Dactylospongia elegans collected from the South China Sea - Jing Li; Zhuo Wang; Fan Yang; Wei-Hua Jiao; Hou-Wen Lin; Shi-Hai Xu (Natural Product Research, 2019)

Ionomic profile and arsenic speciation in Semisulcospira cancellata, a freshwater shellfish from a mine-impacted river in China - Fan Du; Lin Wang; Zhaoguang Yang; Peng Liu; Deliang Li (Environmental Science and Pollution Research, 2019)

Trace metal pollution and ecological risk assessment in agricultural soil in Dexing Pb/Zn mining area, China - Junjie Hu; Boji Lin; Meiyi Yuan; Zhilang Lao; Kangming Wu; Yanyan Zeng; Zhihui Liang; Huiru Li; Yanliang Li; Dan Zhu; Junlong Liu; Hongbo Fan (Environmental Geochemistry and Health, 2019)

Cenozoic drainage evolution of the Rio Grande paleoriver recorded in detrital zircons in South Texas - Majie Fan; Elizabeth Brown; Lin Li (International Geology Review, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Ras-Related C3 Botulinum Toxin Substrate 1 Promotes Axonal Regeneration after Stroke in Mice - Lin Liu; Hui Yuan; Yanhua Yi; Edward C. Koellhoffer; Yashasvee Munshi; Fan Bu; Yi Zhang; Zhenggang Zhang; Louise D. McCullough; Jun Li (Translational Stroke Research, 2018)

Soil infiltration processes of different underlying surfaces in the permafrost region on the Tibetan Plateau - Guo-jie Hu; Li-ming Tian; Lin Zhao; Xiao-dong Wu; Ren Li; Tong-hua Wu; Xiao-fan Zhu; Er-ji Du; Zhi-wei Wang; Jun-ming Hao; Wang-ping Li; Song-he Wang (Hydrological Sciences Journal, 2018)

DELLA proteins negatively regulate dark-induced senescence and chlorophyll degradation in Arabidopsis through interaction with the transcription factor WRKY6 - Yongqiang Zhang; Zhongjuan Liu; Xiaoyun Wang; Jianfeng Wang; Kai Fan; Zhaowei Li; Wenxiong Lin (Plant Cell Reports, 2018)

The effect of temperature on the developmental rates of seedling emergence and leaf-unfolding in two dwarf bamboo species - Shuyan Lin; Lijuan Shao; Cang Hui; Hardev S. Sandhu; Tingting Fan; Li Zhang; Fang Li; Yulong Ding; Peijian Shi (Trees, 2018)

Effects of body mass index on the outcomes of in vitro fertilization in Chinese patients with polycystic ovary syndrome: a retrospective cohort study - Xiao-ming Pan; Zhong Lin; Nan Li; Jia-qi Wu; Dan-qing Chen; Yi-min Zhu; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2018)

Phthalate exposure and high blood pressure in adults: a cross-sectional study in China - Shao-hui Zhang; Ya-xin Shen; Lin Li; Tong-tong Fan; Yan Wang; Ning Wei (Environmental Science and Pollution Research, 2018)

Identification of antibiotic mycelia residue in protein rich feed using on near-infrared microscopy imaging - Yufei Lin; Zengling Yang; Hao Liang; Shouxue Li; Xia Fan; Zhiming Xiao (Food Additives & Contaminants: Part A, 2018)

Future changes of temperature and heat waves in Ontario, Canada - Zhong Li; Guohe Huang; Wendy Huang; Qianguo Lin; Renfei Liao; Yurui Fan (Theoretical and Applied Climatology, 2018)

Effects of Fluoride on Surface Structure of Primary Culture Leydig Cells in Mouse - Jian Li; Yan Shi; Hua Fan; Yanyan Li; Yuchen Zhu; Xijun Lin; Jianhai Zhang (Biological Trace Element Research, 2018)

Characterization of 25 microsatellite loci for the Guenther’s frog Hylarana guentheri - Weiwei Shao; Zhihua Lin; Xiaoli Fan; Guohua Ding; Li Wei (Conservation Genetics Resources, 2018)

Comparative Transcriptome Analysis Provides Insights into Differentially Expressed Genes and Long Non-Coding RNAs between Ovary and Testis of the Mud Crab (Scylla paramamosain) - Xiaolong Yang; Mhd Ikhwanuddin; Xincang Li; Fan Lin; Qingyang Wu; Yueling Zhang; Cuihong You; Wenhua Liu; Yinwei Cheng; Xi Shi; Shuqi Wang; Hongyu Ma (Marine Biotechnology, 2018)

Barcode index numbers expedite quarantine inspections and aid the interception of nonindigenous mealybugs (Pseudococcidae) - Jing-Mei Ren; Muhammad Ashfaq; Xu-Nan Hu; Jun Ma; Fan Liang; Paul D. N. Hebert; Li Lin; Jean François Germain; Muhammad Z. Ahmed (Biological Invasions, 2018)

Transcriptome Profiling Reveals the Important Role of Exogenous Nitrogen in Alleviating Cadmium Toxicity in Poplar Plants - Fan Zhang; Junqiang Li; Jinliang Huang; Lihua Lin; Xueqin Wan; Jinglong Zhao; Jifei Dong; Lingxia Sun; Qibing Chen (Journal of Plant Growth Regulation, 2017)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Efficacy and immunogenicity of recombinant swinepox virus expressing the truncated S protein of a novel isolate of porcine epidemic diarrhea virus - Xiaomin Yuan; Huixing Lin; Bin Li; Kongwang He; Hongjie Fan (Archives of Virology, 2017)

Laboratory assessment of bioleaching of shallow eutrophic sediment by immobilized photosynthetic bacteria - Shiyong Sun; Shenglan Fan; Kexuan Shen; Shen Lin; Xiaoqin Nie; Mingxue Liu; Faqin Dong; Jian Li (Environmental Science and Pollution Research, 2017)

Shear wave velocity prediction during CO2-EOR and sequestration in the Gao89 well block of the Shengli Oilfield - Lin Li; Jin-Feng Ma; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu (Applied Geophysics, 2017)

Stability Analysis of Clastic Rock Slope with Mudstone Interlayer Under Rainfall Infiltration - Yingzi Xu; Jian Li; Haoran Fan; Lihua Chen; Yanlin Zhao; Lin Li (Geotechnical and Geological Engineering, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Genome-wide identification, phylogeny and expression analyses of SCARECROW-LIKE(SCL) genes in millet (Setaria italica) - Hongyun Liu; Jiajia Qin; Hui Fan; Jinjin Cheng; Lin Li; Zheng Liu (Physiology and Molecular Biology of Plants, 2017)

N-Myc Downstream-Regulated Gene 2 (Ndrg2) Is Involved in Ischemia–Hypoxia-Induced Astrocyte Apoptosis: a Novel Target for Stroke Therapy - Yu-Long Ma; Li-xia Zhang; Guang-lin Liu; Yanhong Fan; Ye Peng; Wu-Gang Hou (Molecular Neurobiology, 2017)

Cloning and characterization of DoMYC2 from Dendrobium officinale - Yanfang Zhu; Cancan Meng; Liqin Zhu; Dahui Li; Qing Jin; Cheng Song; Yongping Cai; Honghong Fan; Yi Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Intelligent diagnosis of jaundice with dynamic uncertain causality graph model - Shao-rui Hao; Shi-chao Geng; Lin-xiao Fan; Jia-jia Chen; Qin Zhang; Lan-juan Li (Journal of Zhejiang University-SCIENCE B, 2017)

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

A new isoquinolone alkaloid from an endophytic fungus R22 of Nerium indicum - Yang-min Ma; Ke Qiao; Yang Kong; Meng-yun Li; Lin-xin Guo; Zhi Miao; Chao Fan (Natural Product Research, 2017)

Associations Between Hepatic Functions and Plasma Amyloid-Beta Levels—Implications for the Capacity of Liver in Peripheral Amyloid-Beta Clearance - Ye-Ran Wang; Qing-Hua Wang; Tao Zhang; Yu-Hui Liu; Xiu-Qing Yao; Fan Zeng; Jing Li; Fa-Yin Zhou; Lin Wang; Jia-Chuan Yan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Effects of pre-pregnancy body mass index and gestational weight gain on neonatal birth weight - Meng-kai Du; Li-ya Ge; Meng-lin Zhou; Jun Ying; Fan Qu; Min-yue Dong; Dan-qing Chen (Journal of Zhejiang University-SCIENCE B, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

The Chlorophyll a Fluorescence Characteristic in Different Types of Leaf Senescence in Alhagi sparsifolia - Gang-Liang Tang; Xiang-Yi Li; Li-Sha Lin; Zhu-Yu Gu; Fan-Jiang Zeng (Journal of Plant Growth Regulation, 2016)

A novel bocavirus from domestic mink, China - Shixing Yang; Yan Wang; Wang Li; Zhaobin Fan; Lili Jiang; Yuan Lin; Xingli Fu; Quan Shen; Zixuan Sun; Xiaochun Wang; Xutao Deng; Wen Zhang; et al. (Virus Genes, 2016)

Secondary metabolites from marine-derived Streptomyces antibioticus strain H74-21 - Shuna Fu; Fan Wang; Hongyu Li; Yixuan Bao; Yu Yang; Huifang Shen; Birun Lin; Guangxiong Zhou (Natural Product Research, 2016)

Early detection of white mold caused by Sclerotinia sclerotiorum in potato fields using real-time PCR - Mohammad Reza Ojaghian; Jing-Ze Zhang; Fan Zhang; Wen Qiu; Xiao-Lin Li; Guan-Lin Xie; Shui-Jin Zhu (Mycological Progress, 2016)

Erratum to: Initiation and evolution of the South China Sea: an overview - Wei-dong Sun; Chiou-ting Lin; Chan-chan Zhang; Yong-bin Hu; Ming-xing Ling; Xing Ding; Cong-ying Li; He Li; Kai Wu; Wei-ming Fan (Acta Geochimica, 2016)

Impact of Heat Shock Protein A 12B Overexpression on Spinal Astrocyte Survival Against Oxygen-Glucose-Serum Deprivation/Restoration in Primary Cultured Astrocytes - Xun Xia; Yuan Ma; Li-bin Yang; Jing-ming Cheng; Tao Yang; Ke-xia Fan; Yun-ming Li; En-yu Liu; Lin Cheng; Hai-dong Huang; Jian-wen Gu; Yong-qin Kuang (Journal of Molecular Neuroscience, 2016)

Luman recruiting factor is involved in stromal cell proliferation during decidualization in mice - Xiao Li; Pengfei Lin; Fenglei Chen; Nan Wang; Fan Zhao; Aihua Wang; Yaping Jin (Cell and Tissue Research, 2016)

Hypocrol A, a new tyrosol derivative from a sponge-derived strain of the fungus Hypocrea koningii - Li-Jian Ding; Wei Yuan; Ying-Xin Li; Xiao-Jian Liao; Huan Sun; Qi Peng; Bing-Nan Han; Hou-Wen Lin; Zhi-Yong Li; Fan Yang; Shi-Hai Xu (Natural Product Research, 2016)

From folding to transpressional faulting: the Cenozoic Fusha structural belt in front of the Western Kunlun Orogen, northwestern Tibetan Plateau - Cong Wang; Xiao-Gan Cheng; Han-Lin Chen; Kang Li; Xiao-Gen Fan; Chun-Yang Wang (International Journal of Earth Sciences, 2016)

Different causes of photosynthetic decline and water status in different stages of girdling in Alhagi sparsifolia Shap. (Fabaceae) - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Fan-jiang Zeng (Brazilian Journal of Botany, 2016)

Geophysical monitoring technology for CO2 sequestration - Jin-Feng Ma; Lin Li; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu; Ling-Yun Jia; Shu-Hai Zhang (Applied Geophysics, 2016)

Sequences analyses and expression profiles in tissues and embryos of Japanese flounder (Paralichthys olivaceus) PRDM1 - Conghui Liu; Wei Liu; Lin Fan; Jinxiang Liu; Peizhen Li; Wei Zhang; Jinning Gao; Zan Li; Quanqi Zhang; Xubo Wang (Fish Physiology and Biochemistry, 2016)

Characteristics, sources and health risk assessment of toxic heavy metals in PM2.5 at a megacity of southwest China - Youping Li; Zhisheng Zhang; Huifang Liu; Hong Zhou; Zhongyu Fan; Mang Lin; Dalei Wu; Beicheng Xia (Environmental Geochemistry and Health, 2016)

Identification and Evaluation of Reliable Reference Genes in the Medicinal Fungus Shiraia bambusicola - Liang Song; Tong Li; Li Fan; Xiao-Ye Shen; Cheng-Lin Hou (Current Microbiology, 2016)

Association between occupational stressors and type 2 diabetes among Chinese police officers: a 4-year follow-up study in Tianjin, China - Hao Yu; Jin-chuan Liu; Ya-jiao Fan; Chen Li; Li-xin Zhang; Xi Chen; Song Yue; Wen-li Lu; Xi-lin Yang; Nai-jun Tang (International Archives of Occupational and Environmental Health, 2016)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Impact of phloem girdling on water status in desert plants Alhagi sparsifolia Shap. (Fabaceae) and Karelinia Caspica (Pall.) Less. (Asteraceae) - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zi-chun Guo; Chang-jun Li; Hui Guo; Fan-jiang Zeng (Brazilian Journal of Botany, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

Association between vitamin D receptor gene polymorphism (TaqI) and obesity in Chinese population - HUI-RU FAN; LI-QUN LIN; HAO MA; YING LI; CHANG-HAO SUN (Journal of Genetics, 2015)

Adverse symptoms with anti-TNF-alpha therapy in inflammatory bowel disease: systematic review and duration-response meta-analysis - Fan Wang; Xue Lin; Qiu Zhao; Jin Li (European Journal of Clinical Pharmacology, 2015)

Altered microRNA Expression in Peripheral Blood Mononuclear Cells from Young Patients with Schizophrenia - Hui-min Fan; Xin-yang Sun; Wei Niu; Lin Zhao; Qiao-Li Zhang; Wan-shuai Li; Ai-fang Zhong; Li-yi Zhang; Jim Lu (Journal of Molecular Neuroscience, 2015)

Saussurea medusa, source of the medicinal herb snow lotus: a review of its botany, phytochemistry, pharmacology and toxicology - Jia-Yi Fan; Hu-Biao Chen; Lin Zhu; Hong-Li Chen; Zhong-Zhen Zhao; Tao Yi (Phytochemistry Reviews, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

Diacylglycerol Kinase (DGK) Inhibitor II (R59949) Could Suppress Retinal Neovascularization and Protect Retinal Astrocytes in an Oxygen-Induced Retinopathy Model - Lu Yang; Yue Xu; Weihua Li; Boyu Yang; Shanshan Yu; Huanjiao Zhou; Cheng Yang; Fan Xu; Jun Wang; Yi Gao; Yongsheng Huang; Lin Lu; et al. (Journal of Molecular Neuroscience, 2015)

Risk assessment of heavy metals in air, water, vegetables, grains, and related soils irrigated with biogas slurry in Taihu Basin, China - Bo Bian; Ling Jun Zhou; Lei Li; Lin Lv; Ya Min Fan (Environmental Science and Pollution Research, 2015)

Effects of growth conditions on the production of neurotoxin 2,4-diaminobutyric acid (DAB) in Microcystis aeruginosa and its universal presence in diverse cyanobacteria isolated from freshwater in China - Hua Fan; Jiangbing Qiu; Lin Fan; Aifeng Li (Environmental Science and Pollution Research, 2015)

Three-dimensional tensor controlled-source electromagnetic modeling based on the vector finite-element method - Ying-Cai Hu; Tong-Lin Li; Cui-Song Fan; Da-Yong Wang; Jian-Ping Li (Applied Geophysics, 2015)

Lipophilic shellfish toxins in Dinophysis caudata picked cells and in shellfish from the East China Sea - Aifeng Li; Geng Sun; Jiangbing Qiu; Lin Fan (Environmental Science and Pollution Research, 2015)

A review of seasonal climate prediction research in China - Huijun Wang; Ke Fan; Jianqi Sun; Shuanglin Li; Zhaohui Lin; Guangqing Zhou; Lijuan Chen; Xianmei Lang; Fang Li; Yali Zhu; Hong Chen; Fei Zheng (Advances in Atmospheric Sciences, 2015)

Genome re-sequencing suggested a weedy rice origin from domesticated indica-japonica hybridization: a case study from southern China - Jie Qiu; Jinwen Zhu; Fei Fu; Chu-Yu Ye; Weidi Wang; Linfeng Mao; Zhangxiang Lin; Li Chen; Haiqiang Zhang; Longbiao Guo; Shen Qiang; Yongliang Lu; et al. (Planta, 2014)

The Association Between Single Nucleotide Polymorphisms of GSK 3β Gene and Sporadic Alzheimer’s Disease in a Cohort of Southern Chinese Han Population - Jing Li; Fan Zeng; Juan Deng; Jie Zhu; Lin Li; Tao Zhang; Juan Liu; Li–Li Zhang; Chang-Yue Gao; Meng Zhang; Zhi-Qiang Xu; Hua-Dong Zhou; et al. (Neurotoxicity Research, 2014)

Comparison of interpolation methods for estimating spatial distribution of precipitation in Ontario, Canada - S. Wang; G. H. Huang; Q. G. Lin; Z. Li; H. Zhang; Y. R. Fan (International Journal of Climatology, 2014)
In this study, different interpolation techniques in a geographical information system ( GIS ) environment are analysed and compared for estimating the spatial distribution of precipitation in the province of Ontario, Canada. A high‐resolution regional climate modelling system [Providing Regional Climates for Impacts Studies ( PRECIS )] is used to simulate the present (1961–1990) and future (2071–2100) precipitation events for 12 meteorological stations over Ontario. The results verify that for the present case PRECIS simulates well the precipitation events when compared with observed data. The future precipitation events can be projected after the validation of PRECIS . Six interpolation methods are then used to generate spatial distribution of precipitation based on the projections of future precipitation of 12 meteorological stations; they include inverse distance weighting ( IDW ), global polynomial interpolation ( GPI ), local polynomial interpolation ( LPI ), radial basis functions ( RBF ), ordinary kriging ( OK ), and universal kriging ( UK ). Cross‐validation is applied to evaluate the accuracy of interpolation methods in terms of the root mean square error ( RMSE ). The results indicate that LPI is the optimal method with the least RMSE for interpolating the PRECIS precipitation. LPI is then used to analyse spatial variations of the average annual precipitation for the period of 2071–2100 over Ontario.

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

The study of regulatory effects of Pdx-1, MafA and NeuroD1 on the activity of porcine insulin promoter and the expression of human islet amyloid polypeptide - Xiao-Dan Liu; Jin-Xue Ruan; Ji-Han Xia; Shu-Lin Yang; Jun-Hua Fan; Kui Li (Molecular and Cellular Biochemistry, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

Variations of DNA methylation and genes expression for brown fiber during its development process - Zhenpeng Li; Tingchun Li; Honghong Fan; Ning Guo; Xu Sun; Yongping Cai; Yi Lin (Acta Physiologiae Plantarum, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

miR-27b targets LIMK1 to inhibit growth and invasion of NSCLC cells - Li Wan; Lin Zhang; Kai Fan; Jianjun Wang (Molecular and Cellular Biochemistry, 2014)

Photosystem II activity of typical desert plant Alhagi sparsifolia Sharp.: response to exposure to natural light after being kept in shade - Lei Li; Xiang-yi Li; Xin-wen Xu; Li-sha Lin; Fan-jiang Zeng; Feng-li Chen (Trees, 2014)

Recurrent breakdown of Late Permian reef communities in response to episodic volcanic activities: evidence from southern Guizhou in South China - Guanghui Fan; Yongbiao Wang; Stephen Kershaw; Guoshan Li; Zheng Meng; Qixiang Lin; Zaiming Yuan (Facies, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

Genetic diversity analysis of yams (Dioscorea spp.) cultivated in China using ISSR and SRAP markers - Zhi Gang Wu; Xiao Xia Li; Xin Chun Lin; Wu Jiang; Zheng Ming Tao; Nitin Mantri; Chuan Yin Fan; Xiao Qing Bao (Genetic Resources and Crop Evolution, 2014)

Unraveling the complex genetic model for cystic fibrosis: pleiotropic effects of modifier genes on early cystic fibrosis-related morbidities - Weili Li; David Soave; Melissa R. Miller; Katherine Keenan; Fan Lin; Jiafen Gong; Theodore Chiang; Anne L. Stephenson; Peter Durie; Johanna Rommens; Lei Sun; Lisa J. Strug (Human Genetics, 2014)

Effects of high temperature on the chlorophyll a fluorescence of Alhagi sparsifolia at the southern Taklamakan Desert - Lei Li; Xiang-Yi Li; Xin-Wen Xu; Li-Sha Lin; Fan-Jiang Zeng (Acta Physiologiae Plantarum, 2014)

Antibacterial mechanisms of methyl gallate against Ralstonia solanacearum - Wan-Wan Fan; Gao-Qing Yuan; Qi-Qin Li; Wei Lin (Australasian Plant Pathology, 2014)

Changes in soil organic carbon and total nitrogen stocks after conversion of meadow to cropland in Northeast China - Fan Ding; Ya-Lin Hu; Lu-Jun Li; Ang Li; Shengwei Shi; Pei-Yong Lian; De-Hui Zeng (Plant and Soil, 2013)

Piperine potentiates the antidepressant-like effect of trans-resveratrol: involvement of monoaminergic system - Wu Huang; Zhuoyou Chen; Qiandong Wang; Mengmeng Lin; Shujuan Wu; Qizhi Yan; Fan Wu; Xuefeng Yu; Xupei Xie; Gaowen Li; Ying Xu; Jianchun Pan (Metabolic Brain Disease, 2013)

Identification of MHC class I sequences in four species of Macaca of China - Xiang Yan; Aixue Li; Lin Zeng; Yuhua Cao; Jianbin He; Longbao Lv; Lihua Sui; Huahu Ye; Junwen Fan; Xiaoxia Cui; Zhaozeng Sun (Immunogenetics, 2013)

Forward simulation of root’s ground penetrating radar signal: simulator development and validation - Li Guo; Henry Lin; Bihang Fan; Xihong Cui; Jin Chen (Plant and Soil, 2013)

Impact of root water content on root biomass estimation using ground penetrating radar: evidence from forward simulations and field controlled experiments - Li Guo; Henry Lin; Bihang Fan; Xihong Cui; Jin Chen (Plant and Soil, 2013)

Study on the quantitative structure–toxicity relationships of aconitine compounds basing on PCA-ANN method - Zuo-jing Li; Lin Wang; Jing Peng; Xin-li Yan; Fan-hao Meng (Medicinal Chemistry Research, 2013)

Polycyclic aromatic hydrocarbons in water, sediment and soil of the Songhua River Basin, China - Wan-Li Ma; Li-Yan Liu; Hong Qi; Zi-Feng Zhang; Wei-Wei Song; Ji-Min Shen; Zhong-Lin Chen; Nan-Qi Ren; Josey Grabuski; Yi-Fan Li (Environmental Monitoring and Assessment, 2013)

Evaluation of the sedative and hypnotic effects of Eucommiol in Eucommia - Xin Li; Wenxue Zhu; Lipeng Yang; Dongqing Fei; Jinling Fan; Lin Du; Yan Liu (Natural Product Research, 2013)

Functional analyses of a flavonol synthase–like gene from Camellia nitidissima reveal its roles in flavonoid metabolism during floral pigmentation - Xing-Wen Zhou; Zheng-Qi Fan; Yue Chen; Yu-Lin Zhu; Ji-Yuan Li; Heng-Fu Yin (Journal of Biosciences, 2013)

Analysis of artificial corner reflector’s radar cross section: a physical optics perspective - Xin-Jian Shan; Jing-Yuan Yin; Dan-Lin Yu; Cheng-Fan Li; Jun-Juan Zhao; Gui-Fang Zhang (Arabian Journal of Geosciences, 2013)

DNA methylation alterations of upland cotton (Gossypium hirsutum) in response to cold stress - Hong Hong Fan; Jun Wei; Ting Chun Li; Zheng Peng Li; Ning Guo; Yong Ping Cai; Yi Lin (Acta Physiologiae Plantarum, 2013)

Association between XRCC1 and XRCC3 polymorphisms and colorectal cancer risk: a meta-analysis of 23 case–control studies - Li Liu; Lin Miao; Guozhong Ji; Fulin Qiang; Zheng Liu; Zhining Fan (Molecular Biology Reports, 2013)

Development of a core set of single-locus SSR markers for allotetraploid rapeseed (Brassica napus L.) - Haitao Li; Muhammad Younas; Xiaofeng Wang; Xuemin Li; Lin Chen; Bo Zhao; Xun Chen; Jinsong Xu; Fan Hou; Baohua Hong; Gang Liu; Hongyang Zhao; et al. (Theoretical and Applied Genetics, 2013)

Variations in silicate concentration affecting photosynthetic carbon fixation by spring phytoplankton assemblages in surface water of the Strait of Malacca - Gang Li; Qiang Lin; Pingping Shen; Guangyan Ni; Xingyu Song; Shengfu Wang; Yanzhi Fan; Liangmin Huang; Yehui Tan (Acta Oceanologica Sinica, 2013)

Recent advances in the study of testicular nuclear receptor 4 - Xian-fan Ding; Shi-cheng Yu; Bi-de Chen; Shin-jen Lin; Chawnshang Chang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2013)

Construction and analysis of different expression cDNA libraries in Rehmannia glutinosa plants subjected to continuous cropping - Yan Hui Yang; Zhong Yi Zhang; Hua Min Fan; Yi Dan Zhao; Ming Jie Li; Juan Li; Jun Ying Chen; Wen Xiong Lin; Xin Jian Chen (Acta Physiologiae Plantarum, 2013)

Establishment of SYBR green-based qPCR assay for rapid evaluation and quantification for anti-Hantaan virus compounds in vitro and in suckling mice - Fei Wei; Jin-lin Li; Jia-xin Ling; Liang-Jun Chen; Ning Li; Yuan-Yuan Liu; Fan Luo; Hai-Rong Xiong; Wei Hou; Zhan-Qiu Yang (Virus Genes, 2013)

Application of ground penetrating radar for coarse root detection and quantification: a review - Li Guo; Jin Chen; Xihong Cui; Bihang Fan; Henry Lin (Plant and Soil, 2013)

Sarpogrelate inhibits the expression of ICAM-1 and monocyte–endothelial adhesion induced by high glucose in human endothelial cells - Ying Su; Nan Mao; Min Li; Xia Dong; Fan-Zhen Lin; Ying Xu; Yan-Bo Li (Molecular and Cellular Biochemistry, 2013)

Isolation and characterization of a stress responsive small GTP-binding protein AhRabG3b in peanut (Arachis hypogaea L.) - Jiong-Ming Sui; Rui Li; Qian-Cheng Fan; Lin Song; Chun-Hua Zheng; Jing-Shan Wang; Li-Xian Qiao; Shan-Lin Yu (Euphytica, 2013)

Biodegradation of poly(ε-caprolactone) (PCL) by a new Penicillium oxalicum strain DSYD05-1 - Fan Li; Dan Yu; Xiumei Lin; Dongbo Liu; Hongmei Xia; Shan Chen (World Journal of Microbiology and Biotechnology, 2012)

Simulation of Wind Circulation and Pollutant Diffusion Over the Pearl River Delta Region - Li-Ping Zeng; Wen-Shi Lin; Qi Fan; Ye-Rong Feng (Environmental Modeling & Assessment, 2012)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Retrieval of aerosol optical depth over bright targets in the urban areas of North China during winter - ShenShen Li; LiangFu Chen; JinHua Tao; Dong Han; ZhongTing Wang; Lin Su; Meng Fan; Chao Yu (Science China Earth Sciences, 2012)

Erratum to: Identification of C4 photosynthesis metabolism and regulatory-associated genes in Eleocharis vivipara by SSH - Taiyu Chen; Rongjian Ye; Xiaolei Fan; Xianghua Li; Yongjun Lin (Photosynthesis Research, 2012)

Cool seasons are related to poor prognosis in patients with infective endocarditis - Su-Jung Chen; Tze-Fan Chao; Yenn-Jiang Lin; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Tsui-Lieh Hsu; Wen-Chung Yu; Hsin-Bang Leu; Shih-Lin Chang; Shih-Ann Chen (International Journal of Biometeorology, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Impacts of global emissions of CO, NO x , and CH4 on China tropospheric hydroxyl free radicals - Mingfeng Su; Yunping Lin; Xinqiang Fan; Li Peng; Chunsheng Zhao (Advances in Atmospheric Sciences, 2012)

Effects of exogenous nitric oxide on antioxidation and DNA methylation of Dendrobium huoshanense grown under drought stress - Honghong Fan; Tingchun Li; Lei Guan; Zhengpeng Li; Ning Guo; Yongping Cai; Yi Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

The accumulation of pigment in fiber related to proanthocyanidins synthesis for brown cotton - Tingchun Li; Honghong Fan; Zhengpeng Li; Jun Wei; Yi Lin; Yongping Cai (Acta Physiologiae Plantarum, 2012)

Two species of Lirula on Abies from Yunnan, Southwest China - Li Fan; Ying-Ren Lin; Shuang Wang; Cheng-Lin Hou (Mycological Progress, 2012)

Experimental Pathogenicity of a Clinical Isolate of Trichosporon dermatis in a Murine Model - Ying-Ping Lin; Yan-Ping Yang; Wen-Ming Huang; Yong-Hua Chen; Shun-Fan Li; Yi-Ming Fan (Mycopathologia, 2011)

Overexpression of osteopontin in hepatocellular carcinoma and its relationships with metastasis, invasion of tumor cells - Fan Lin; YuYuan Li; Jie Cao; ShaoFeng Fan; JiFeng Wen; GuangHui Zhu; Hong Du; YanXiao Liang (Molecular Biology Reports, 2011)

Retinol, vitamins A, C, and E and breast cancer risk: a meta-analysis and meta-regression - Hu Fulan; Jiang Changxing; Wang Yi Baina; Zhang Wencui; Lin Chunqing; Wang Fan; Li Dandan; Sun Dianjun; Wang Tong; Pang Da; Zhao Yashuang (Cancer Causes & Control, 2011)

Identification of C4 photosynthesis metabolism and regulatory-associated genes in Eleocharis vivipara by SSH - Taiyu Chen; Rongjian Ye; Xiaolei Fan; Xianghua Li; Yongjun Lin (Photosynthesis Research, 2011)

Relationship between temperature change and the requirement for a permanent pacemaker implantation in bradyarrhythmias - I-Fan Liu; Shih-Lin Chang; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Chi-Woon Kong; Tsu-Juey Wu; Chern-En Chiang; Shih-Ann Chen; Yenn-Jiang Lin (International Journal of Biometeorology, 2011)

Cellular Toxicity of TiO2 Nanoparticles in Anatase and Rutile Crystal Phase - Chan Jin; Ying Tang; F. Guang Yang; X. Lin Li; Shan Xu; X. Yan Fan; Y. Ying Huang; Y. Ji Yang (Biological Trace Element Research, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Inhibition of ATIR by shRNA prevents collagen synthesis in hepatic stellate cells - Peihong Dong; Fujun Yu; Xufei Fan; Zhuo Lin; Yongping Chen; Ji Li (Molecular and Cellular Biochemistry, 2010)

Study on the quantitative structure–toxicity relationships of benzoic acid derivatives in rats via oral LD50 - Ye-zhi Sun; Zuo-jing Li; Xin-li Yan; Lin Wang; Fan-hao Meng (Medicinal Chemistry Research, 2009)

Modifier gene study of meconium ileus in cystic fibrosis: statistical considerations and gene mapping results - Ruslan Dorfman; Weili Li; Lei Sun; Fan Lin; Yongqian Wang; Andrew Sandford; Peter D. Paré; Karen McKay; Hana Kayserova; Tereza Piskackova; Milan Macek; Kamila Czerska; et al. (Human Genetics, 2009)

Evidence for marine transgression between 7500–5400BC at the Luotuodun Site in Yixing, Jiangsu Province - Lan Li; Cheng Zhu; Liugen Lin; Quanhong Zhao; Gongyue Shi; Chaogui Zheng; Chao Fan (Journal of Geographical Sciences, 2009)

Numerical Simulations on the Effect of Sea–Land Breezes on Atmospheric Haze over the Pearl River Delta Region - Chen Xun-lai; Feng Ye-rong; Li Jiang-nan; Lin Wen-shi; Fan Shao-jia; Wang An-yu; Fong Soikun; Lin Hui (Environmental Modeling & Assessment, 2009)

Molecular characterisation of two plasmids from paulownia witches’-broom phytoplasma and detection of a plasmid-encoded protein in infected plants - Cai-Li Lin; Tao Zhou; Huai-Fang Li; Zai-Feng Fan; Yong Li; Chun-Gen Piao; Guo-Zhong Tian (European Journal of Plant Pathology, 2009)

GTPase activity is not essential for the interferon-inducible MxA protein to inhibit the replication of hepatitis B virus - Zhijian Yu; Zhanhui Wang; Jinjun Chen; Hui Li; Zhanzhou Lin; Fan Zhang; Yuanping Zhou; Jinlin Hou (Archives of Virology, 2008)

Spatial distribution and sources of polycyclic aromatic hydrocarbons (PAHs) in soils from typical oil-sewage irrigation area, Northeast China - Xiaojun Li; Peijun Li; Xin Lin; Zongqiang Gong; Shuxiu Fan; Le Zheng; E. A. Verkhozina (Environmental Monitoring and Assessment, 2008)

Involvement of GlnK, a PII protein, in control of nitrogen fixation and ammonia assimilation in Pseudomonas stutzeri A1501 - Sheng He; Ming Chen; Zhihong Xie; Yongliang Yan; Hongquan Li; Ying Fan; Shuzhen Ping; Min Lin; Claudine Elmerich (Archives of Microbiology, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)

Mapping of genome-wide resistance gene analogs (RGAs) in maize (Zea mays L.) - Wenkai Xiao; Jing Zhao; Shengci Fan; Lin Li; Jinrui Dai; Mingliang Xu (Theoretical and Applied Genetics, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Cloning and identification of partial DNA fragment for the B mating-type factor in Lentinula edodes using degenerate PCR - An-Zheng Li; Xue-Feng Xu; Fan-Xue Lin; Shui-Ming Cheng; Fang-Can Lin (World Journal of Microbiology and Biotechnology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Numerical comparison study of cloud microphysical parameterization schemes for a moderate snowfall event in North China - W. S. Lin; C.-H. Sui; C. Bueh; A. Wang; S. Fan; C. Wu; S. Fong; J. Li; J. Meng (Meteorology and Atmospheric Physics, 2007)

Screening and identification of vascular-endothelial-cell-specific binding peptide in gastric cancer - Shuhui Liang; Tao Lin; Jie Ding; Yanglin Pan; Dongmei Dang; Changcun Guo; Min Zhi; Pengtao Zhao; Li Sun; Liu Hong; Yongquan Shi; Liping Yao; et al. (Journal of Molecular Medicine, 2006)

A new dihydroisocoumarin from the rhizomes of Notopterygium forbesii - Yan-Hui Li; Fan Luo; Shu-Lin Peng; Jian Liang; Li-Sheng Ding (Natural Product Research, 2006)

Construction and characterization of a transformation-competent artificial chromosome (TAC) library ofZizania latifolia (Griseb.) - Fan Na Kong; Shao Mei Jiang; Li Xue Shi; Cheng Li Song; Min De Jin; Shao Lin Jiang; Manli Weng; Bin Wang (Plant Molecular Biology Reporter, 2006)

The role of halogen substitution in classical cannabinoids: A CB1 pharmacophore model - Spyros P. Nikas; Jolanta Grzybowska; Demetris P. Papahatjis; Avgui Charalambous; Ali R. Banijamali; Ravi Chari; Pusheng Fan; Therapia Kourouli; Sonyuan Lin; Albert J. Nitowski; Gilbert Marciniak; Yan Guo; et al. (The AAPS Journal, 2004)

Erratum: Cloning and sequencing of the phycocyanin gene from Spirulina maxima and its evolutionary analysis - Ping Yu; Jian-Rong Li; Pei-Lin Cen; Song Qin; Fan Lin (Journal of Applied Phycology, 2003)

RAPD markers in diversity detection and variety identification of Tibetan hulless barley - Zeng Yu; Lan Li-Qiong; Luo Huan; Bai Jie; Yang Man-Ye; Miao Chen; Cai Ying-Fan; Qiang Xiao-Lin; Chen Fang (Plant Molecular Biology Reporter, 2002)